AAV-induced re-expression of Dp71 in retinal Muller glial cells recovers electroretinographic responses in Dp71-null mice - Salgueiro Barboni, Mirella Telles; Vaillend, Cyrille; Joachimsthaler, Anneka; Liber, Andre; Khabou, Hanen; Roux, Michel J.; Vignaud, Lucile; Dalkara, Deniz; Guillonneau, Xavier; Ventura, Dora; Rendon, Alvaro; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

Absence of ocular interaction in flicker ERG responses reflecting cone opponent and luminance signals - Salgueiro Barboni, Mirella Telles; Ventura, Dora Fix; Kremers, Jan (Documenta Ophthalmologica, 2010)
The aim of the study was to investigate whether there is an ocular interaction in the flicker ERG responses reflecting luminance and cone opponency in normal human subjects. Flicker ERGs were recorded from one dilated eye of 10 healthy volunteers. Each subject was tested twice: once with and once without occluding the opposite eye. Red and green LEDs were modulated in counterphase in a Ganzfeld stimulator. ERG responses were recorded for different ratios of the modulation in the red and green LEDs and at 12 and 36 Hz. The amplitudes and phases of the fundamental components were compared between the conditions with and without occlusion. The 12-Hz flicker ERGs reflected activity of the cone opponent channel, whereas the 36-Hz data reflected luminance activity. There were no significant differences between the conditions with and without occluding the opposite eye for any of the stimulus protocols. Ocular interaction is absent in flicker ERGs reflecting cone opponent and luminance activity.
Keywords: Ocular interaction; Electroretinogram; Luminance; Cone opponency

A comparison of the suitability of cathode ray tube (CRT) and liquid crystal display (LCD) monitors as visual stimulators in mfERG diagnostics - Kaltwasser, Christoph; Horn, Folkert; Kremers, Jan; Jünemann, Anselm (Documenta Ophthalmologica, 2009)
The aim of this study was to determine up to which extent the specific characteristics of cathode ray tube (CRT) and liquid crystal display (LCD) monitors influence the retinal biosignal when used as stimulators in ocular electrophysiology. In a conventional CRT monitor, each pixel lights up only for a duration of a few milliseconds during each frame. In contrast, liquid crystal displays are quasi-static, i.e. each pixel has a constant luminance during the whole length of the frame, but lights up only with a certain delay after the trigger. These different display characteristics may affect the mfERG signal. The temporal and spatial luminance distributions of a CRT and an LCD monitor were measured in white flashes. The total amount of emitted light was calculated by integration of the intensity versus time curves. By means of an mfERG recording system (RETIsystem, Roland Consult, Brandenburg, Germany) first-order kernel (FOK) mfERG signals were computed and then analysed using customized MATLAB (TheMathWorks, Natick, MA, USA) software. With the two stimulator monitors, differences in the mfERG signal were observed. The latencies of mfERG responses recorded with the LCD monitor were significantly increased by 7.1 ms for N1 and 9.5 ms for P1 compared to the CRT. Due to a higher luminance, the N1 amplitude was significantly higher by approx. 2 dB in measurements with the LCD monitor while no significant difference could be detected with regard to the more contrast sensitive P1 amplitude. When using LCD monitors as stimulators the increase in latencies and differences in the luminance versus time profile must be taken into account. Prior to clinical application, the establishment of guidelines for the use of LCD monitors is recommended.
Keywords: CRT; LCD; Multifocal ERG; Stimulus delivery

A dim view of M-cone onsets - Parry, Neil R. A.; Mckeefry, Declan J.; Kremers, Jan; Murray, Ian J. (Journal of the Optical Society of America A-Optics Image Science and Vision, 2016)
We investigated the brightness (i.e., perceived luminance) of isolated L- and M-cone pulses to seek a perceptual correlate of our previous reports that M-on electroretinograms resemble L-off responses, implying the operation of post-receptoral opponent processing. Using triple silent substitutions, cone increments were generated in a 4-primary ganzfeld, masked by random positive or negative luminance bias. The results show that M-cone increments decrease in brightness, while L-cone increments increase. These differences became smaller as field size reduced; this was not eccentricity or area dependent. We speculate about early retinal input into brightness perception.
EVALuna2:21291

Alouatta trichromatic color vision: cone spectra and physiological responses studied with microspectrophotometry and single unit retinal electrophysiology - Silveira, Luiz Carlos L.; Saito, Cezar A.; Da Silva Filho, Manoel; Kremers, Jan; Bowmaker, James K.; Lee, Barry B. (PLoS ONE, 2014)
The howler monkeys (Alouatta sp.) are the only New World primates to exhibit routine trichromacy. Both males and females have three cone photopigments. However, in contrast to Old World monkeys, Alouatta has a locus control region upstream of each opsin gene on the X-chromosome and this might influence the retinal organization underlying its color vision. Post-mortem microspectrophotometry (MSP) was performed on the retinae of two male Alouatta to obtain rod and cone spectral sensitivities. The MSP data were consistent with only a single opsin being expressed in each cone and electrophysiological data were consistent with this primate expressing full trichromacy. To study the physiological organization of the retina underlying Alouatta trichromacy, we recorded from retinal ganglion cells of the same animals used for MSP measurements with a variety of achromatic and chromatic stimulus protocols. We found MC cells and PC cells in the Alouatta retina with similar properties to those previously found in the retina of other trichromatic primates. MC cells showed strong phasic responses to luminance changes and little response to chromatic pulses. PC cells showed strong tonic response to chromatic changes and small tonic response to luminance changes. Responses to other stimulus protocols (flicker photometry; changing the relative phase of red and green modulated lights; temporal modulation transfer functions) were also similar to those recorded in other trichromatic primates. MC cells also showed a pronounced frequency double response to chromatic modulation, and with luminance modulation response saturation accompanied by a phase advance between 10-20 Hz, characteristic of a contrast gain mechanism. This indicates a very similar retinal organization to Old-World monkeys. Cone-specific opsin expression in the presence of a locus control region for each opsin may call into question the hypothesis that this region exclusively controls opsin expression.
EVALuna2:21215

Altered visual processing in the mdx52 mouse model of Duchenne muscular dystrophy - Barboni, Mirella Telles Salgueiro; Liber, André Maurício Passos; Joachimsthaler, Anneka; Saoudi, Amel; Goyenvalle, Aurélie; Rendon, Alvaro; Roger, Jérome E.; Ventura, Dora Fix; Kremers, Jan; Vaillend, Cyrille (Neurobiology of Disease, 2021)
The mdx52 mouse model of Duchenne muscular dystrophy (DMD) is lacking exon 52 of the DMD gene that is located in a hotspot mutation region causing cognitive deficits and retinal anomalies in DMD patients. This deletion leads to the loss of the dystrophin proteins, Dp427, Dp260 and Dp140, while Dp71 is preserved. The flash electroretinogram (ERG) in mdx52 mice was previously characterized by delayed dark-adapted b-waves. A detailed description of functional ERG changes and visual performances in mdx52 mice is, however, lacking. Here an extensive full-field ERG repertoire was applied in mdx52 mice and WT littermates to analyze retinal physiology in scotopic, mesopic and photopic conditions in response to flash, sawtooth and/or sinusoidal stimuli. Behavioral contrast sensitivity was assessed using quantitative optomotor response (OMR) to sinusoidally modulated luminance gratings at 100% or 50% contrast. The mdx52 mice exhibited reduced amplitudes and delayed implicit times in dark-adapted ERG flash responses, particularly in their b-wave and oscillatory potentials, and diminished amplitudes of light-adapted flash ERGs. ERG responses to sawtooth stimuli were also diminished and delayed for both mesopic and photopic conditions in mdx52 mice and the first harmonic amplitudes to photopic sine-wave stimuli were smaller at all temporal frequencies. OMR indices were comparable between genotypes at 100% contrast but significantly reduced in mdx52 mice at 50% contrast. The complex ERG alterations and disturbed contrast vision in mdx52 mice include features observed in DMD patients and suggest altered photoreceptor-to-bipolar cell transmission possibly affecting contrast sensitivity. The mdx52 mouse is a relevant model to appraise the roles of retinal dystrophins and for preclinical studies related to DMD.
CRIS-Team Scopus Importer:2021-02-26
Keywords: B-wave; Dp140; Dp260; Dp427; Duchenne muscular dystrophy; Dystrophin; Electroretinogram; Mouse model; Photoreceptors; Retina

A method for estimating intrinsic noise in electroretinographic (ERG) signals - Zele, Andrew J.; Feigl, Beatrix; Kambhampati, Pradeep K.; Hathibelagal, Amithavikram R.; Kremers, Jan (Documenta Ophthalmologica, 2015)
To develop a signal processing paradigm for extracting ERG responses to temporal sinusoidal modulation with contrasts ranging from below perceptual threshold to suprathreshold contrasts and estimate the magnitude of intrinsic noise in ERG signals at different stimulus contrasts.Photopic test stimuli were generated using a 4-primary Maxwellian view optical system. The 4-primary lights were sinusoidally temporally modulated in-phase (36 Hz; 2.5-50 % Michelson contrast). The stimuli were presented in 1-s epochs separated by a 1-ms blank interval and repeated 160 times (160.160-s duration) during the recording of the continuous flicker ERG from the right eye using DTL fibre electrodes. After artefact rejection, the ERG signal was extracted using Fourier transforms in each of the 1-s epochs where a stimulus was presented. The signal processing allows for computation of the intrinsic noise distribution in addition to the signal-to-noise (SNR) ratio.We provide the initial report that the ERG intrinsic noise distribution is independent of stimulus contrast, whereas SNR decreases linearly with decreasing contrast until the noise limit at 2.5 %. The 1-ms blank intervals between epochs de-correlated the ERG signal at the line frequency (50 Hz) and thus increased the SNR of the averaged response. We confirm that response amplitude increases linearly with stimulus contrast. The phase response shows a shallow positive relationship with stimulus contrast.This new technique will enable recording of intrinsic noise in ERG signals above and below perceptual visual threshold and is suitable for measurement of continuous rod and cone ERGs across a range of temporal frequencies, and post-receptoral processing in the primary retinogeniculate pathways at low stimulus contrasts. The intrinsic noise distribution may have application as a biomarker for detecting changes in disease progression or treatment efficacy.
EVALuna2:21230

A modified silent substitution electroretinography protocol to separate photoreceptor subclass function in lightly sedated dogs - Wise, E. N.; Foster, M. L.; Kremers, Jan; Mowat, F. M. (Veterinary Ophthalmology, 2020)
Objective: A previously published study successfully isolated photoreceptor responses from canine rods, long/medium-wavelength (L/M) cones, and short-wavelength (S) cones using silent substitution electroretinography (ERG) performed under general anesthesia. We hypothesized that responses would be similar in dogs under sedation and that a curtailed protocol suitable for use in clinical patients could effectively isolate responses from all three photoreceptor subtypes. Animals studied: Three normal adult purpose-bred beagles (2 females and 1 male). Methods: Dogs were dark-adapted for 1 hour. Sine wave color stimuli were delivered using LEDs in a Ganzfeld dome. The ERG protocol under anesthesia was performed as previously published; sedated ERG protocols were performed after a 3-day washout period. Intravenous sedation (dexmedetomidine 1.25 mcg/kg, butorphanol 0.1 mg/kg) was administered for sedation. Statistical analysis was performed using two-way repeated-measures ANOVA and linear regression. Results: In both anesthetized and sedated animals, rod-derived responses peaked at low frequency (4-12 Hz), L/M-cone responses peaked at high frequency (32-38 Hz), and S-cone responses peaked at low frequency (4-12 Hz). The frequencies eliciting maximal responses were similar in sedated and anesthetized protocols, although rod amplitudes were significantly higher in the sedated protocols compared with anesthetized (P <.001). Conclusion: We present a clinically applicable method to consistently isolate rod and cone subclass function in sedated dogs. This may allow detailed evaluation of photoreceptor function in clinical patients with rod or cone subclass deficits without the need for general anesthesia or protracted adaptation times.
CRIS-Team Scopus Importer:2020-12-04
Keywords: electroretinography; L/M-cone; photoreceptor; rod; S-cone; silent substitution

A Multiple Piccolino-RIBEYE Interaction Supports Plate-Shaped Synaptic Ribbons in Retinal Neurons - Müller, Tanja; Gierke, Kaspar; Joachimsthaler, Anneka; Sticht, Heinrich; Izsvak, Zsuzsanna; Hamra, F. Kent; Fejtová, Anna; Ackermann, Frauke; Garner, Craig C.; Kremers, Jan; Brandstätter, Johann Helmut; Regus-Leidig, Hanna (Journal of Neuroscience, 2019)
Active zones at chemical synapses are highly specialized sites for the regulated release of neurotransmitters. Despite a high degree of active zone protein conservation in vertebrates, every type of chemical synapse expresses a given set of protein isoforms and splice variants adapted to the demands on neurotransmitter release. So far, we know little about how specific active zone proteins contribute to the structural and functional diversity of active zones. In this study, we explored the nanodomain organization of ribbon-type active zones by addressing the significance of Piccolino, the ribbon synapse-specific splice variant of Piccolo, for shaping the ribbon structure. We followed up on previous results, which indicated that rod photoreceptor synaptic ribbons lose their structural integrity in a knockdown of Piccolino. Here, we demonstrate an interaction between Piccolino and the major ribbon component RIBEYE that supports plate-shaped synaptic ribbons in retinal neurons. In a detailed ultrastructural analysis of three different types of retinal ribbon synapses in Piccolo/Piccolino-deficient male and female rats, we show that the absence of Piccolino destabilizes the superstructure of plate-shaped synaptic ribbons, although with variable manifestation in the cell types examined. Our analysis illustrates how the expression of a specific active zone protein splice variant (e.g., Piccolino) contributes to structural diversity of vertebrate active zones.
CRIS-Team WoS Importer:2019-04-12

Analysis of RIM Expression and Function at Mouse Photoreceptor Ribbon Synapses - Löhner, Martina; Babai, Norbert; Müller, Tanja; Gierke, Kaspar; Atorf, Jenny; Joachimsthaler, Anneka; Peukert, Angela; Martens, Henrik; Feigenspan, Andreas; Kremers, Jan; Schoch, Susanne; Brandstätter, Johann Helmut; et al. (The Journal of Neuroscience, 2017)
RAB3A-interacting molecule (RIM) proteins are important regulators of transmitter release from active zones. At conventional chemical synapses, RIMs contribute substantially to vesicle priming and docking and their loss reduces the readily releasable pool of synaptic vesicles by up to 75%. The priming function of RIMs is mediated via the formation of a tripartite complex with Munc13 and RAB3A, which brings synaptic vesicles in close proximity to Ca(2+) channels and the fusion site and activates Munc13. We reported previously that, at mouse photoreceptor ribbon synapses, vesicle priming is Munc13 independent. In this study, we examined RIM expression, distribution, and function at male and female mouse photoreceptor ribbon synapses. We provide evidence that RIM1? and RIM1? are highly likely absent from mouse photoreceptors and that RIM2? is the major large RIM isoform present at photoreceptor ribbon synapses. We show that mouse photoreceptors predominantly express RIM2 variants that lack the interaction domain for Munc13. Loss of full-length RIM2? in a RIM2? mutant mouse only marginally perturbs photoreceptor synaptic transmission. Our findings therefore strongly argue for a priming mechanism at the photoreceptor ribbon synapse that is independent of the formation of a RIM-Munc13-RAB3A complex and thus provide further evidence for a fundamental difference between photoreceptor ribbon synapses and conventional chemical synapses in synaptic vesicle exocytosis.SIGNIFICANCE STATEMENT RAB3A-interacting molecules 1 and 2 (RIM1/2) are essential regulators of exocytosis. At conventional chemical synapses, their function involves Ca(2+) channel clustering and synaptic vesicle priming and docking through interactions with Munc13 and RAB3A, respectively. Examining wild-type and RIM2 mutant mice, we show here that the sensory photoreceptor ribbon synapses most likely lack RIM1 and predominantly express RIM2 variants that lack the interaction domain for Munc13. Our findings demonstrate that the photoreceptor-specific RIM variants are not essential for synaptic vesicle priming at photoreceptor ribbon synapses, which represents a fundamental difference between photoreceptor ribbon synapses and conventional chemical synapses with respect to synaptic vesicle priming mechanisms.
EVALuna2:21339

A new interpretation of components in the ERG signals to sine wave luminance stimuli at different temporal frequencies and contrasts - Pangeni, Gobinda; Horn, Folkert; Kremers, Jan (Visual Neuroscience, 2010)
Full-field electroretinograms were recorded from five normal human subjects using white light (mean luminance: 250 cd/m(2)) sine wave stimuli at different frequencies and contrasts. In agreement with previous studies, we found that the amplitude of the fundamental component displayed a dip at about 12 Hz, coinciding with a maximum in the second harmonic component, indicating frequency doubling of the responses. By including measurements at different contrasts, we were able to recognize two (sine-like and transient) response components. We found that the waveform of the transient response was relatively frequency independent. An algorithm to separate the two components was developed. The interaction between these two components can explain the frequency-doubled responses around 12 Hz. The sine-like component is more linear and prominent in the low-frequency region, whereas the transient seems to be more nonlinear and prominent in the high-frequency region.
Keywords: Electroretinogram; Sine wave stimuli; Component analysis; Temporal modulation; Luminance contrast

A New Interpretation of Components in the Erg Signals to Sine Wave Luminance Stimuli at Different Temporal Frequencies and Contrasts - Pangeni, G.; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2010)
Keywords: electroretinography: non-clinical; retina: distal (photoreceptors; horizontal cells; bipolar cells); retina: proximal (bipolar; amacrine; and ganglion cells)

A new method to measure electroretinograms (ERGs) elicited by temporal white noise - Kremers, Jan; Feigl, Beatrix K.; Aher, Avinash; Mckeefry, Declan J.; Parry, Neil Robert Alan; Maguire, John; Murray, Ian J.; Zele, Andrew J. (Investigative Ophthalmology & Visual Science, 2017)

A novel approach to analyze white noise ERGs in mice - Stallwitz, Nina; Joachimsthaler, Anneka; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2022)
CRIS-Team WoS Importer:2022-09-30

Artificial intelligence for detection of retinal toxicity in chloroquine and hydroxychloroquine therapy using multifocal electroretinogram waveforms - Kulyabin, Mikhail; Kremers, Jan; Holbach, Vera; Maier, Andreas; Huchzermeyer, Cord (Scientific Reports, 2024)
Chloroquine and hydroxychloroquine, while effective in rheumatology, pose risks of retinal toxicity, necessitating regular screening to prevent visual disability. The gold standard for screening includes retinal imaging and automated perimetry, with multifocal electroretinography (mfERG) being a recognized but less accessible method. This study explores the efficacy of Artificial Intelligence (AI) algorithms for detecting retinal damage in patients undergoing (hydroxy-)chloroquine therapy. We analyze the mfERG data, comparing the performance of AI models that utilize raw mfERG time-series signals against models using conventional waveform parameters. Our classification models aimed to identify maculopathy, and regression models were developed to predict perimetric sensitivity. The findings reveal that while regression models were more adept at predicting non-disease-related variation, AI-based models, particularly those utilizing full mfERG traces, demonstrated superior predictive power for disease-related changes compared to linear models. This indicates a significant potential to improve diagnostic capabilities, although the unbalanced nature of the dataset may limit some application

Asymmetrical Functional Deficits of ON and OFF Retinal Processing in the mdx3Cv Mouse Model of Duchenne Muscular Dystrophy - Tsai, Tina I.; Salgueiro Barboni, Mirella Telles; Nagy, Balazs Vince; Roux, Michel J.; Rendon, Alvaro; Ventura, Dora Fix; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2016)
The dystrophin mouse mutant mdx3Cv exhibits scotopic electroretinograpic (ERG) abnormalities, which resemble clinical changes observed in Duchenne muscular dystrophy (DMD) patients. In the present study, ERGs obtained from mdx3Cv and their wild-type littermates under scotopic, mesopic, and photopic conditions were analyzed to provide further insight on the affected retinal pathways, and to compare them with human data.Electroretinograms of mdx3Cv (n = 9) and age-matched C57BL/6J mice (n = 10) included the scotopic full-field flash (for outer retinal deficits in rod pathway), scotopic threshold response (for inner retinal integrity), photopic flash, sinusoidal flicker (for outer retinal deficits in cone pathway), mesopic rapid-on/-off sawtooth flicker, and photopic long-duration flash measurements (for separate ON-/OFF-responses under different conditions).The mdx3Cv mice exhibited diminished and delayed scotopic and photopic ERGs, particularly in their b-wave and oscillatory potentials. Interestingly, homologues to the a- and b-wave of the mesopic ON-response were affected in their peak/trough times but not in their amplitude, whereas changes to both features were uncovered for photopic ON-response and sinusoidal flicker. Mesopic and photopic OFF-components were within the norm.Abnormal scotopic and photopic flash ERGs were observed in mdx3Cv, which corroborate with deficits that are likely restricted to the level of photoreceptor-to-bipolar cell transmission. Further overlaps between mdx3Cv mice and DMD patients exist, including asymmetrical ON versus OFF ERG alterations under mesopic versus photopic vision. In mice, ON-pathway function is compromised, whereas the OFF-pathway is spared.
EVALuna2:21316
Keywords: Duchenne muscular dystrophy; dystrophin; electrophysiology; mouse model

Asymmetrical ON/OFF retinal dysfunction in the mdx(Cv3) mouse model of Duchenne muscular dystrophy - Tsai, Tina I.; Barboni, Mirella Telles Salgueiro; Nagy, Balazs Vince; Roux, Michel J.; Rendon, Alvaro; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2016)

Asymmetries in the contributions of on- and off-mechanisms to the ERG signal - Kremers, Jan (Psychology & Neuroscience, 2013)
Keywords: Asymmetries; L- and M-cones; Electroretinograms; On- and off-responses

A Temporal White Noise Analysis for Extracting the Impulse Response Function of the Human Electroretinogram - Zele, Andrew J.; Feigl, Beatrix; Kambhampati, Pradeep K.; Aher, Avinash; Mckeefry, Declan; Parry, Neil; Maguire, John; Murray, Ian; Kremers, Jan (Translational Vision Science & Technology, 2017)
Purpose: We introduce a method for determining the impulse response function (IRF) of the ERG derived from responses to temporal white noise (TWN) stimuli.Methods: This white noise ERG (wnERG) was recorded in participants with normal trichromatic vision to full-field (Ganzfeld) and 39.3 degrees diameter focal stimuli at mesopic and photopic mean luminances and at different TWN contrasts. The IRF was obtained by cross-correlating the TWN stimulus with the wnERG.Results: We show that wnERG recordings are highly repeatable, with good signal-tonoise ratio, and do not lead to blink artifacts. The wnERG resembles a flash ERG waveform with an initial negativity (N1) followed by a positivity (P1), with amplitudes that are linearly related to stimulus contrast. These N1 and N1-P1 components showed commonalties in implicit times with the a-and b-waves of flash ERGs. There was a clear transition from rod-to cone-driven wnERGs at similar to 1 photopic cd.m(-2). We infer that oscillatory potentials found with the flash ERG, but not the wnERG, may reflect retinal nonlinearities due to the compression of energy into a short time period during a stimulus flash.Conclusion: The wnERG provides a new approach to study the physiology of the retina using a stimulation method with adaptation and contrast conditions similar to natural scenes to allow for independent variation of stimulus strength and mean luminance, which is not possible with the conventional flash ERG.
Keywords: electroretinogram (ERG); temporal white noise; impulse response function

Blue-Yellow VEP with Projector-Stimulation in Glaucoma - Dussan Molinos, Laura; Huchzermeyer, Cord; Lämmer, Robert; Kremers, Jan; Horn, Folkert (Graefes Archive For Clinical and Experimental Ophthalmology, 2021)
Background and aim In the past, increased latencies of the blue-on-yellow pattern visually evoked potentials (BY-VEP), which predominantly originate in the koniocellular pathway, have proven to be a sensitive biomarker for early glaucoma. However, a complex experimental setup based on an optical bench was necessary to obtain these measurements because computer screens lack sufficient temporal, spatial, spectral, and luminance resolution. Here, we evaluated the diagnostic value of a novel setup based on a commercially available video projector.
CRIS-Team WoS Importer:2021-12-03

Ccdc66 null mutation causes retinal degeneration and dysfunction - Gerding, Wanda M.; Schreiber, Sabrina; Schulte-Middelmann, Tobias; Marques, Andreia De Castro; Atorf, Jenny; Akkad, Denis A.; Dekomien, Gabriele; Kremers, Jan; Dermietzel, Rolf; Gal, Andreas; Ruelicke, Thomas; Ibrahim, Saleh; et al. (Human Molecular Genetics, 2011)
Retinitis pigmentosa (RP) is a group of human retinal disorders, with more than 100 genes involved in retinal degeneration. Canine and murine models are useful for investigating human RP based on known, naturally occurring mutations. In Schapendoes dogs, for example, a mutation in the CCDC66 gene has been shown to cause autosomal recessively inherited, generalized progressive retinal atrophy (gPRA), the canine counterpart to RP. Here, a novel mouse model with a disrupted Ccdc66 gene was investigated to reveal the function of protein CCDC66 and the pathogenesis of this form of gPRA. Homozygous Ccdc66 mutant mice lack retinal Ccdc66 RNA and protein expression. Light and electron microscopy reveal an initial degeneration of photoreceptors already at 13 days of age, followed by a slow, progressive retinal degeneration over months. Retinal dysfunction causes reduced scotopic a-wave amplitudes, declining from 1 to 7 months of age as well as an early reduction of the photopic b-wave at 1 month, improving slightly at 7 months, as evidenced by electroretinography. In the retina of the wild-type (WT) mouse, protein CCDC66 is present at highest levels after birth, followed by a decline until adulthood, suggesting a crucial role in early development. Protein CCDC66 is expressed predominantly in the developing rod outer segments as confirmed by subcellular analyses. These findings illustrate that the lack of protein CCDC66 causes early, slow progressive rod-cone dysplasia in the novel Ccdc66 mutant mouse model, thus providing a sound foundation for the development of therapeutic strategies.
EVALuna2:21029

Cell types and synapses expressing the snare complex regulating proteins complexin 1 and complexin 2 in mammalian retina - Lux, Uwe; Ehrenberg, Johanna; Joachimsthaler, Anneka; Atorf, Jenny; Pircher, Bianca; Reim, Kerstin; Kremers, Jan; Gießl, Andreas; Brandstätter, Johann Helmut (International Journal of Molecular Sciences, 2021)
Complexins (Cplxs) 1 to 4 are components of the presynaptic compartment of chemical synapses where they regulate important steps in synaptic vesicle exocytosis. In the retina, all four Cplxs are present, and while we know a lot about Cplxs 3 and 4, little is known about Cplxs 1 and 2. Here, we performed in situ hybridization experiments and bioinformatics and exploited Cplx 1 and Cplx 2 single-knockout mice combined with immunocytochemistry and light microscopy to characterize in detail the cell type and synapse-specific distribution of Cplx 1 and Cplx 2. We found that Cplx 2 and not Cplx 1 is the main isoform expressed in normal and displaced amacrine cells and ganglion cells in mouse retinae and that amacrine cells seem to operate with a single Cplx isoform at their conventional chemical synapses. Surprising was the finding that retinal function, determined with electroretinographic recordings, was altered in Cplx 1 but not Cplx 2 single-knockout mice. In summary, the results provide an important basis for future studies on the function of Cplxs 1 and 2 in the processing of visual signals in the mammalian retina.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Amacrine cells; Complexin 1; Complexin 2; Conventional chemical synapses; Ganglion cells; Horizontal cells; Retina

Center-Surround Interactions in Flicker Perception of Glaucoma Patients - Teixeira, C. E.; Silveira, L. C. L.; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2010)
Keywords: visual impairment: neuro-ophthalmological disease; visual fields; temporal vision

Changes in perceived temporal variation due to context: contributions from two distinct neural mechanisms - D'Antona, Anthony D.; Kremers, Jan; Shevell, Steven K. (Vision research, 2011)
The percept of a time-varying light depends on the temporal properties of light within the surrounding area. The locus of the neural mechanism mediating this lateral interaction is controversial; neural mechanisms have been posited at the LGN (Kremers et al., 2004) or cortical level (D'Antona & Shevell, 2007). To determine the neural locus, changes in perceived temporal variation were compared with ipsilateral versus contralateral surrounding context. In both cases, a temporally varying central field was viewed within a temporally varying surround; relative phase between center and surround was varied. Perceived modulation depth in the central field depended strongly on the relative phase between center and surround, in both the ipsilateral and contralateral conditions. The results revealed lateral interactions arising from both a weak monocular (plausibly LGN) and a stronger central (cortical) mechanism. The monocular contribution was similar over the range of temporal frequencies tested (approx. 3-12Hz), while the central component showed low-pass temporal-frequency selectivity.
EVALuna2:21031

Changes of Osteopontin in the Aqueous Humor of the DBA2/J Glaucoma Model Correlated with Optic Nerve and RGC Degenerations - Birke, Marco; Neumann, Carolin; Birke, Kerstin; Kremers, Jan; Scholz, Michael (Investigative Ophthalmology & Visual Science, 2010)
PURPOSE. To identify age-dependent regulated aqueous humor (AH) factors in DBA2/J (D2J) mice and to correlate them with optic nerve degeneration and intraocular pressure (IOP) by population and individual analysis.METHODS. AH samples of D2J mice aged 2 (n = 3), 7 (n = 5), and 10 months (n = 14) were analyzed by mouse cytokine antibody array. Ten-month samples were classified into eyes with (D2J+) or without (D2J-) optic neuropathy. Ten-month-old C57/B16 (B6; n = 13) and DBA2/Rj (D2Rj; n = 15) mice served as controls. IOP was recorded from 2 to 10 months. Individual AH osteopontin (OPN) was determined in 31 D2J eyes (10 months) and was correlated with optic neuropathy and IOP. OPN mRNA was detected by in situ hybridization. OPN blood plasma content of D2J and B6 was monitored from 8 to 10 months. Effect of OPN on cell survival in the ganglion cell layer (GCL) or metabolism was tested in ex vivo-cultured D2Rj eyes and murine neuronal precursors.RESULTS. In array analysis, OPN was detected in 10-month-old D2J mice only. They significantly differed between D2J- and D2J+ (P = 0.006). By Western blot analysis, a sevenfold OPN increase in D2J+ was determined compared with B6. Individual analysis confirmed the positive correlation of OPN with optic neuropathy. IOP was not correlated with OPN. OPN blood plasma contents steadily increased with age in D2J. OPN+ cells were detected within the ciliary body of D2J, and OPN+ RGCs were approximate to 30% reduced. OPN treatment inhibited cell degeneration within the GCL in ex vivo-cultured D2Rj eyes and increased the metabolic activity of neuronal precursor cells.CONCLUSIONS. OPN is an age-dependent increased AH factor associated with degeneration of the optic nerve in D2J mice. By modulating the metabolism of neuronal cells, deregulated levels of OPN could be involved in degenerative processes affecting RGCs or optic nerve axons in the D2J model. (Invest Ophthalmol Vis Sci. 2010; 51:5759-5767) DOI:10.1167/iovs.105558

Chromatic discrimination measures in mature observers depend on the response window - Fars, Julien; Fernandes, Thiago P.; Huchzermeyer, Cord; Kremers, Jan; Paramei, Galina V. (Scientific Reports, 2022)
Our past anecdotal evidence prompted that a longer response window (RW) in the Trivector test (Cambridge Colour Test) improved mature observers' estimates of chromatic discrimination. Here, we systematically explored whether RW variation affects chromatic discrimination thresholds measured by the length of Protan, Deutan and Tritan vectors. We employed the Trivector test with three RWs: 3 s, 5 s, and 8 s. Data of 30 healthy normal trichromats were stratified as age groups: 'young' (20-29 years), 'middle-aged' (31-48 years), and 'mature' (57-64 years). We found that for the 'young' and 'middle-aged', the thresholds were comparable at all tested RWs. However, the RW effect was apparent for the 'mature' observers: their Protan and Tritan thresholds decreased at 8-s RW compared to 3-s RW; moreover, their Tritan threshold decreased at 5-s RW compared to 3-s RW. Elevated discrimination thresholds at shorter RWs imply that for accurate performance, older observers require longer stimulus exposure and are indicative of ageing effects manifested by an increase in critical processing duration. Acknowledging low numbers in our 'middle-aged' and 'mature' samples, we consider our study as pilot. Nonetheless, our findings encourage us to advocate a RW extension in the Trivector protocol for testing mature observers, to ensure veridical measures of their chromatic discrimination by disentangling these from other ageing effects-slowing down of both motor responses and visual processing.
CRIS-Team WoS Importer:2022-06-17

Chromatic discrimination: The response window does matter for veridical measurement in mature observers - Fars, Julien; Fernandes, Thiago M. P.; Huchzermeyer, Cord; Kremers, Jan; Paramei, Galina V. (PERCEPTION, 2021)
CRIS-Team WoS Importer:2022-01-21

Chromatic visual evoked potentials: A review of physiology, methods and clinical applications - Marmoy, Oliver R.; Tekavčič Pompe, Manca; Kremers, Jan (Progress in Retinal and Eye Research, 2024)
Objective assessment of the visual system can be performed electrophysiologically using the visual evoked potential (VEP). In many clinical circumstances, this is performed using high contrast achromatic patterns or diffuse flash stimuli. These methods are clinically valuable but they may only assess a subset of possible physiological circuitries within the visual system, particularly those involved in achromatic (luminance) processing. The use of chromatic VEPs (cVEPs) in addition to standard VEPs can inform us of the function or dysfunction of chromatic pathways. The chromatic VEP has been well studied in human health and disease. Yet, to date our knowledge of their underlying mechanisms and applications remains limited. This likely reflects a heterogeneity in the methodology, analysis and conclusions of different works, which leads to ambiguity in their clinical use. This review sought to identify the primary methodologies employed for recording cVEPs. Furthermore cVEP maturation and application in understanding the function of the chromatic system under healthy and diseased conditions are reviewed. We first briefly describe the physiology of normal colour vision, before describing the methodologies and historical developments which have led to our understanding of cVEPs. We thereafter describe the expected maturation of the cVEP, followed by reviewing their application in several disorders: congenital colour vision deficiencies, retinal disease, glaucoma, optic nerve and neurological disorders, diabetes, amblyopia and dyslexia. We finalise the review with recommendations for testing and future directions.
CRIS-Team Scopus Importer:2024-05-31
Keywords: Chromatic; Chromatic VEP; Colo*r; Electrophysiology; VEP; Visual evoked potentials

Color Vision 2018: Introduction by the feature editors - Buck, Steven L.; Baraas, Rigmor; Kremers, Jan; Lindsey, Delwin T.; Nascimento, Sergio M. C.; Webster, Michael A.; Werner, John S. (Journal of the Optical Society of America A-Optics Image Science and Vision, 2018)
This feature issue of the Journal of the Optical Society of America A (JOSA A) reflects the basic and applied research interests of members of the color vision community. Most of the articles stem from presentations at the 24th Biennial Symposium of the International Colour Vision Society (ICVS).
EVALuna2:34925

Combining L- and M-cone-isolating stimuli to measure parvo- and magnocellular function in normal subjects and glaucoma patients - Huchzermeyer, Cord; Mardin, Christian Y.; Lämmer, Robert; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-11-01

Combining temporal white noise stimulation and silent substitution technique: wnERGs driven by single photoreceptor types in LIAIS mice - Joachimsthaler, Anneka; Stallwitz, Nina; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2021)
CRIS-Team WoS Importer:2021-09-24

Comparing functional defects measured by mfERG and standard automated perimetry in patients under (hydroxy-)chloroquine therapy - Huchzermeyer, Cord; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2022)
CRIS-Team WoS Importer:2022-09-30

Comparing Transient and Steady-State Multifocal-VEP (mfVEP) using Dartboard Stimulation as Possible Tool for Objective Perimetry - Horn, Folkert; Selle, Franziska; Hohberger, Bettina; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2015)

Comparison of frequency doubling and flicker defined form perimetry in early glaucoma - Horn, Folkert; Scharch, Vicki; Mardin, Christian Y.; Lämmer, Robert; Kremers, Jan (Graefes Archive For Clinical and Experimental Ophthalmology, 2016)
To compare perimetric data based on the second-generation frequency doubling technology (FDT) and on flicker defined form (FDF) stimulation in early glaucoma patients.Seventy-two experienced glaucoma patients and 50 healthy subjects of the Erlangen Glaucoma Registry participated in the study. The definition of glaucoma was solely based on optic disc appearance. All patients underwent FDF perimetry (HEP), FDT perimetry (Matrix), standard automated perimetry (SAP, Octopus), and peripapillar measurements of the RNFL thickness (Spectralis OCT). Exclusion criteria were: mean defect (MD) in SAP > 6 dB, eye diseases other than glaucoma, or non-reliable FDF or FDT measurements. Statistical analyses included comparison of the standard indices and correlations between methods. Venn-diagrams show the number of patients with abnormal results in HEP, Matrix, SAP, and mean RNFL thickness.Mean defect data from FDT and FDF perimetry were strongly correlated (R = -0.85, P <0.001). In this cohort of early glaucoma patients, the MD values were 6.1 ± 5.0 dB (FDF) and 4.5 ± 4.1 dB (FDT). Sensitivity in this patient group was 65 % for FDF-MD, 60 % for FDT-MD, and 60 % for RNFL-thickness, all at a specificity of 95 %. The correlation analysis between local RNFL thickness and corresponding visual defects revealed significant Spearman correlation coefficients for the arcuate bundles of the visual field (FDF-inferior: R = -0.65, FDF-superior: R = -0.74, FDT-inferior: R = -0.55, FDT-superior: R = -0.72).FDF and FDT stimulations can be used to detect patients with early glaucoma. Combined consideration of RNFL thickness and results from one of these perimetric tests can increase the total number of detected patients.
EVALuna2:21278

Comparison of macaque and human L- and M-cone driven electroretinograms - Kremers, Jan; Aher, Avinash; Parry, Neil R.A.; Patel, Nimesh B.; Frishman, Laura J. (Experimental Eye Research, 2021)
Purpose: The macaque retina is often used as a model for the human retina. However, there are only a handful of direct in vivo comparisons of the retinal physiology in humans and macaques. In the current study, ERG responses to luminance, L-cone isolating and M-cone isolating stimuli with sinusoidal, sawtooth and square wave temporal profiles were measured. The results were compared with those obtained from human observers. Methods: The responses from five anesthetized adult macaques were measured. Full field stimuli were created. L- and M-cone isolating stimuli were based on the triple silent substitution technique. Sinusoidal stimuli had temporal frequencies between 4 and 56 Hz in 4 Hz steps. Sawtooth stimuli with rapid-on ramp-off and with rapid-off ramp-on excitation profiles had a frequency of 4 Hz. Square stimuli were presented at 2 Hz. Results: Macaque and human ERGs in response to L- and M-cone isolating stimuli reflect L/M opponency and luminance activity. In responses to sine waves, cone opponency dominates at low temporal frequencies (4–12 Hz); luminance dominates at high temporal frequencies. The responses to sawtooth and square wave stimuli reflect a mixture of chromatic and luminance activity. L:M response ratios vary between individuals both in macaques and humans. Macaques show more complex responses, including greater second harmonic contributions than those in humans. Conclusions: Macaque and human ERGs share basic underlying mechanisms reflecting L/M opponency and luminance activity. There may be quantitative differences possibly reflecting differences in contributions of inner retinal mechanisms to the ERGs.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Cone opponency; Electroretinogram; Human; L-cones; Luminance; M-cones; Macaque

Complementarity of sensitivity and just noticeable difference in the study of Retinitis Pigmentosa and Stargardt disease - Fars, Julien; Kremers, Jan; Huchzermeyer, Cord (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2022)
CRIS-Team WoS Importer:2022-09-30

Correlated and uncorrelated invisible temporal white noise alters mesopic rod signaling - Hathibelagal, Amithavikram R.; Feigl, Beatrix; Kremers, Jan; Zele, Andrew J. (Journal of the Optical Society of America A-Optics Image Science and Vision, 2016)
We determined how rod signaling at mesopic light levels is altered by extrinsic temporal white noise that is correlated or uncorrelated with the activity of one (magnocellular, parvocellular, or koniocellular) postreceptoral pathway. Rod and cone photoreceptor excitations were independently controlled using a four-primary photostimulator. Psychometric (Weibull) functions were measured for incremental rod pulses (50 to 250 ms) in the presence (or absence; control) of perceptually invisible subthreshold extrinsic noise. Uncorrelated (rod) noise facilitates rod detection. Correlated postreceptoral pathway noise produces differential changes in rod detection thresholds and decreases the slope of the psychometric functions. We demonstrate that invisible extrinsic noise changes rod-signaling characteristics within the three retinogeniculate pathways at mesopic illumination depending on the temporal profile of the rod stimulus and the extrinsic noise type.
EVALuna2:21298

Correlation between Loss of the Retinal Nerve Fiber Layer Thickness and Local Visual Field Defects measured with FDF-Perimetry - Horn, Folkert; Tornow, Ralf-Peter; Jünemann, Anselm; Lämmer, Robert; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2014)
Keywords: 642 perimetry; 610 nerve fiber layer; 758 visual fields

Correlations between dark-adapted rod threshold elevations and erg response deficits in duchenne muscular dystrophy - Barboni, Mirella Telles Salgueiro; Dias, Sarah Leonardo; Silva, Leonardo Aparecido; Damico, Francisco Max; Vidal, Kallene Summer; Costa, Marcelo Fernandes; Nagy, Balázs Vince; Kremers, Jan; Ventura, Dora Fix (Investigative Ophthalmology & Visual Science, 2021)
PURPOSE. The purpose of this study was to characterize changes in the full-field flash electroretinogram (ERG) in association with psychophysical dark-adapted visual thresholds in patients with genetically characterized Duchenne muscular dystrophy (DMD) either lacking Dp427 (Up 30) or at least Dp260 in addition to Dp427 (Down 30). METHODS. Twenty-one patients with DMD and 27 age-similar controls participated in this study. Dark-adapted (0.01, 3.0, and 10 cd.s/m2 flashes) and light-adapted (3.0 cd.s/m2 flash) ERGs were recorded following International Society for Clinical Electrophysiology of Vision (ISCEV) standard protocols. Visual detection thresholds to 625-nm (cone function) and 527-nm (rod function) light-emitting diode (LED) flashes (2 degree diameter) were measured during a dark adaptation period after a 1-minute exposure to a bleaching light (3000 cd/m2). Initially, 8 minutes of interleaved 625-nm and 527-nm thresholds were measured. After an additional 5 minutes of dark-adaptation, a second set of threshold measurements to 527-nm stimuli was performed during the subsequent 6 minutes. RESULTS. Dark-adapted b-wave amplitude was significantly reduced to all strengths of flash and a-wave in response to the strong flash stimulus was delayed (15.6 vs. 14.7 ms, P < 0.05) in patients with Down 30 compared with controls. Dark-adapted cone thresholds did not differ among the groups (−2.0, −1.8, and −1.7 log cd/m2 for Down 30, Up 30, and controls, respectively, P = 0.21). In contrast, dark-adapted rod thresholds were elevated (F(2,36) = 8.537, P = 0.001) in patients with Down 30 (mean = −3.2 ± 1.1 log cd/m2) relative to controls (mean = −4.2 ± 0.3 log cd/m2). Dark-adapted b-wave amplitudes were correlated with dark-adapted rod sensitivity in patients with DMD (Spearman Rho = 0.943, P = 0.005). The changes were much smaller or absent in patients with intact Dp260. CONCLUSIONS. Dp260 is particularly required for normal rod-system function in dark adaptation.
CRIS-Team Scopus Importer:2021-05-14
Keywords: Cone; Dark-adaptation; Duchenne muscular dystrophy (DMD); Dystrophin protein; Electroretinogram (ERG); Human vision; Retina; Rod

Dark adapted cone/rod thresholds and ERGs in Duchenne muscular dystrophy - Barboni, Mirella Telles Salgueiro; Dias, Sarah; Silva, Leonardo; Damico, Francisco Max; Vidal, Kallene Summer; Costa, Marcelo Fernandes; Grossklauss, Luis Fernando; Nagy, Balazs Vince; Kremers, Jan; Ventura, Dora Fix (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2020)
CRIS-Team WoS Importer:2020-09-11

Developments in non-invasive visual electrophysiology - Kremers, Jan; McKeefry, Declan J.; Murray, Ian J.; Parry, Neil R.A. (Vision research, 2020)
To study the physiology of the primate visual system, non-invasive electrophysiological techniques are of major importance. Two main techniques are available: the electroretinogram (ERG), a mass potential originating in the retina, and the visual evoked potential (VEP), which reflects activity in the primary visual cortex. In this overview, the history and the state of the art of these techniques are briefly presented as an introduction to the special issue “New Developments in non-invasive visual electrophysiology”. The overview and the special issue can be used as the starting point for exciting new developments in the electrophysiology of primate and mammalian vision.
CRIS-Team Scopus Importer:2020-06-23
Keywords: Cortical pathways; Electrophysiology; Electroretinography; Retinal pathways; Visual evoked potentials

Diet enriched with the Amazon fruit açaí (Euterpe oleracea) prevents electrophysiological deficits and oxidative stress induced by methyl-mercury in the rat retina - Brasil, Aldia; De Farias Rocha, Fernando Allan; Gomes, Bruno Duarte; Oliveira, Karen Renata M.; De Carvalho, Tayana Silva; Batista, Evander De Jesus O.; Borges, Rosivaldo Dos Santos; Kremers, Jan; Herculano, Anderson Manoel (Nutritional Neuroscience, 2016)
Background The protective effect of a diet supplemented by the Amazonian fruit Euterpe oleracea (EO) against methylmercury (MeHg) toxicity in rat retina was studied using electroretinography (ERG) and biochemical evaluation of oxidative stress. Method Wistar rats were submitted to conventional diet or EO-enriched diet for 28 days. After that, each group received saline solution or 5 mg/kg/day of MeHg for 7 days. Full-field single flash, flash and flicker ERGs were evaluated in the following groups: control, EO, MeHg, and EO+MeHg. The amplitudes of the a-wave, b-wave, photopic negative response from rod and/or cone were measured by ERGs as well as the amplitudes and phases of the fundamental component of the sine-wave flicker ERG. Lipid peroxidation was determined by thiobarbituric acid reactive species. Results All ERG components had decreased amplitudes in the MeHg group when compared with controls. EO-enriched food had no effect on the non-intoxicated animals. The intoxicated animals and those that received the supplemented diet presented significant amplitude reductions of the cone b-wave and of the fundamental flicker component when compared with non-intoxicated control. The protective effect of the diet on scotopic conditions was only observed for bright flashes eliciting a mixed rod and cone response. There was a significant increase of lipid peroxidation in the retina from animals exposed to MeHg and EO-supplemented diet was able to prevent MeHg-induced oxidative stress in retinal tissue. Conclusion These findings open up perspectives for the use of diets supplemented with EO as a protective strategy against visual damage induced by MeHg.
EVALuna2:21319
Keywords: Retina; Electroretinogram; Methyl-mercury; Oxidative stress; Euterpe oleracea

Discriminating anomalous trichromacy and cone degeneration in retinitis pigmentosa patients - Fars, Julien; Kremers, Jan; Huchzermeyer, Cord (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2020)
CRIS-Team WoS Importer:2020-09-11

Dynamics of adaptation process to different light levels in the mouse retina studied with ERGs - Joachimsthaler, Anneka; Tsai, Tina I.; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2017)

Dystrophin Is Required for Proper Functioning of Luminance and Red-Green Cone Opponent Mechanisms in the Human Retina - Salgueiro Barboni, Mirella Telles; Gomes Martins, Cristiane Maria; Nagy, Balazs Vince; Tsai, Tina; Damico, Francisco Max; Da Costa, Marcelo Fernandes; Cassia, Rita De; Pavanello, M.; Vilaca Lourenco, Naila Cristina; Pereirade Cerqueira, Antonia Maria; Zatz, Mayana; Kremers, Jan; et al. (Investigative Ophthalmology & Visual Science, 2016)
Visual information is processed in parallel pathways in the visual system. Parallel processing begins at the synapse between the photoreceptors and their postreceptoral neurons in the human retina. The integrity of this first neural connection is vital for normal visual processing downstream. Of the numerous elements necessary for proper functioning of this synaptic contact, dystrophin proteins in the eye play an important role. Deficiency of muscle dystrophin causes Duchenne muscular dystrophy (DMD), an X-linked disease that affects muscle function and leads to decreased life expectancy. In DMD patients, postreceptoral retinal mechanisms underlying scotopic and photopic vision and ON- and OFF-pathway responses are also altered.In this study, we recorded the electroretinogram (ERG) while preferentially activating the (red-green) opponent or the luminance pathway, and compared data from healthy participants (n = 16) with those of DMD patients (n = 10). The stimuli were heterochromatic sinusoidal modulations at a mean luminance of 200 cd/m2. The recordings allowed us also to analyze ON and OFF cone-driven retinal responses.We found significant differences in 12-Hz response amplitudes and phases between controls and DMD patients, with conditions with large luminance content resulting in larger response amplitudes in DMD patients compared to controls, whereas responses of DMD patients were smaller when pure chromatic modulation was given.The results suggest that dystrophin is required for the proper function of luminance and red-green cone opponent mechanisms in the human retina.
EVALuna2:21300

Electrodiagnosis of dichromacy - Barboni, Mirella Telles Salgueiro; Hauzman, Einat; Nagy, Balázs Vince; Martins, Cristiane Maria Gomes; Aher, Avinash; Tsai, Tina I.; Bonci, Daniela Maria Oliveria; Ventura, Dora Fix; Kremers, Jan (Vision research, 2019)
Retinal and cortical signals initiated by a single cone type can be recorded using the spectral compensation (or silent substitution) paradigm. Moreover, responses to instantaneous excitation increments combined with gradual excitation decreases are dominated by the response to the excitation increment. Similarly, the response to a sudden excitation decrement dominates the overall response when combined with a gradual excitation increase. Here ERGs and VEPs were recorded from 34 volunteers [25.9 ± 10.4 years old (mean ± 1 SD); 25 males, 9 females] to sawtooth flicker (4 Hz) stimuli that elicited L- or M-cone responses using triple silent substitution. The mean luminance (284 cd/m 2 ) and the mean chromaticity (x = 0.5686, y = 0.3716; CIE 1931 color space) remained constant and thus the state of adaptation was the same in all conditions. Color discrimination thresholds along protan, deutan, and tritan axes were obtained from all participants. Dichromatic subjects were genetically characterized by molecular analysis of their opsin genes. ERG responses to L-cone stimuli were absent in protanopes whereas ERG responses to M-cone stimuli were strongly reduced in deuteranopes. Dichromats showed generally reduced VEP amplitudes. Responses to cone-specific stimuli obtained with standard electrophysiological methods may give the same classification as that obtained with the Cambridge Colour Test and in some cases with the genetic analysis of the L- and M-opsin genes. Therefore, cone-specific ERGs and VEPs may be reliable methods to detect cone dysfunction. The present data confirm and emphasize the potential use of cone-specific stimulation, combined with standard visual electrodiagnostic protocols.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Color vision; Cone-isolating stimulus; Electroretinogram; Opsin gene; Silent substitution; Spectral compensation; Visual evoked potential

Electrophysiological deficits in the retina of the DBA/2J mouse - Scholz, Michael; Kremers, Jan; et al. (Documenta Ophthalmologica, 2009)
The DBA/2J (D2J) is a genetic mouse model for glaucomatous neurodegeneration because the animals develop anatomical and functional retinal deficits that partially can be correlated with elevated intraocular pressure (IOP). The IOP starts to increase at an age of about 6 months as a result of morphological changes within the anterior eye segment, e.g., pigment dispersion and iris synechiae. The purpose of the present study was to investigate how ERG responses change in individuals at different ages in D2J mice and to compare these changes with normal aging effects in pigmented C57/B6 (B6) mice. IOP was measured in awake, non-sedated D2J and B6 mice with a rebound tonometer. At ages between 2-3 and 10 months, scotopic flash ERGs were measured five times with about 2 months' intervals. In addition, light adapted flicker ERGs were recorded. Our data show that the D2J shows lower flicker ERG responses than the B6 mice already at an age of 2-3 months. Dark adapted flash ERG responses are not decreased at this age. In both mouse strains the ERG responses decrease as a function of age, but there is a stronger decrease in the D2J mice. The data of flicker ERGs suggest the presence of early functional deficits in the D2J retina that possibly have a post-receptoral origin. The scotopic flash ERG reveals a functional deficit that occurs at a later stage and that possibly is IOP dependent. But, the deficits appear at an age at which the IOP is still lower than in the B6 mouse, indicating that other factors play an additional role. © 2009 Springer-Verlag.
UnivIS-Import:2015-03-09:Pub.2009.med.AI.LAIPDL.electr
Keywords: DBA/2J mouse; Electroretinography; Flash ERG; Flicker ERG; Glaucoma; Intraocular pressure

Electroretinographical determination of human color vision type - Aher, Avinash; Martins, Cristiane M. G.; Barboni, Mirella T. S.; Nagy, Balazs V.; Hauzman, Einat; Bonci, Daniela M. O.; Ventura, Dora F.; Kremers, Jan (Journal of the Optical Society of America A-Optics Image Science and Vision, 2018)
It has been previously demonstrated that electroretinography (ERG) elicited by heterochromatically modulated stimuli can be used for objective determination of color vision type. Color vision of trichromatic, deuteranopic, and protanopic participants was psychophysically assessed by the Cambridge Color Test and confirmed genetically. ERG responses to red and green lights modulating in counterphase at 12 and 36 Hz were recorded, while the fraction of red modulation was varied. At 36 Hz (and second harmonics at 12 Hz), the responses were minimal at red fractions that differed significantly in protanopes. At 12 Hz (fundamental component), the responses of the trichromats differed significantly compared to those of the dichromats. An improved protocol shows that the three subject groups can be separated with no overlap. (C) 2018 Optical Society of America

Electroretinographic Recordings in a Mouse Model for CSNB2 Featuring Mutations in the Cacna1f Gene - Atorf, Jenny; Specht, D.; Maw, M.; Brandstätter, Johann Helmut; Dieck, S. Tom; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2010)
Keywords: photoreceptors; electroretinography: non-clinical; synapse

Electroretinographic responses that may reflect activity of parvo- and magnocellular post-receptoral visual pathways - Kremers, Jan; Link, Barbara (Journal of Vision, 2008)
The electroretinogram (ERG) is a complex retinal response to visual stimuli that contains receptoral and post-receptoral components. Here, data are presented using stimuli that isolate the responses of L (long wavelength sensitive)- or M (middle wavelength sensitive)- cones or that stimulate the two simultaneously. The data show that at a temporal frequency of 12 Hz, ERG responses are L- to M-cone opponent with little inter-individual variability. Furthermore, the ratio of L- to M-cone-driven response strengths in the ERGs is about unity. These are also properties of the L- and M-cone opponent chromatic channel mediated by parvocellular activity. Similar to the parvocellular-mediated temporal sensitivity, the ERG response is robust to moderate changes in state of cone adaptation. Thus, the 12-Hz ERG shares distinct characteristics with the post-receptoral red-green sensitive parvocellular pathway. At higher temporal frequencies, the responses are not cone opponent, the inter-individual variability is larger, the mean L/M ratio is larger than unity, and the responses change more strongly when the state of cone adaptation is altered. These properties are reminiscent of the magnocellular non-opponent channel. The data suggest that under well-controlled conditions, the ERG can be used to study post-receptoral processes of the visual system.
Keywords: electroretinography; magnocellular; parvocellular; L-cones; M-cones; cone opponency; luminance

Electroretinographic responses to luminance and cone-isolating white noise stimuli in macaques - Kremers, Jan; Aher, Avinash; Parry, Neil R. A.; Patel, Nimesh B.; Frishman, Laura J. (Frontiers in Neuroscience, 2022)
Electroretinograms (ERGs) are mass potentials with a retinal origin that can be measured non-invasively. They can provide information about the physiology of the retina. Often, ERGs are measured to flashes that are highly unnatural stimuli. To obtain more information about the physiology of the retina, we measured ERGs with temporal white noise (TWN) stimuli that are more natural and keep the retina in a normal range of operation. The stimuli can be combined with the silent substitution stimulation technique with which the responses of single photoreceptor types can be isolated. We characterized electroretinogram (ERG) responses driven by luminance activity or by the L- or the M-cones. The ERGs were measured from five anesthetized macaques (two females) to luminance, to L-cone isolating and to M-cone isolating stimuli in which luminance or cone excitation were modulated with a TWN profile. The responses from different recordings were correlated with each other to study reproducibility and inter-individual variability. Impulse response functions (IRFs) were derived by cross-correlating the response with the stimulus. Modulation transfer functions (MTFs) were the IRFs in the frequency domain. The responses to luminance and L-cone isolating stimuli showed the largest reproducibility. The M-cone driven responses showed the smallest inter-individual variability. The IRFs and MTFs showed early (high frequency) components that were dominated by L-cone driven signals. A late component was equally driven by L- and M-cone activity. The IRFs showed characteristic similarities and differences relative to flash ERGs. The responses to TWN stimuli can be used to characterize the involvement of retinal cells and pathways to the ERG response. It can also be used to identify linear and non-linear processes.
CRIS-Team WoS Importer:2022-09-02

Electroretinographic responses to periodic stimuli in primates and the relevance for visual perception and for clinical studies - Kremers, Jan; Huchzermeyer, Cord (Visual Neuroscience, 2024)
Currently, electroretinograms (ERGs) are mainly recorded while using flashes as stimuli. In this review, we will argue that strong flashes are not ideal for studying visual information processing. ERG responses to periodic stimuli may be more strongly associated with the activity of post-receptoral neurons (belonging to different retino-geniculate pathways) and, therefore, be more relevant for visual perception. We will also argue that the use of periodic stimuli may be an attractive addition to clinically available retinal electrophysiological methods.
CRIS-Team Scopus Importer:2024-12-06
Keywords: chromaticity; electroretinogram; luminance; psychophysics; repetitive stimuli; retino-geniculate pathways

Electroretinographic responses to photoreceptor specific sine wave modulation - Kremers, Jan; Pangeni, Gobinda (Journal of the Optical Society of America A-Optics Image Science and Vision, 2012)
Electroretinographic responses to cone and rod isolating stimuli and to simultaneous L- and M-cone modulation were measured at different temporal frequencies between 2 and 60 Hz and at two mean luminances using a four primary stimulator. The responses driven by each photoreceptor type had distinct characteristics. The responses to stimuli containing L- and/or M-cone stimulation indicated the presence of two underlying mechanisms that were active in distinct frequency regions. Between 2 and 12 Hz, the responses displayed properties that were reminiscent of the L-M-cone opponent system. At higher temporal frequencies, the electroretinograms were more determined by the luminance content in the stimuli.
EVALuna2:21078

ERG responses and the Ferry-Porter law - Kremers, Jan; Aher, Avinash; Huchzermeyer, Cord (Journal of the Optical Society of America A: Optics and Image Science, and Vision, 2025)
The Ferry-Porter law states that the psychophysically measured critical flicker fusion frequency (CFF) is linearly correlated with the logarithm of the mean luminance. We studied the relationship between the CFFs of L- and M-cone driven ERGs (five normal trichromats; sinusoidal modulation; 18% cone contrast) and mean luminance. The measurements were performed at seven mean luminances between 2.84 and 284 cd/m2. Close to the CFF, the ERG amplitudes versus temporal frequency could be described by a simple exponential function. The CFFs were higher for L- than for M-cone driven ERGs and depended linearly on the logarithm of the mean luminance (i.e., adhered to the Ferry-Porter law) with steeper slopes compared to psychophysical measurements.
CRIS-Team Scopus Importer:2025-05-02

ERG responses to heterochromatic stimuli that reflect L- and M-cone inputs and their additive or opponent interactions - Kremers, Jan; Bhatt, Deepak (Investigative Ophthalmology & Visual Science, 2016)

ERG signals elicited by temporal white noise in macaques - Kremers, Jan; Aher, Avinash; Parry, Neil; Patel, Nimesh Bhikhu; Frishman, Laura J. (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2022)
CRIS-Team WoS Importer:2022-09-30

Evaluation of a 345 nm Femtosecond Laser for Corneal Surgery with Respect to Intraocular Radiation Hazard - Menzel-Severing, Johannes; Petsch, Corinna; Tourtas, Theofilos; Polisetti, Naresh; Klenke, Joerg; Skerl, Katrin; Wuellner, Christian; Donitzky, Christof; Kruse, Friedrich; Kremers, Jan; Hammer, Christian (PLoS ONE, 2015)
We report our findings from a preclinical safety study designed to assess potential side effects of corneal ultraviolet femtosecond laser treatment on lens and retina.Refractive lenticules (-5 dpt) with a diameter of 6 mm were created in the right cornea of eight Dutch Belted rabbits. Radiant exposure was 0.5 J/cm² in two animals and 18 J/cm² in six animals. The presence of lens opacities was assessed prior to and up to six months following laser application using Scheimpflug images (Pentacam, Oculus) and backscatter analysis (Opacity Lensmeter 702, Interzeag). Ganzfeld flash and flicker electroretinogram (ERG) recordings were obtained from both eyes prior to and up to six weeks following laser application. At the study endpoint, retinas were examined by light microscopy.Independent of energy dose applied, no cataract formation could be observed clinically or with either of the two objective methods used. No changes in ERG recordings over time and no difference between treated and untreated eye were detected. Histologically, retinal morphology was preserved and retinal pigment epithelium as well as photoreceptor inner and outer segments appeared undamaged. Quantitative digital image analysis did not reveal cell loss in inner or outer nuclear layers.Our analysis confirms theoretical considerations suggesting that ultraviolet femtosecond laser treatment of the cornea is safe for intraocular tissues. Transmitted light including stray light induces no photochemical effects in lens or retina at energy levels much higher than required for the clinical purpose. These conclusions cannot be applied to eyes with pre-existing retinal damage, as these may be more vulnerable to light.
EVALuna2:4434

Evidence for two types of lateral interactions in visual perception of temporal signals - Teixeira, Claudio E. C.; Salomao, Railson C.; Rodrigues, Anderson R.; Horn, Folkert; Silveira, Luiz Carlos L.; Kremers, Jan (Journal of Vision, 2014)
The aim of this work was to investigate the mechanisms of lateral interactions involved in flicker perception. Furthermore, the spatial properties of the monoptic and dichoptic components of these mechanisms were studied. We quantified the perceived flicker strength (PFS) in the center of a test stimulus, which was simultaneously modulated with a surround stimulus of variable size. The modulation depth of a separate stimulus, identical to the center test stimulus but without the surround, was determined using a two-alternative forced choice procedure. Using LCD goggles synchronized to the frame rate of a CRT screen, the center and surround of the test stimulus were presented either monoptically or dichoptically. In the monoptic condition, center-surround interactions have subcortical and cortical origins. In the dichoptic condition, center-surround interactions must have a cortical origin. The difference between the dichoptic and the monoptic data is an estimate of the contribution of the subcortical mechanisms. At each condition (surround stimulus size; monoptic or dichoptic presentation), the PFS was measured for phase differences between center and surround stimuli. The PFS changed systematically with phase difference. It also was observed that the PFS in the center stimulus changed merely be the presence of a surround stimulus independently of the center-surround phase difference. We propose that this is a phase-independent mechanism related to contrast adaptation owing to the presence of surround modulation. Our data suggest that both phase-dependent and -independent mechanisms have cortical and subcortical origins. There were no systematic differences between the spatial properties of subcortical and cortical components involved in PFS modulation.
EVALuna2:21165

Feasibility of intravitreal injections and ophthalmic safety assessment in marmoset (Callithrix jacchus) monkeys - Niggemann, B.; Korte, S.; Hill, M.; Shenton, J.; Mansfield, K.; Pilling, A.; Mecklenburg, L.; Fridrichs-Gromoll, S.; Wiederhold, A.; Atorf, J.; Kremers, Jan (Toxicology Letters, 2015)

Flicker-defined form perimetry in glaucoma patients - Horn, Folkert; Kremers, Jan; Mardin, Christian Y.; Jünemann, Anselm; Adler, Werner; Tornow, Ralf-Peter (Graefes Archive For Clinical and Experimental Ophthalmology, 2015)
To assess the potential of flicker-defined form (FDF) perimetry to detect functional loss in patient groups with beginning glaucoma, and to evaluate the dynamic range of the FDF stimulus in individual patients and at individual test positions.FDF perimetry and standard automated perimetry (SAP) were performed at identical test locations (adapted G1 protocol) in 60 healthy subjects and 111 glaucoma patients. All patients showed glaucomatous optic disc appearance. Grouping within the glaucoma cohort was based on SAP-performance: 33 "preperimetric" open-angle glaucoma (OAG) patients, 28 "borderline" OAG (focal defects and SAP-mean defect (MD) <2 dB), 33 "early" OAG (SAP-MD < 5 dB), 17 "advanced" OAG. All participants were experienced in psychophysical and perimetric tests. Defect values and the areas under receiver operating characteristic curves (ROC) in patient groups were statistically compared.The values of FDF-MD in the preperimetric, borderline, and early OAG group were 2.7 ± 3.4 dB, 5.5 ± 2.6 dB, and 8.5 ± 3.4 dB respectively (all significantly above normal). The percentage of patients exceeding normal FDF-MD was 27.3 %, 60.7 %, and 87.9 % respectively. The age-adjusted FDF-mean defect (MD) of the G1X-protocol was not significantly correlated with refractive error, lens opacity, pupil size, or gender. Occurrence of ceiling effects (inability to detect targets at highest contrast) showed a high correlation with visual field losses (R = 0.72, p < 0.001). Local analysis indicates that SAP losses exceeding 5 dB could not be distinguished with the FDF technique.The FDF stimulus was able to detect beginning glaucoma damage. Patients with SAP-MD values exceeding 5 dB should be monitored with conventional perimetry because of its larger dynamic range.
EVALuna2:5485

Flicker ERGs Representing Chromaticity and Luminance Signals - Kremers, Jan; Rodrigues, Anderson Raiol; De Lima Silveira, Luiz Carlos; Da Silva Filho, Manoel (Investigative Ophthalmology & Visual Science, 2010)
PURPOSE. To test the hypothesis that electroretinograms (ERGs) reflect luminance activity when measured at high temporal frequencies and chromatic activity when measured near 12 Hz.METHODS. The authors measured the responses to stimuli in which the output of red and green light-emitting diodes was modulated in counterphase at different ratios, varying the luminance content in the stimulus while keeping the red-green chromatic contrast and its phase constant.RESULTS. The high temporal frequency electroretinography was determined mainly by the luminance contrast. At 12 Hz, electroretinographic response amplitudes and phases primarily reflected the red-green chromatic content of the stimulus. Control experiments, performed with a deuteranopic subject and with stimuli that silenced the rods and S-cones, excluded an explanation based on intrusion from rod-and S-cone-driven responses.CONCLUSIONS. It now is possible to perform noninvasive measurements of basic electrophysiological properties of the luminance and chromatic pathways on a retinal level, and their disease-related changes, in human observers. (Invest Ophthalmol Vis Sci. 20010;51:577-587) DOI:10.1167/iovs.09-3899

Frequency dependency of temporal contrast adaptation in normal subjects - Hohberger, Bettina; Roessler, Christopher W.; Jünemann, Anselm; Horn, Folkert; Kremers, Jan (Vision research, 2011)
The aim of this study was to determine the influence of temporal frequency of temporal contrast adaptation on contrast sensitivity in healthy subjects. Temporal contrast sensitivities (TCS) were measured monocularly in seven healthy subjects with a modified ERG full-field bowl stimulator at eight different test temporal frequencies (9, 15, 20, 25, 31, 37, 44, 51 Hz) using a two-alternative-forced-choice strategy. Before each presentation of the test stimulus, a 100% contrast adapting flicker stimulus was presented (frequencies: 9, 15, 20, 25, 31, 37, 44, 51, 100 Hz). At each adapting frequency, a complete set of TCSs was measured. All temporal contrast sensitivities decreased with increasing temporal frequencies. Adaptation led to a general temporal contrast sensitivity decrease. Largest adaptation effects were seen at an adaptation frequency of 25 Hz. Reduction of contrast sensitivity was significantly larger at 25 Hz adaptation than at 9 Hz adaptation (t-test of paired samples, Bonferroni corrected). The results of this study showed a general TCS decrease with the largest effect at an adaptation frequency of 25 Hz. This finding indicates that the contrast adaptation probably occurred in the magnocellular-pathway. In future clinical studies adaptation effects could be investigated in patients with reduced temporal contrast sensitivity.
EVALuna2:21010

Functional Protective Effects of Long-Term Memantine Treatment in the DBA/2J Mouse. - Atorf, Jenny; Scholz, Michael; Garreis, Fabian; Lehmann, Julia; Bräuer, Lars; Kremers, Jan (Documenta Ophthalmologica, 2013)
Purpose: To analyse the effects of long-term memantine treatment on the retinal physiology and morphology of DBA/2J mice. Methods: DBA/2J (D2J) mice received i.p. injections of the NMDA receptor antagonist memantine, which protects neurons from abnormally elevated glutamate levels, twice a day over a period of 7 months. At the age of 2, 6 and 10 months, the intraocular pressure (IOP) and electroretinograms (ERGs) were measured in all treated D2J mice, in untreated D2J controls and in C57Bl/6 (B6) wild-type mice. After the last measurement at the age of 10 months, the mice were killed and the retinae and the optic nerves were analysed morphologically. Results: The IOP increased with age in both D2J and B6 mice with a larger increase in the D2J strain. IOPs were not influenced by memantine treatment. The response amplitude of the scotopic flash ERG decreased with age in the D2J strain. This amplitude decrease, particularly that of the b-wave, was smaller in treated D2J mice. The retinae of treated D2J mice exhibited less peripheral degeneration of cone photoreceptors, and optic nerve neuropathy was less frequent. Conlcusions: Application of the NMDA receptor antagonist memantine diminished retinal neurodegeneration in the D2J mice and had a protective effect on the b-wave amplitude of the scotopic flash ERG. This protection may occur secondarily as memantine primarily acts on retinal ganglion cells. © 2013 Springer-Verlag Berlin Heidelberg.
UnivIS-Import:2015-03-09:Pub.2013.med.AI.LAIPDL.functi
Keywords: DBA/2J mouse; Electroretinography; Memantine; Neurodegeneration

Genetic disruption of bassoon in two mutant mouse lines causes divergent retinal phenotypes - Ryl, Miriam; Urbasik, Alexander; Gierke, Kaspar; Babai, Norbert; Joachimsthaler, Anneka; Feigenspan, Andreas; Frischknecht, Renato; Stallwitz, Nina; Fejtová, Anna; Kremers, Jan; von Wittgenstein, Julia; Brandstätter, Johann Helmut (The FASEB Journal, 2021)
Bassoon (BSN) is a presynaptic cytomatrix protein ubiquitously present at chemical synapses of the central nervous system, where it regulates synaptic vesicle replenishment and organizes voltage-gated Ca2+ channels. In sensory photoreceptor synapses, BSN additionally plays a decisive role in anchoring the synaptic ribbon, a presynaptic organelle and functional extension of the active zone, to the presynaptic membrane. In this study, we functionally and structurally analyzed two mutant mouse lines with a genetic disruption of Bsn-Bsngt and Bsnko -using electrophysiology and high-resolution microscopy. In both Bsn mutant mouse lines, full-length BSN was abolished, and photoreceptor synaptic function was similarly impaired, yet synapse structure was more severely affected in Bsngt/gt than in Bsnko/ko photoreceptors. The synaptic defects in Bsngt/gt retina coincide with remodeling of the outer retina-rod bipolar and horizontal cell sprouting, formation of ectopic ribbon synaptic sites-and death of cone photoreceptors, processes that did not occur in Bsnko/ko retina. An analysis of Bsngt/ko hybrid mice revealed that the divergent retinal phenotypes of Bsngt/gt and Bsnko/ko mice can be attributed to the expression of the Bsngt allele, which triggers cone photoreceptor death and neurite sprouting in the outer retina. These findings shed new light on the existing Bsn mutant mouse models and might help to understand mechanisms that drive photoreceptor death.
CRIS-Team Scopus Importer:2021-04-16
Keywords: active zone; bassoon; photoreceptor; photoreceptor death; ribbon synapse

Guest Editorial: Proceedings of the 20th Biennial Symposium of the International Colour Vision Society July 2009, Braga, Portugal - Buck, Steven; Barbur, John; Kremers, Jan; Nascimento, Sergio; Smithson, Hannah (20th Biennial Symposium of the International Colour Vision Society, 2010)

Heterochromatic flicker electroretinograms reflecting luminance and cone opponent activity in glaucoma patients - Salgueiro Barboni, Mirella Telles; Pangeni, Gobinda; Ventura, Dora Fix; Horn, Folkert; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2011)
To measure heterochromatic flicker electroretinograms (ERGs) at high (36 Hz) and intermediate (12 Hz) temporal frequencies to evaluate luminance and cone opponent responses, respectively, in glaucoma eyes with (perimetric) and without (preperimetric) visual field defects.Flicker ERGs were recorded from one randomly chosen dilated eye of 32 patients (mean age, 61 ± 11 years; 15 men, 17 women) from the Erlangen Glaucoma Registry and from 24 healthy volunteers (mean age, 43 ± 11 years; 14 men, 10 women). Red and green light-emitting diodes in a Ganzfeld stimulator were sine wave-modulated in counterphase. The responses were measured at 36 Hz, the frequency at which ERGs reflect activity of the luminance pathway, and at 12 Hz, the frequency at which ERGs reflect chromatic activity.Response amplitudes were similar in glaucoma patients and controls. Phase differences were observed in patients with visual field defects (perimetric) compared with the control group at 36 and 12 Hz in the first harmonic and second harmonic responses. Patients without visual field defects (preperimetric) showed phase differences for the second harmonic component at 36 Hz. No age effect on response amplitudes and phases was found in any of the subject groups (controls and patients).The responses displayed phase differences but not amplitude differences in perimetric glaucoma patients at both 36 and 12 Hz, suggesting that both magnocellular and parvocellular pathways are affected. Preperimetric glaucoma patients also showed phase differences. The response phase may be sensitive to early dysfunction of the inner retina. (ClinicalTrials.gov number, NCT00494923).
EVALuna2:21030

Heterochromatic Modulation Photometry can be used to measure Macular Pigment Optical Density - Huchzermeyer, Cord; Schlomberg, Juliane; Welge-Luessen, Ulrich; Berendschot, Tos T. J. M.; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2013)
Keywords: 587 macular pigment; 468 clinical research methodology; 478 contrast sensitivity

Heterogeneous presynaptic distribution of munc13 isoforms at retinal synapses and identification of an unconventional bipolar cell type with dual expression of munc13 isoforms: A study using munc13-exfp knock-in mice - Gierke, Kaspar; von Wittgenstein, Julia; Hemmerlein, Maike; Atorf, Jenny; Joachimsthaler, Anneka; Kremers, Jan; Cooper, Benjamin H.; Varoqueaux, Frederique; Regus-Leidig, Hanna; Brandstätter, Johann Helmut (International Journal of Molecular Sciences, 2020)
Munc13 isoforms are constituents of the presynaptic compartment of chemical synapses, where they govern important steps in preparing synaptic vesicles for exocytosis. The role of Munc13-1,-2 and-3 is well documented in brain neurons, but less is known about their function and distribution among the neurons of the retina and their conventional and ribbon-type chemical synapses. Here, we examined the retinae of Munc13-1-,-2-, and-3-EXFP knock-in (KI) mice with a combination of immunocytochemistry, physiology, and electron microscopy. We show that knock-in of Munc13-EXFP fusion proteins did not affect overall retinal anatomy or synapse structure, but slightly affected synaptic transmission. By labeling Munc13-EXFP KI retinae with specific antibodies against Munc13-1,-2 and-3, we found that unlike in the brain, most retinal synapses seem to operate with a single Munc13 isoform. A surprising exception to this rule was type 6 ON bipolar cells, which expressed two Munc13 isoforms in their synaptic terminals, ubMunc13-2 and Munc13-3. The results of this study provide an important basis for future studies on the contribution of Munc13 isoforms in visual signal processing in the mammalian retina.
CRIS-Team Scopus Importer:2020-11-06
Keywords: BrMunc13-2; Conventional synapse; Munc13-1; Munc13-3; Retina; Ribbon synapse; Type 6 ON bipolar cell; UbMunc13-2

High-frequency characteristics of L- and M-cone driven electroretinograms - Aher, Avinash; Jacob, Mellina M.; Kremers, Jan (Vision research, 2019)
Electroretinograms (ERGs) elicited by high temporal frequency (26–95 Hz) L- and M-cone isolating sine-wave stimuli were investigated in human observers for full-field (FF) and different spatially restricted stimulus sizes (70°, 50°, 30°, and 10° diameter). Responses to L- and M-cone isolating FF stimuli were maximal around 48 Hz and decreased gradually with increasing temporal frequency up to 95 Hz. The response maximum was shifted to about 30–32 Hz for both L- and M-cone driven responses obtained with spatially restricted stimuli. The M-cone driven responses could only be measured up to 54 Hz with 70° stimuli. The response amplitudes for L- and M-cones and L-/M-cone amplitude ratios decreased with decreasing stimulus size. The ERG response phases to L- and M-cone isolating stimuli decreased with increasing temporal frequency and were about −160° apart for all stimulus sizes up to 34 Hz. Further increase in the temporal frequency displayed a positive correlation between stimulus size and L-M phase difference. The ERG data indicate that the responses evoked by high temporal frequency cone isolating stimuli reflect two mechanisms, one that is more centrally located and displays a maximum at about 30–32 Hz and a peripheral mechanism that is sensitive to higher temporal modulations. We propose that the peripheral mechanism (FF ERGs) reflects magnocellular activity, whereas the central mechanism (ERGs with spatially restricted stimuli) is based on a parvocellular activity up to about 30 Hz.
CRIS-Team Scopus Importer:2019-05-16
Keywords: Electroretinograms; Magnocellular; Parvocellular; Stimulus size; Temporal frequency

How the use of dim red-light pre-recording affects ERG responses of mice with long-wavelength shifted opsin - Joachimsthaler, Anneka; Stallwitz, Nina; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2022)
CRIS-Team WoS Importer:2022-09-30

Human flicker electroretinography using different temporal modulations at mesopic and photopic luminance levels - Nagy, Balazs Vince; Salgueiro Barboni, Mirella Telles; Gomes Martins, Cristiane Maria; Da Costa, Marcelo Fernandes; Kremers, Jan; Ventura, Dora Fix (Documenta Ophthalmologica, 2014)
Electroretinographic measurement instruments allow the variation of several stimulation parameters enabling to study a wide range of retinal processes. The purpose of the present study was to measure human flicker electroretinograms (ERGs) varying temporal modulation, temporal frequency and mean luminance in the photopic and higher mesopic ranges where the change from cone to rod dominance occurs.Fourteen healthy subjects (mean age = 31 ± 6) participated in this study. ERG recordings were performed with the RetiPort system (Roland Consult, Germany). The stimuli were ON and OFF sawtooth waves, square wave and sine wave. The temporal frequencies were 4 and 8 Hz. The mean luminance varied from 1 to 60 cd/m(2).The results confirmed the possibility to distinguish between rod- and cone-dominated retinal responses when using the flicker ERG at different temporal frequencies and luminances. We have also evaluated the responses at luminance levels at which the transition between rod- and cone-dominated responses occurs. This transition between rod- and cone-dominated flicker ERG responses is indicated by a significant change in the response characteristics between 4 and 8 cd/m(2) (between 200 and 400 phot Td).The findings on the transition between rod- and cone-dominated ERGs along with the demonstration of ERG responses to different temporal flicker modulations might be informative for the electrophysiologists when setting up the stimulus at mesopic and photopic luminance levels.
EVALuna2:21188

Human photopic ON-and OFF-ERG responses elicited by square wave and sawtooth stimuli - Pangeni, Gobinda; Kremers, Jan (Psychology & Neuroscience, 2013)
Keywords: Electroretinogram; Contrast; Square wave stimuli; Sawtooth stimuli; Temporal frequency

Human S-Cone Electroretinograms Obtained by Silent Substitution Stimulation - Maguire, J.; Parry, N. R. A.; Kremers, Jan; Murray, I. J.; Mckeefry, D. (i-Perception, 2018)

Human S-cone electroretinograms obtained by silent substitution stimulation - Maguire, J.; Parry, N. R. A.; Kremers, Jan; Murray, I. J.; Mckeefry, D. (Journal of the Optical Society of America A-Optics Image Science and Vision, 2018)
We used triple silent substitution stimuli to characterize human S-cone electroretinograms (ERGs) in normal trichromats. Short-wavelength-cone (S-cone) ERGs were found to have different morphological features and temporal frequency response characteristics compared to ERGs derived from L-cones, M-cones, and rod photoreceptors in normal participants. Furthermore, in two cases of retinal pathology, blue cone monochromatism (BCM) and enhanced S-cone syndrome (ESCS), S-cone ERGs elicited by our stimuli were preserved and enhanced, respectively. The results from both normal and pathological retinae demonstrate that triple silent substitution stimuli can be used to generate ERGs that provide an assay of human S-cone function. (c) 2018 Optical Society of America

Identification and immunocytochemical characterization of Piccolino, a novel Piccolo splice variant selectively expressed at sensory ribbon synapses of the eye and ear - Regus-Leidig, Hanna; Ott, Corinna; Löhner, Martina; Atorf, Jenny; Fuchs, Michaela; Sedmak, Tina; Kremers, Jan; Fejtova, Anna; Gundelfinger, Eckart D.; Brandstätter, Johann Helmut (PLoS ONE, 2013)
Piccolo is one of the largest cytomatrix proteins present at active zones of chemical synapses, where it is suggested to play a role in recruiting and integrating molecules relevant for both synaptic vesicle exo- and endocytosis. Here we examined the retina of a Piccolo-mutant mouse with a targeted deletion of exon 14 in the Pclo gene. Piccolo deficiency resulted in its profound loss at conventional chemical amacrine cell synapses but retinal ribbon synapses were structurally and functionally unaffected. This led to the identification of a shorter, ribbon-specific Piccolo variant, Piccolino, present in retinal photoreceptor cells, bipolar cells, as well as in inner hair cells of the inner ear. By RT-PCR analysis and the generation of a Piccolino-specific antibody we show that non-splicing of intron 5/6 leads to premature translation termination and generation of the C-terminally truncated protein specifically expressed at active zones of ribbon synapse containing cell types. With in situ proximity ligation assays we provide evidence that this truncation leads to the absence of interaction sites for Bassoon, Munc13, and presumably also ELKS/CAST, RIM2, and the L-type Ca(2) (+) channel which exist in the full-length Piccolo at active zones of conventional chemical synapses. The putative lack of interactions with proteins of the active zone suggests a function of Piccolino at ribbon synapses of sensory neurons different from Piccolo's function at conventional chemical synapses.
EVALuna2:21139

Incremental and decremental L- and M-cone driven ERG responses: II. Sawtooth stimulation - Kremers, Jan; Pangeni, Gobinda; Tsaousis, Konstantinos; Mckeefry, Declan; Murray, Ian J.; Parry, Neil R. A. (Journal of the Optical Society of America A-Optics Image Science and Vision, 2014)
L- and M-cone driven on- and off-ERG responses and their interactions were examined using full field stimuli with sawtooth temporal profiles. The effects of temporal frequency and contrast were studied. ERG recordings were obtained from 21 trichromatic, 1 protanopic, and 1 deuteranopic subjects. ERGs to L-cone increments and decrements resembled those to M-cone decrements and increments, respectively (i.e., of the opposite polarity). Temporal frequency and contrast had little effect on the implicit times. All response components varied linearly with contrast. When stimulated simultaneously, the responsivities of most components were larger for counterphase than for inphase modulation. The retinal processing leading to an ERG response is reversed for L-and M-cone driven responses. (c) 2014 Optical Society of America

Incremental and decremental L- and M-cone-driven ERG responses: I. Square-wave pulse stimulation - Mckeefry, Declan; Kremers, Jan; Kommanapalli, Deepika; Challa, Naveen K.; Murray, Ian J.; Maguire, John; Parry, Neil R. A. (Journal of the Optical Society of America A-Optics Image Science and Vision, 2014)
Electroretinograms (ERGs) elicited by transient, square-wave L- and M-cone isolating stimuli were recorded from human trichromatic (n=19) and dichromatic (n=4) observers. The stimuli were generated on a four primary LED stimulator and were equated in terms of cone modulation (cone contrast=0.11) and retinal illuminance (12,000 trolands). L- and M-cone isolated ERGs had waveforms similar to those observed for luminance responses. However, M-cone ERGs exhibited a phase reversal in their responses to onset and offset stimuli relative to the L-cone responses. This on-off response reversal was observed in trichromats but not dichromats. Simultaneous counterphase and inphase combinations of L- and M-cone isolating stimuli generated responses that reflected chromatic and luminance processing, respectively. We conclude that L- and M-cone specific ERGs provide a measure of how photoreceptors contribute to postreceptoral mechanisms.
EVALuna2:21214

Interactions between rod and L-cone signals in deuteranopes: Gains and phases - Kilavik, B.E.; Kremers, Jan (Visual Neuroscience, 2006)
The dynamics of interactions between rod and L-cone driven signals were studied psychophysically in two deuteranopic observers. Flicker detection thresholds for different ratios of rod to L-cone modulation were measured at temporal frequencies between 1 and 15 Hz. A model, which assumes that rod and L-cone driven signals are vector added, can describe the threshold data adequately. We found that up to about 8-10 Hz temporal frequency, rod and L-cone signals interact additively, whereas at higher frequencies the interaction is subtractive. Rod and L-cone signal strengths depend similarly on temporal frequency and are maximal between 3 and 5 Hz. The phase difference between rod and L-cone signals increases linearly with temporal frequency, indicating that their responses have a delay difference of about 20 to 30 ms, consistent with involvement of the faster rod pathway. The data would suggest a nearly complete additivity of the rod and cone driven signals when using flashed stimuli. But, literature data showed only partial additivity of the two, suggesting that different postreceptoral mechanisms are involved in the two tasks.
Keywords: rod; L-cone; temporal frequency; gain; latency difference

In vivo electroretinographic differentiation of rod, short-wavelength and long/medium-wavelength cone responses in dogs using silent substitution stimuli - Mowat, Freya M.; Wise, Elisabeth; Oh, Annie; Foster, Melanie L.; Kremers, Jan (Experimental Eye Research, 2019)
The canine species has dichromatic color vision comprising short-wavelength (S-) and long/medium (L/M-) wavelength-sensitive cones with peak spectral sensitivity of 429–435 nm and 555 nm respectively. Although differentiation of rod- and cone-mediated responses by electroretinogram (ERG) in dogs is commonly performed, and standards have been developed based on standards for human observers, methods to differentiate S- and L/M-cone responses in dogs have not been described. We developed flicker protocols derived from previously published rod and cone spectral sensitivities. We used a double silent substitution paradigm to isolate responses from each of the 3 photoreceptor subclasses. ERG responses were measured to sine-wave modulation of photoreceptor excitation at different temporal frequencies (between 4 and 56 Hz) and mean luminance (between 3.25 and 130 cd/m2) on 6 different normal dogs (3 adult female, and 3 adult male beagles) and one female beagle dog with suspected hereditary congenital stationary night blindness (CSNB). Peak rod driven response amplitudes were achieved with low frequency (4 Hz, maximal range 4–12 Hz) and low mean luminance (3.25 cd/m2). In contrast, peak L/M-cone driven response amplitudes were achieved with high frequency (32 Hz, maximal range 28–44 Hz) and high mean luminance (32.5–130 cd/m2). Maximal S-cone driven responses were obtained with low frequency stimuli (4 Hz, maximal range 4–12 Hz) and 32.5–130 cd/m2 mean luminance. The dog with CSNB had reduced rod- and S-cone-driven responses, but normal/supernormal L/M cone-driven responses. We have developed methods to differentiate rod, S- and L/M-cone function in dogs using silent substitution methods. The influence of temporal frequency and mean luminance on the ERGs originating in each photoreceptor type can now be studied independently. Dogs and humans have similar L/M cone responses, whereas mice have significantly different L/M responses. This work will facilitate a greater understanding of canine retinal electrophysiology and will complement the study of canine models of human hereditary photoreceptor disorders.
CRIS-Team Scopus Importer:2019-06-25
Keywords: Congenital stationary night blindness; dog; Electroretinogram; L/M-cone; Photoreceptor; Rod; S-Cone; Silent substitution

ISCEV extended protocol for the photopic negative response (PhNR) of the full-field electroretinogram - Frishman, Laura; Sustar, Maja; Kremers, Jan; Mcanany, J. Jason; Sarossy, Marc; Tzekov, Radouil; Viswanathan, Suresh (Documenta Ophthalmologica, 2018)
The International Society for Clinical Electrophysiology of Vision (ISCEV) Standard for full-field electroretinography (ERG) describes a minimum procedure, but encourages more extensive testing. This ISCEV extended protocol describes an extension to the ERG Standard, namely the photopic negative response (PhNR) of the light-adapted flash ERG, as a well-established technique that is broadly accepted by experts in the field. The PhNR is a slow negative-going wave after the b-wave that provides information about the function of retinal ganglion cells and their axons. The PhNR can be reduced in disorders that affect the innermost retina, including glaucoma and other forms of optic neuropathy. This document, based on existing literature, provides a protocol for recording and analyzing the PhNR in response to a brief flash. The protocol includes full-field stimulation, a frequency bandwidth of the recording in which the lower limit does not exceed 0.3 Hz, and a spectrally narrowband stimulus, specifically, a red flash on a rod saturating blue background. Suggested flash strengths cover a range up to and including the minimum required to elicit a maximum amplitude PhNR. This extended protocol for recording the PhNR provides a simple test of generalized retinal ganglion cell function that could be added to standard ERG testing.
EVALuna2:34923

ISCEV extended protocol for the photopic On-Off ERG - Sustar, Maja; Holder, Graham E.; Kremers, Jan; Barnes, Claire S.; Lei, Bo; Khan, Naheed W.; Robson, Anthony G. (Documenta Ophthalmologica, 2018)
The International Society for Clinical Electrophysiology of Vision (ISCEV) standard for full-field electroretinography (ERG) describes a minimum procedure, but encourages more extensive testing. This ISCEV extended protocol describes an extension to the ERG standard, namely the photopic On-Off ERG, and outlines common clinical applications. A light stimulus duration of 150-200 ms is used in the presence of a rod-suppressing background to elicit cone-driven On- and Off-system ERG components. The On-response occurs after the stimulus onset and has a negative a-wave and positive b-wave. The Off d-wave is a positive component evoked by stimulus offset. Common diagnoses that may benefit from additional photopic On-Off ERG testing include retinal dystrophies and retinal disorders that cause dysfunction at a level that is post-phototransduction or post-receptoral. On-Off ERGs assess the relative involvement of On- and Off-systems and may be of use in the diagnosis of disorders such as complete and incomplete congenital stationary night blindness (complete and incomplete CSNB), melanoma-associated retinopathy, and some forms of autoimmune retinopathy. The photopic On-Off ERGs may also be useful in X-linked retinoschisis, Batten disease, Duchenne muscular dystrophy, spinocerebellar degeneration, quinine toxicity, and other retinal disorders.
EVALuna2:34922
Keywords: Retinopathy; Retinal dystrophy; On–Off ERG; Long-duration ERG; Bipolar cells; Full-field ERG; International Society of Clinical Electrophysiology of Vision (ISCEV); Clinical standards; Electroretinogram (ERG)

Lack of a Retinal Phenotype in a Syne-2/Nesprin-2 Knockout Mouse Model - Falk, Nathalie; Joachimsthaler, Anneka; Keßler, Kristin; Lux, Uwe; Noegel, Angelika Anna; Kremers, Jan; Brandstätter, Johann Helmut; Gießl, Andreas (Cells, 2019)
Syne-2 (also known as Nesprin-2) is a member of a family of proteins that are found primarily in the outer nuclear membrane, as well as other subcellular compartments. Syne-2 contains a C-terminal KASH transmembrane domain and is part of a protein network that associates the nuclear envelope to the cytoskeleton via the binding to actin filaments. Syne-2 plays a role in nuclear migration, nuclear positioning during retinal development, and in ciliogenesis. In a previous study, we showed a connection between Syne-2 and the multifunctional scaffold protein Pericentrin (Pcnt). The elimination of the interaction of Syne-2 and Pcnt showed defects in nuclear migration and the formation of outer segments during retinal development, as well as disturbances in centrosomal migration at the beginning of ciliogenesis in general. In this study, the Syne-2 KO mouse model Nesprin-2oABD (Syne-2(tm1Ngl), MGI) with special attention to Pcnt and ciliogenesis was analyzed. We show reduced expression of Syne-2 in the retina of the Syne-2 KO mouse but found no significant structural-and only a minor functional-phenotype. For the first time, detailed expression analyses showed an expression of a Syne-2 protein larger than 400 kDa (similar to 750 kDa) in the Syne-2/Nesprin-2 KO mouse. In conclusion, the lack of an overt phenotype in Syne-2/Nesprin-2 KO mice suggests the usage of alternative translational start sites, producing Syne-2 splice variants with an intact Pcnt interaction site. Nevertheless, deletion of the actin-binding site in the Syne-2/Nesprin-2 KO mouse revealed a high variability in scotopic oscillatory potentials assuming a novel function of Syne-2 in synchronizing inner retinal processes.
CRIS-Team WoS Importer:2019-11-29

L- and M-cone driven temporal contrast sensitivity is reduced at low frequencies in patients with Stargardt's disease - Huchzermeyer, Cord; Pasutto, Francesca; Wiesmann da Silva Reis, André; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2017)

L- and M-cone input to 12Hz and 30Hz flicker ERGs across the human retina - Challa, N. K.; Mckeefry, D.; Parry, N. R. A.; Kremers, Jan; Murray, I. J.; Panorgias, Athanasios (Ophthalmic and Physiological Optics, 2010)
Keywords: Human retina; Luminance; Electroretinograms; Colour

L- and M-Cone Input to Opponent and Non-Opponent Channels as a Function of Retinal Eccentricity in the Human Erg - Kremers, Jan; Challa, N. K.; Parry, N. R. A.; Murray, I. J.; Panorgias, A.; Mckeefry, D. (Investigative Ophthalmology & Visual Science, 2010)
Keywords: electroretinography: non-clinical; color vision; photoreceptors

L- and M-cone isolating ERGs: LED versus CRT stimulation - Murray, I. J.; Kremers, Jan; Parry, N. R. A. (Visual Neuroscience, 2008)
Keywords: CRT; L-cones; Electroretinograms; M-cones; LED

Lateral interactions in visual perception of temporal signals: Cortical and subcortical components - Teixeira, Claudio E.C.; Silveira, Luiz Carlos L.; Kremers, Jan (Psychology & Neuroscience, 2011)
Keywords: Dichoptic lateral interactions; Cortical interactions; Monoptic lateral interactions; Flicker perception; Temporal processing; Subcortical interactions

Linking ERG recordings to psychophysical data in human subjects - Kremers, Jan; Aher, Avinash; Stuewe, Karin (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2021)
CRIS-Team WoS Importer:2021-09-24

Linking lateral interactions in flicker perception to lateral geniculate nucleus cell responses - Kozyrev, Vladislav; Silveira, Luiz Carlos L.; Kremers, Jan (The Journal of Physiology, 2007)
The perception of flicker strength in a circular stimulus can be changed by altering the relative temporal phase of a simultaneously flickering surrounding annulus: perceived flicker is weak when the two stimuli are modulated in-phase and strong when the two are modulated in counter-phase. Previously, we found that responses of single neurons in the monkey lateral geniculate nucleus (LGN) to such stimuli resemble the psychophysical data. On the basis of the resemblance in data, it was proposed that the physiological basis for the flicker perception may be present as proximal as the LGN. To strengthen this hypothesis, we simulated the response of an array of LGN neurons, the receptive fields (RFs) of which are covered by the stimulus. The simulations were based upon single-cell recordings in the LGN of anaesthetized marmosets (Callithrix jacchus) using the same stimuli as previously. The measurements were repeated for different spatial displacement between the stimulus and the RF. The responses depended upon the spatial displacement and the relative phase between centre and surround stimuli. The neuronal responses can be adequately described by a difference-of-Gaussians (DOG) model with a time delay in the RF surround. The model responses at different displacements can be considered to be identical to the output of an array of ideal and identical LGN cells with different RF locations. To be able to describe physiological and psychophysical data, obtained at different stimulus contrasts, it was necessary to consider previously described non-linear interactions between the RF centres and surrounds. We applied a spatial peak-to-trough detector with a subsequent saturation and threshold to simulate a simple cortical decision mechanism. The output of this peak-to-trough detector could adequately describe the psychophysical data.

L-/M-cone opponency in visual evoked potentials of human cortex - Salgueiro Barboni, Mirella Telles; Nagy, Balazs Vince; Gomes Martins, Cristiane Maria; Oliveria Bonci, Daniela Maria; Hauzman, Einat; Aher, Avinash; Tsai, Tina I.; Kremers, Jan; Ventura, Dora Fix (Journal of Vision, 2017)
L and M cones send their signals to the cortex using two chromatic (parvocellular and blue-yellow koniocellular) and one luminance (magnocellular) pathways. These pathways contain ON and OFF subpathways that respond to excitation increments and decrements respectively. Here, we report on visually evoked potentials (VEP) recordings that reflect L- and M-cone driven increment (LI and MI) and decrement (LD and MD) activity. VEP recordings were performed on 12 trichromats and four dichromats (two protanopes and two deuteranopes). We found that the responses to LI strongly resembled those to MD, and that LD and MI responses were very similar. Moreover, the lack of a photoreceptor type (L or M) in the dichromats led to a dominance of the ON pathway of the remaining photoreceptor type. These results provide electrophysiological evidence that antagonistic L/M signal processing, already present in the retina and the lateral geniculate nucleus (LGN), is also observed at the visual cortex. These data are in agreement with results from human psychophysics where MI stimuli lead to a perceived brightness decrease whereas LI stimuli resulted in perceived brightness increases. VEP recording is a noninvasive tool that can be easily and painlessly applied. We propose that the technique may provide information in the diagnosis of color vision deficiencies.
EVALuna2:21340

Long Term Follow-Up of Preperimetric Open-Angle Glaucoma: Improvement of the Visual Field in Morphological Stable Patients Only - Jünemann, Anselm; Bellios, N.; Lämmer, Robert; Link, B.; Mardin, C. Y.; Kremers, Jan; Kruse, Friedrich; Horn, Folkert (Investigative Ophthalmology & Visual Science, 2010)
Keywords: visual fields

Luminance white noise electroretinograms (wnERGs) in mice - Stallwitz, Nina; Joachimsthaler, Anneka; Kremers, Jan (Frontiers in neuroscience, 2022)
PurposeTo record and analyse electroretinograms (ERGs) to luminance stimuli with white noise temporal profiles in mice. White noise stimuli are expected to keep the retina in a physiologically more natural state than, e.g., flashes. The influence of mean luminance (ML) was studied. MethodsElectroretinograms to luminance temporal white noise (TWN) modulation (wnERGs) were measured. The white noise stimuli contained all frequencies up to 20 Hz with equal amplitudes and random phases. Responses were recorded at 7 MLs between -0.7 and 1.2 log cd/m(2). Impulse response functions (IRFs) were calculated by cross correlating the averaged white noise electroretinogram (wnERG) responses with the stimulus. Amplitudes and latencies of the initial trough and subsequent peak in the IRFs were measured at each ML. Fourier transforms of the IRFs resulted in modulation transfer functions (MTFs). wnERGs were averaged across different animals. They were measured twice and the responses at identical instances in the 1st and 2nd recordings were plotted against each other. The correlation coefficient (r(repr)(2)) of the linear regression quantified the reproducibility. The results of the first and second measurement were further averaged. To study the underlying ERG mechanisms, the ERG potentials at the different MLs were plotted against those at the lowest and highest ML. The correlation coefficients (r(ML)(2)) were used to quantify their similarities. ResultsThe amplitudes of the initial (a-wave-like) trough of the IRFs increased with increasing ML. The following positive (b-wave-like) peak showed a minimum at -0.4 log cd/m(2) above which there was a positive correlation between amplitude and ML. Their latencies decreased monotonously with increasing ML. In none of the IRFs, oscillatory potential (OP)-like components were observed. r(repr)(2) values were minimal at a ML of -0.1 log cd/m(2), where the MTFs changed from low-pass to band-pass. r(ML)(2) values increased and decreased with increasing ML when correlated with responses obtained at the highest or the lowest ML, respectively. ConclusionWhite noise electroretinograms can be reliably recorded in mice with luminance stimuli. IRFs resemble flash ERGs superficially, but they offer a novel procedure to study retinal physiology. New components can be described in the IRFs. The wnERGs are either rod- or cone-driven with little overlap.
CRIS-Team WoS Importer:2023-01-06

Macular pigment optical density measured by heterochromatic modulation photometry - Huchzermeyer, Cord; Schlomberg, Juliane; Welge-Lüssen, Ulrich-Christoph; Berendschot, Tos T. J. M.; Pokorny, Joel; Kremers, Jan (PLoS ONE, 2014)
To psychophysically determine macular pigment optical density (MPOD) employing the heterochromatic modulation photometry (HMP) paradigm by estimating 460 nm absorption at central and peripheral retinal locations.For the HMP measurements, two lights (B: 460 nm and R: 660 nm) were presented in a test field and were modulated in counterphase at medium or high frequencies. The contrasts of the two lights were varied in tandem to determine flicker detection thresholds. Detection thresholds were measured for different R:B modulation ratios. The modulation ratio with minimal sensitivity (maximal threshold) is the point of equiluminance. Measurements were performed in 25 normal subjects (11 male, 14 female; age: 30±11 years, mean ± sd) using an eight channel LED stimulator with Maxwellian view optics. The results were compared with those from two published techniques - one based on heterochromatic flicker photometry (Macular Densitometer) and the other on fundus reflectometry (MPR).We were able to estimate MPOD with HMP using a modified theoretical model that was fitted to the HMP data. The resultant MPODHMP values correlated significantly with the MPODMPR values and with the MPODHFP values obtained at 0.25° and 0.5° retinal eccentricity.HMP is a flicker-based method with measurements taken at a constant mean chromaticity and luminance. The data can be well fit by a model that allows all data points to contribute to the photometric equality estimate. Therefore, we think that HMP may be a useful method for MPOD measurements, in basic and clinical vision experiments.
EVALuna2:21179

Measuring retinal function in the mouse - Kremers, Jan; Tanimoto, Naoyuki (Mouse Retinal Phenotyping, 2018)
Keywords: Anesthesia; B-wave; A-wave; Analysis; ERG; Oscillatory potentials; Electroretinogram; Equipment; Stimulators

Melanopsin interacting with the cone-mediated white noise electroretinogram (wnERG) - Adhikari, Prakash; Zele, Andrew J.; Cao, Dingcai; Kremers, Jan; Feigl, Beatrix K. (Investigative Ophthalmology & Visual Science, 2018)

Mesopic and Photopic Rod and Cone Photoreceptor-Driven Visual Processes in Mice With Long-Wavelength-Shifted Cone Pigments - Tsai, Tina I.; Joachimsthaler, Anneka; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2017)
The clearer divergence in spectral sensitivity between native rod and human L-cone (L*-cone) opsins in the transgenic Opn1lwLIAIS mouse (LIAIS) allows normal visual processes mediated by these photoreceptor subtypes to be isolated effectively using the silent substitution technique. The objective of this study was to further characterize the influence of mean luminance and temporal frequency on the functional properties of signals originating in each photoreceptor separately and independently of adaptation state in LIAIS mice.Electroretinographic (ERG) recordings to sine-wave rod and L*-cone modulation at different mean luminances (0.1-130.0 cd/m2) and temporal frequencies (6-26 Hz) were examined in anesthetized LIAIS (N = 17) and C57Bl/6 mice (N = 8).We report maximum rod-driven response with 8-Hz modulation at 0.1 to 0.5 cd/m2, which was almost four times larger than maximum cone-driven response at 8 Hz, 21.5 to 130 cd/m2. Over these optimal luminances, both rod- and cone-driven response amplitudes exhibited low-pass functions with similar frequency resolution limits, albeit their distinct luminance sensitivities. There were, however, two distinguishing features: (1) the frequency-dependent amplitude decrease of rod-driven responses was more profound, and (2) linear relationships describing rod-driven response phases as a function of stimulus frequency were steeper.Employing the silent substitution method with stimuli of appropriate luminance on the LIAIS mouse (as on human observers) increases the specificity, robustness, and scope to which photoreceptor-driven responses can be reliably assayed compared to the standard photoreceptor isolation methods.
EVALuna2:21338
Keywords: Cone; Photoreceptor isolation; Rod; Electrophysiology; Mouse model

Mesopic rod and S-cone interactions revealed by modulation thresholds - Zele, Andrew J.; Kremers, Jan; Feigl, Beatrix (Journal of the Optical Society of America A-Optics Image Science and Vision, 2012)
We analyzed mesopic rod and S-cone interactions in terms of their contributions to the blue-yellow opponent pathway. Stimuli were generated using a four-primary colorimeter. Mixed rod and S-cone modulation thresholds (constant L-, M-cone excitation) were measured as a function of their phase difference. Modulation amplitude was equated using threshold units and contrast ratios. This study identified three interaction types: (1) a linear and antagonistic rod:S-cone interaction, (2) probability summation, and (3) a previously unidentified mutual nonlinear reinforcement. Linear rod:S-cone interactions occur within the blue-yellow opponent pathway. Probability summation involves signaling by different postreceptoral pathways. The origin of the nonlinear reinforcement is possibly at the photoreceptors.
EVALuna2:21077

Modulation of flash ERGs by dynamic backgrounds - Kremers, Jan; Aher, Avinash; Huchzermeyer, Cord (Documenta Ophthalmologica, 2022)
Purpose The aim of this study was to characterize the signal processing mechanisms that lead to an ERG response and to use this characterization for obtaining more robust responses in patients who display feeble responses with standard recordings. We studied the influence of sinusoidally modulating backgrounds on flash ERGs and the relationship between the ERG components' amplitudes and the momentary Weber fraction of the flash stimulus. Methods ERG recordings were performed in nine healthy subjects and three RP patients. In four normal subjects, we measured the response to flashes (500 cd/m(2), 1 ms duration) on a steady background (50 cd/m(2)) and on a sine wave (50 cd/m(2) mean luminance) modulating background at 1, 5, 10, and 25 Hz temporal frequencies. The flashes were delivered at eight different phases (0-315 degrees in a step of 45 degrees) during the modulating background sine wave. The responses to the backgrounds were also recorded and subtracted from the responses to flash plus modulating backgrounds to obtain the flash ERGs at the different phases. The recordings in the remaining five normal subjects and the RP patients were performed with a subset of these stimuli. Results The flash ERGs were strongly modulated by the backgrounds particularly at low frequencies and were enhanced when the momentary Weber fraction was large. The amplitudes of the components could be described by the Weber fraction plus a saturating nonlinearity and a delay in the processing of background luminance. The strength of the modulation decreased with increasing peak time of the component. Furthermore the background luminance delay was positively correlated with the peak time. The effect was also present in RP patients. Conclusions A sine wave background of about 1 Hz can be used to enhance ERG responses. Weber fraction of the flashes is an adequate quantification of stimulus for describing the amplitudes of the ERGs. The data provide basic information on how background luminance is processed in ERG generating mechanisms. The response enhancement can be used in clinical applications to obtain a more robust comparison between normal and patient data.
CRIS-Team WoS Importer:2022-11-04

Mouse Cones Adapt Fast, Rods Slowly In Vivo - Joachimsthaler, Anneka; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2019)
Purpose: To study rod- and cone-driven adaptation dynamics separately, we used the silent substitution technique to selectively stimulate rods or cones in the Opn1lwLIAIS (LIAIS) mouse, in which the native M-cone pigment is replaced by a human L-cone pigment (L*). Methods: ERG recordings were performed on anesthetized LIAIS mice. ERG stimuli were sinusoidally modulated. After 10 minutes of adaptation to 0.4 candela per square meter (cd/m2) ERGs were measured, followed by 11-minute adaptation to 8.8 cd/m2 background and recordings directly after the luminance increase and every second minute. Finally, during adaptation to 0.4 cd/m2 for 32 minutes, ERG responses were recorded directly after the change in background and every second minute. This protocol was repeated with rod-isolating stimuli (8 Hz; 75% rod contrast), L*-cone-isolating stimuli (12 Hz; 55% cone contrast) and white light (8 Hz and 12 Hz; 100% Michelson contrast). Results: At 8.8 cd/m2, responses directly displayed photopic response properties without further changes in either cone or white light responses. Rod-driven responses were very small. After the return to 0.4 cd/m2, both rod-driven and white light responses increased over a time course of about 30 minutes. Cone-driven responses were very small. Response phases changed directly after a change in background without further alterations. Conclusions: Rod- and cone-driven signal pathways display strongly different adaptation characteristics: adaptation of cone-driven responses to photopic conditions is very fast, whereas rod-driven responses change with a time course up to 30 minutes during scotopic conditions. Luminance responses are cone-driven at 8.8 cd/m2 and rod-driven at 0.4 cd/m2.
CRIS-Team Scopus Importer:2019-06-21

Multidimensional Functional Phenotyping Based on Photoreceptor-Directed Temporal Contrast Sensitivity Defects in Inherited Retinal Diseases - Huchzermeyer, Cord; Stingl, Katarina; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2025)
PURPOSE. To identify patterns of functional defects in perifoveal photoreceptor-directed temporal contrast sensitivities (tCSs) in patients with inherited retinal diseases. METHODS. We retrospectively studied patients with RP1L1-associated occult macular dystrophy (OMD), Stargardt disease (STGD), and RP. Photoreceptor-directed tCS directed at L-, M-, S-cones and rods at different temporal frequencies were measured using a four-primary LED-stimulator with an annular test field (2° inner diameter and 12° outer diameter). Mean defects (MDs) were calculated by subtracting sensitivities from age-correlated normal values and averaging defects in frequency ranges where single postreceptoral pathways mediate flicker detection. Each patient was characterized by 6 MD values (one value each for S-cones [SMD] rods [RMD]; two values each for L- [LMDlow/high] and M-cones [MMDlow/high], where low refers to 1–6 Hz and high to 8–20 Hz temporal frequency ranges). Groups of similar phenotypes were identified with (supervised) decision trees and (unsupervised) hierarchical classification trees (based on nearest neighbors) and compared with the clinical diagnoses. RESULTS. The pruned decision tree used RMD for separating RP/STGD from normal/OMD, LMDlow for separating OMD from normal, and SMD for discriminating between RP and STGD. The accuracy was 66%. The hierarchical tree (independent of clinical diagnosis) was cut to four clusters, resulting in one cluster containing mainly normal participants, one cluster with severe L- and M-cone defects caused by OMD or STGD, one cluster with severe rod defects (4/5 with RP) and a large cluster with intermediate rod and cone defects that was dominated by RP and STGD patients. CONCLUSIONS. LMDlow, SMD, and RMD were the most important parameters. Photoreceptor-directed tCSs allow sophisticated functional phenotyping of inherited retinal diseases and complement other structural and functional parameters for genotype–phenotype correlations.
CRIS-Team Scopus Importer:2025-05-02
Keywords: occult macular dystrophy; retinitis pigmentosa; silent substitution; Stargardt’s disease; temporal contrast sensitivity

Multifocal electroretinographical changes in monkeys with experimental ocular hypertension: a longitudinal study - Kremers, Jan; Doelemeyer, Arno; Polska, Elzbieta A.; Moret, Fabrice; Lambert, Christian; Lambrou, George N. (Documenta Ophthalmologica, 2008)
Purpose To study the time course of changes in the multifocal electroretinograms (mfERG) in monkeys with experimental ocular hypertension (OHT). Methods The mfERGs were recorded in 12 eyes out of 6 monkeys. Two baseline measurements were used to quantify the reproducibility, the inter-ocular and the inter-individual variability of the ERG signals. Thereafter, the trabeculum of one eye of each animal was laser-coagulated in one to three sessions to induce OHT. ERG measurements were repeated regularly in a period of 18 months and the changes in ERG waveforms were quantified. Results All animals displayed OHT (between 20 and 50 mmHg) in the laser-coagulated eyes. An ERG change was defined as the sum of differences during the first 90 ms between the laser-coagulated eye and the same eye before laser coagulation and between the laser-coagulated eye and the non-treated fellow eye. Three animals displayed significant changes for nearly all retinal areas and all stimulus conditions. The three remaining animals displayed significant changes only in one comparison, indicating very mild changes. The data indicate that a high stimulus contrast is more sensitive to detect changes, probably because of a better signal-to-noise ratio. Moreover, the comparisons with the fellow eye are more sensitive to detect changes than comparisons with the measurements before laser-coagulation. Conclusions OHT does not always lead to ERG changes. Comparisons with fellow eyes using high contrast stimuli are more sensitive to detect changes related to OHT.
Keywords: glaucoma; multifocal electroretinograms; non-human primates; ocular hypertension

Multifocal electroretinography after high dose chloroquine therapy for malaria - de Carvalho, Aline Correa; Schwarz, Martin; Souza, Givago da Silva; Gomes, Bruno Duarte; Rosa, Alexandre Antônio Marques; da Silva Ventura, Ana Maria Revoredo; de Souza, José Maria; Silveira, Luiz Carlos de Lima; Kremers, Jan (Journal of Ophthalmic & Vision Research, 2013)
To investigate changes in multifocal electroretinography (mfERG) parameters associated with high dose chloroquine therapy for treatment of malaria in the Amazonia region of Brazil.Forty-eight subjects who had received chloroquine treatment for single or multiple malaria infections with a cumulative dose ranging from 1,050 to 27,000mg were included. The control group consisted of 37 healthy aged-matched subjects. Data was collected on amplitude and implicit time of the N1, P1 and N2 waves in the central macular hexagon (R1) and in five concentric rings at different retinal eccentricities (R2-R6).No significant difference was observed in any mfERG parameter between chloroquine treated patients and control subjects. A comparison with previous data obtained from patients with rheumatologic disorders in the same region of Brazil who had received larger cumulative doses of chloroquine and had displayed mfERG changes, indicated that retinal toxicity seems to be dependent on cumulative dose.Lack of mfERG changes in the current study suggests that intensive high dose chloroquine therapy for treatment of malaria is not associated with retinal toxicity.
EVALuna2:21145

Multifocal Electroretinography with simultaneous fundus imaging in mice - Dutescu, R. Michael; Skosyrski, Sergej; Kociok, Norbert; Semkova, Irina; Mergler, Stefan; Atorf, Jenny; Joussen, Antonia; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2013)
Keywords: 508 electrophysiology: non-clinical; 578 laser; 612 neuro-ophthalmology: diagnosis

Multifocal ERG recordings under visual control of the stimulated fundus in mice - Dutescu, Ralf M.; Skosyrski, Sergej; Kociok, Norbert; Semkova, Irina; Mergler, Stefan; Atorf, Jenny; Joussen, Antonia M.; Strauss, Olaf; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2013)
Therapeutic approaches to retinal disease require a continuous monitoring of functional improvement over lesion areas that sometimes cannot be shown in full-field ERG. The aim of this study was to assess the usefulness of multifocal electroretinograms (mfERGs) under visual control using scanning laser ophthalmoscopy (SLO) for evaluation of local retinopathy in mice.mfERGs were optimized for recordings in C57BL/6 mice by varying dark steps between each stimuli, background intensity, and the numbers of hexagons. Local retinopathy was induced by argon laser photocoagulation with different spot sizes and retinal irradiances. mfERG recordings were performed before, and 10 days and 4 weeks after laser treatment. In each recording, the central hexagon was positioned on the optic nerve head visualized by SLO images. The amplitudes of the P1 response components were analyzed as a function of retinal location.The mfERG amplitudes depended on stimulus condition. The P1 amplitudes increased with increasing number of dark frames in the m-sequence and with decreasing number of hexagons. A stimulus with 19 hexagons and four dark frames was chosen because substantial response amplitudes could be achieved while preserving sufficient spatial resolution. In the untreated eyes, the response to the central hexagon, stimulating the optic nerve head, was smaller than those to the surrounding hexagons. The responses to hexagons stimulating photocoagulated areas were reduced compared with the responses of surrounding areas. The amplitude reduction was more pronounced when the coagulated areas were larger and when higher energies were used.Areas with decreased sensitivities to light stimulation (either the optic nerve head or damaged retinal areas) can be detected and correlated with the retinal images and in the mfERG responses. We demonstrate that the mfERG technique is able to reproducibly detect the functional consequences of a local treatment.
EVALuna2:21138

Mutation in Bmpr1b Leads to Optic Disc Coloboma and Ventral Retinal Gliosis in Mice - Yan, Xiaohe; Atorf, Jenny; Ramos, David; Thiele, Frank; Weber, Susanne; Dalke, Claudia; Sun, Minxuan; Puk, Oliver; Michel, Dian; Fuchs, Helmut; Klaften, Matthias; Przemeck, Gerhard K. H.; et al. (Investigative Ophthalmology & Visual Science, 2020)
PURPOSE. The clinical phenotype of retinal gliosis occurs in different forms; here, we characterize one novel genetic feature, (i.e., signaling via BMP-receptor 1b).
CRIS-Team WoS Importer:2020-03-20

Neue Techniken zur Quantifizierung des Farbsinns bei Störungen der Zapfenfunktion - Huchzermeyer, Cord; Fars, Julien; Stöhr, Heidi; Kremers, Jan (Ophthalmologe, 2020)
Background: Inherited retinal diseases with cone dysfunction can be accompanied by severe visual loss and a marked loss of color vision despite relatively normal fundus appearance. Autosomal dominant occult macular dystrophy (RP1L1 gene) and X‑chromosomal retinitis pigmentosa (RPGR gene, including heterozygous female carriers) are important examples. New examination techniques enable quantification of the extent of color vision disturbances. Methods: After a thorough clinical examination, color discrimination and cone function were quantified. The Cambridge color test is a computer-based test that generates pseudo-isochromatic plates with Landolt C figures for quantifying color discrimination along several axes in color space. Examination of photorecepor-specific temporal contrast sensitivity is performed by subtle cyclic modulation of the spectral composition of a light stimulus. Molecular diagnostics were carried out by next generation sequencing (NGS)-based targeted gene panel analysis and Sanger sequencing. Results: Markedly reduced color discrimination as well as reduced photoreceptor-specific temporal contrast sensitivity could be demonstrated in two patients with occult macular dystrophy and two heterozygous female carriers of RPGR mutations. Conclusion: The demonstration of dyschromatopsia is very helpful in the diagnosis of inherited retinal diseases, in addition to modern imaging techniques, such as optical coherence tomography (OCT) and fundus fluorescence. New functional techniques enable quantification of color vision disturbances and could be useful as outcome parameters in clinical trials of new gene and stem cell-based therapies.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Color vision; Cone dystrophy; Contrast sensitivity; Photoreceptors; Retinitis pigmentosa

New developments in non-invasive visual electrophysiology. - Parry, Neil. R. A.; Mckeefry, Declan J.; Murray, Ian J.; Kremers, Jan (Vision research, 2020)
EVALuna2:419179

Novel truncating mutation in CACNA1F in a young male patient diagnosed with optic atrophy - Pasutto, Francesca; Ekici, Arif Bülent; Reis, André; Kremers, Jan; Huchzermeyer, Cord (Ophthalmic Genetics, 2018)
BACKGROUND: Low vision in children can be accompanied by pallor of the optic disc with little or no characteristic morphologic changes of the retina. A variety of diseases can be the underlying cause, including hereditary optic atrophy, Leber's congenital amaurosis (LCA), achromatopsia, and calcium channel, voltage-dependent, L-type, alpha-1F subunit gene (CACNA1F)-associated retinopathy (most widely known as incomplete congenital stationary night blindness: iCSNB). Differentiation at early age is desirable due to large differences in prognosis, but may be difficult because phenotypes overlap and electrophysiological testing is challenging in young patients. We present the case of a 6-year-old boy with unexplained low vision and pallor of the optic disc who originally had been diagnosed with hereditary optic atrophy in the absence of recordable full-field electroretinography (ERG) due to poor patient cooperation. MATERIALS AND METHODS: Standard Sanger sequencing excluded mutations in the OPA1 gene (autosomal-dominant optic atrophy). To identify the underlying genetic cause, whole-exome sequencing was performed on patient's DNA. Recording of the full-field ERG was successfully performed 6 months later. RESULTS: We identified a novel truncating mutation in CACNA1F gene (NM_001256789: c.3895C > T in exon 33) which led to the correct diagnosis of CACNA1F-associated retinopathy in the young boy. ERG recordings showed a negative scotopic mixed response with preserved oscillatory potentials and a flicker ERG with reduced amplitude and biphasic waveform, compatible with a CACNA1F-asssociated phenotype. CONCLUSIONS: We show that genetic testing may help to differentiate between optic atrophy, LCA, and CACNA1F-associated retinopathy at a much earlier age, in absence of electrophysiological examination and by widely overlapping phenotypes.
EVALuna2:34838

Objective detection of visual field defects with multifrequency VEPs - Crux, Katja; Huchzermeyer, Cord; Kremers, Jan; Horn, Folkert (Documenta Ophthalmologica, 2023)
Purpose: To correlate multifrequency pattern reversal VEPs in quadrants (QmfrVEPs) with perimetric field losses for objective detection of visual field losses. Methods: QmfrVEP measurements were performed using four LED-based checkerboard stimulators to stimulate the four quadrants of the visual field. QmfrVEPs were measured monocularly in 5 normal subjects and in 5 glaucoma patients who showed losses in conventional Octopus perimetry. The pattern reversal frequency varied slightly between the stimulators: (11.92, 12.00, 12.08 and 12.16 reversals/sec). The responses to the different stimuli were identified by discrete Fourier analysis. VEPs were recorded using different electrode configurations, and the recording with the highest signal-to-noise ratio (SNR) was used for further analysis. Results: QmfrVEP responses from the different quadrants can be reliably measured and separated using the 0.08 reversals/sec interstimulus reversal frequency differences. The signal-to-noise ratio in the four quadrants was significantly correlated with the equivalent visual field losses obtained with perimetry (Spearman rank correlation: P < 0.001). In the five glaucoma patients, the SNR was reduced in 15 out of the 16 quadrants with a perimetric defect, in comparison to the results in quadrants of healthy subjects. This confirms the sensitivity of the procedure. Conclusion: QmfrVEP responses can be measured reliably. This pilot study suggests that high SNR values exclude visual field defects and that focal defects can be identified in glaucoma patients. Trial registration: www.clinicaltrials.gov . NCT00494923.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Objective visual field test; Pattern reversal; Quadrant multifrequency VEP; Signal-to-noise ratio; Steady state

Objective perimetry using a four-channel multifocal VEP system: correlation with conventional perimetry and thickness of the retinal nerve fibre layer - Horn, Folkert; Kaltwasser, Christoph; Jünemann, Anselm; Kremers, Jan; Tornow, Ralf-Peter (British Journal of Ophthalmology, 2012)
There is evidence that multifocal visual evoked potentials (VEPs) can be used as an objective tool to detect visual field loss. The aim of this study was to correlate multifocal VEP amplitudes with standard perimetry data and retinal nerve fibre layer (RNFL) thickness.Multifocal VEP recordings were performed with a four-channel electrode array using 58 stimulus fields (pattern reversal dartboard). For each field, the recording from the channel with maximal signal-to-noise ratio (SNR) was retained, resulting in an SNR optimised virtual recording. Correlation with RNFL thickness, measured with spectral domain optical coherence tomography and with standard perimetry, was performed for nerve fibre bundle related areas.The mean amplitudes in nerve fibre related areas were smaller in glaucoma patients than in normal subjects. The differences between both groups were most significant in mid-peripheral areas. Amplitudes in these areas were significantly correlated with corresponding RNFL thickness (Spearman R=0.76) and with standard perimetry (R=0.71).The multifocal VEP amplitude was correlated with perimetric visual field data and the RNFL thickness of the corresponding regions. This method of SNR optimisation is useful for extracting data from recordings and may be appropriate for objective assessment of visual function at different locations.This study has been registered at http://www.clinicaltrials.gov (NCT00494923).
EVALuna2:21033

Objective visual field determination in forensic ophthalmology with an optimized 4-channel multifocal VEP perimetry system: a case report of a patient with retinitis pigmentosa - Kaltwasser, C.; Horn, Folkert; Kremers, Jan; Jünemann, Anselm; Bergua, A. (Documenta Ophthalmologica, 2011)
We present the case of a 59-year-old male patient with progressive vision impairment and consecutive visual field narrowing ("tunnel view") for 7 years and a known retinitis pigmentosa for 5 years. The remaining Goldmann perimetric visual field at time reported was less than 5°. A request for blindness-related social benefits was rejected because an ophthalmologic expert assessment suggested malingering. This prompted us to assess an objective determination of the visual field using multifocal VEPs. Objective visual field recordings were performed with a four-channel multifocal VEP-perimeter using 58 stimulus fields (pattern reversal dartboard stimulus configuration). The correlated signal data were processed using an off-line method. At each field, the recording from the channel with the maximal signal-to-noise ratio (SNR) was retained, thus resulting in an SNR optimized virtual recording. Analysis of VEP signals was performed for each single field and concentric rings and compared to an average response measured in five healthy subjects. Substantial VEP responses could be identified in three fields within the innermost ring (eccentricity, 1.7°) for both eyes, although SNR was generally low. More eccentric stimuli did not elicit reliable VEP responses. The mfVEP recording was correlated with perimetric visual field data. The current SNR optimization by using the channel with the largest SNR provides a good method to extract useful data from recordings and may be appropriate for the use in forensic ophthalmology.
EVALuna2:21039

ON and OFF electroretinography and contrast sensitivity in Duchenne muscular dystrophy - Salgueiro Barboni, Mirella Telles; Nagy, Balazs Vince; De Araujo Moura, Ana Laura; Damico, Francisco Max; Da Costa, Marcelo Fernandes; Kremers, Jan; Ventura, Dora Fix (Investigative Ophthalmology & Visual Science, 2013)
The study investigated possible asymmetric dysfunction of the ON and OFF visual mechanisms in DMD (Duchenne muscular dystrophy) patients associated with specific genetic alterations. Methods: nineteen DMD patients and 7 heterozygous dmd carriers were tested, as well as 19 age-matched controls.Full-field ergs were recorded using mesopic (1 cd/m(2)) and photopic (250 cd/m(2)) sawtooth luminance modulations as stimuli: rapid increase and ramping decrease (to isolate ON responses) or rapid decrease and ramping increase (for OFF responses). In addition, a psychophysical study comprised contrast sensitivity tests using two checkerboard stimuli at either higher (ON) or lower (OFF) luminance relative to the background: 0.3 cycles per degree (cpd) presented for 33 ms (low spatial frequency, short duration) and 2 cpd presented for 1500 ms (high spatial frequency, long duration).A significant ERG amplitude reduction, relative to controls, was detected in the DMD patients in the mesopic positive peaks for both ON and OFF stimuli, as well as for the photopic ON stimulus (P < 0.05). Contrast sensitivity was significantly lower in the DMD patients (P < 0.05) relative to controls for the ON stimuli. Neither the ERG nor the contrast sensitivities were altered in the carriers.This study suggests that there are ON and OFF ERG alterations when both rods and cones contribute to the ERG responses in DMD patients. When only cones are activated there is an asymmetrical ERG alteration, also revealed by the contrast sensitivity measurements.
EVALuna2:21134
Keywords: Electroretinogram; ON OFF pathways; Contrast sensitivity; Dystrophin; Retina

On- and off-response ERGs elicited by sawtooth stimuli in normal subjects and glaucoma patients - Pangeni, Gobinda; Lämmer, Robert; Tornow, Ralf-Peter; Horn, Folkert; Kremers, Jan (Documenta Ophthalmologica, 2012)
The aim of this study is to measure the on- and off-responses and their response asymmetries elicited by sawtooth stimuli in normal subjects and glaucoma patients. Furthermore, the correlation between the ERGs and other functional and structural parameters are investigated. Full-field stimuli were produced using a Ganzfeld bowl with Light Emitting Diodes (LEDs) as light sources. On- and off-response ERGs were recorded from 17 healthy subjects, 12 pre-perimetric and 15 perimetric glaucoma patients using 4-Hz luminance rapid-on and rapid-off sawtooth stimuli (white light; mean luminance 55 cd/m(2)) at 100% contrast. The on- and off-responses were added to study response asymmetries. In addition, flash ERGs were elicited by red stimuli (200 cd/m(2)) on a blue background (10 cd/m(2)). The mean deviations (MD) of the visual field defects were obtained by standard automated perimetry. The retinal nerve fibre layer thickness (RNFLT) was measured with Spectral Domain Optical Coherence Tomography (SOCT). We studied the correlation between ERG response amplitudes, visual field mean deviation (MDs) and RNFLT values. The on-responses showed an initial negative (N-on) followed by a positive (P-on), a late positive (LP-on) and a late negative responses (LN-on). The off-responses showed an initial positive (P-off) a late positive (LP-off) and a late negative response (LN-off). The addition of on- and off-responses revealed an initial positive (P-add) and a late negative response (LN-add). The on-response components (N-on, P-on and LN-on) in the glaucoma patients were relatively similar to those of the control subjects. However, the LP-on was significantly elevated (p = 0.03) in perimetric patients. The LP-off was significantly elevated (p < 0.001), and the amplitude of LN-off was significantly reduced in perimetric patients (p = 0.02). The LN-add amplitude was significantly reduced (p < 0.001) and delayed (p = 0.03) in perimetric patients. The amplitudes of the LN-off and LN-add ERG components were significantly correlated with the PhNR in the flash ERG (LN-off: p = 0.01; LN-add: p < 0.001) and with RNFLT (LN-off: p = 0.006; LN-add: p = 0.001). On- and off-response ERGs and their response asymmetries, elicited by sawtooth stimuli, are altered in the glaucoma patients. The late components are affected. Changes in the late negative components are correlated with structural and other functional changes.
EVALuna2:21076
Keywords: Electroretinogram; On- and off-responses; Glaucoma; Sawtooth stimuli

On and off responses of the photopic fullfield ERG in normal subjects and glaucoma patients - Horn, Folkert; Gottschalk, Kristina; Mardin, Christian Y.; Pangeni, Gobinda; Jünemann, Anselm; Kremers, Jan (Documenta Ophthalmologica, 2011)
Recent studies suggest a diagnostic value of the photopic negative response (PhNR) with a long-duration stimulus. The aim of this study was to record the on and off responses of the photopic fullfield electroretinogram (ERG) in normal subjects and glaucoma patients. We focused on different waves of the responses after onset and offset of the long-duration stimulus ERG. Photopic fullfield ERGs were recorded in response to a white bright LED flash on a white 20 cd/m(2) background. Stimulus luminances were 40, 60 and 80 cd/m(2). Responses were averaged using a flash duration of 240 ms and an offset period of 500 ms. We examined 19 healthy subjects, 27 patients with glaucomatous optic disc atrophy and 7 ocular hypertensive patients. The amplitudes and implicit times of the on and off responses of the human ERG depended on flash luminance. Comparing patients with glaucoma and healthy subjects for the 60 cd/m² flash, there was a significant change in the PhNRs (at onset: P < 0.01, at offset: P < 0.001) of the d-wave and of the i-wave at offset (P < 0.01). No significant difference was found for peak times of the fullfield ERG and for a- and b-wave amplitudes. PhNR amplitudes were significantly correlated with mean thickness of retinal nerve fibre layer as measured with OCT. In comparison with the normal photopic long-flash ERG, glaucoma patients showed changes in the PhNR amplitude following stimulus onset and in waves following stimulus offset.
EVALuna2:20998
Keywords: Electroretinogram; Glaucoma; Onset/offset fullfield ERG; Photopic negative response

Paradoxical pupil responses to isolated M-cone increments - Murray, Ian J.; Kremers, Jan; Mckeefry, Declan; Parry, Neil R. A. (Journal of the Optical Society of America A-Optics Image Science and Vision, 2018)
M-cone onsets appear dimmer than the background and elicit electroretinograms (ERGs) resembling the light offset response. We sought a corresponding anomalous pupillary light reflex (PLR) using a 4-primary ganzfeld as stimulator and pupillometer. Increments and decrements of white light were compared with M- and L-cone onsets and offsets using silent substitution. Luminance bias (LB) could be added to or subtracted from the cone-isolating stimuli. There was a normal PLR to L-cone increments, but the pupil constricted mainly to M-cone decrements. Changing LB produced a neutral point where on and off responses were balanced. The results reflect ERG and psychophysical studies. This observation may be linked to the antagonistic nature of the M-cone input to cone opponent mechanisms.
EVALuna2:34924

Pathway-specific light adaptation in human electroretinograms - Brasil, Alódia; Tsai, Tina I.; da Silva Souza, Givago; Herculano, Anderson Manoel; Ventura, Dora Fix; de Lima Silveira, Luiz Carlos; Kremers, Jan (Journal of Vision, 2019)
The cellular origins of slow ERG changes during light adaptation following a dark-adapted state are still unclear. To study light adaptation, six healthy, normal trichromats were dark-adapted for 30 min prior to full-field ERG recordings to sinusoidal stimuli that isolate responses of the L- or M-cones or that stimulate luminance and chromatic mechanisms at 12 or 36 Hz. Recordings were performed for 16 min with 2-min intervals after onset of a constant background. Generally, the responses were sine-wave-like, and the first harmonic (fundamental) component dominated the Fourier spectrum except for the 12-Hz luminance stimulus in which two components, a sine-wave-like component and a transient component, determined the response profiles, leading to large second harmonic components. The amplitude of the first harmonic component (F) increased as a function of the light-adaptation time except for the 12-Hz luminance stimulus at which the F component decreased as a function of the light-adaptation period. The phase of the first harmonic component changed only slightly (less than 30°) during the light-adaptation period for all stimuli conditions. The L/M ratio in luminance reflecting ERGs decreased with increasing adaptation time. Our present data suggest that the light-adaptation process mainly reflects changes in the luminance pathway. The responses to 12-Hz luminance stimuli are determined by two different luminance driven pathways with different adaptation characteristics.
CRIS-Team Scopus Importer:2019-05-02

Pattern electroretinogram, blue-yellow visual evoked potentials and the risk of developing visual field defects in glaucoma suspects: a longitudinal “survival” analysis with a very long follow-up - Huchzermeyer, Cord; Lämmer, Robert; Mardin, Christian Y.; Kruse, Friedrich; Kremers, Jan; Horn, Folkert (Graefes Archive For Clinical and Experimental Ophthalmology, 2024)
Purpose: Estimating glaucoma suspects’ risk for visual field defects helps to avoid under- and over-treatment. In this retrospective, longitudinal cohort study with a very long follow-up, we studied whether pattern electroretinograms (PERG) amplitudes and blue-on-yellow visual evoked potential (BY-VEP) latencies can predict visual field defects. Methods: Participants of the Erlangen Glaucoma Study were examined with PERG and BY-VEP between 9/1991 and 8/2001. Stimuli were created using an optical bench with Maxwellian view and consisted of vertical gratings (0,88 cpd) in a 32° field for both PERG and BY-VEP. Patients were treated according to clinical standards and performed standard automated perimetry (SAP) annually. Retrospectively, patients with normal SAP at baseline were selected. Primary endpoint was conversion to perimetric glaucoma. Predictive value was modeled using Kaplan–Meier analyses and a multivariate cox proportional hazards model with the continuous variables PERG amplitude, BY-VEP peak time and SAP square-root of loss variance (sLV) after stratification for Jonas classification of the optic discs. Results: Of 412 patients (288: Jonas 0, 103: I, and 21: II; baseline age: 20–60 years), 65 converted to perimetric glaucoma during follow-up (0.5–23.3 years; median 5.5 years). Optic disc classification was a strong risk factor for conversion (log rank p < 0.0001), and patients with more advanced changes progressed earlier. In the multivariate analysis (log rank p = 0.005), only PERG amplitude remained an independent risk factor after stratification for optic disc morphology (p = 0.021), with a 30% higher risk per μV amplitude decrease. Conclusions: PERG helps to estimate glaucoma suspects’ risk for visual field defects.
CRIS-Team Scopus Importer:2024-01-12
Keywords: Electroretinogram; Glaucoma; Perimetry; Survival analysis; Visually evoked potentials

Pattern electroretinograms during the cold pressor test in normals and glaucoma patients - La Mancusa, Antonia; Horn, Folkert; Kremers, Jan; Huchzermeyer, Cord; Rudolph, Michael; Jünemann, Anselm (Investigative Ophthalmology & Visual Science, 2014)
To examine the influence of the cold pressor test (CPT) on steady-state pattern electroretinograms (PERG) in healthy subjects and glaucoma patients.Steady-state PERGs to 7.8 Hz pattern reversal stimuli were recorded in 63 subjects. Fifteen healthy control subjects, 14 patients with ocular hypertension (OHT), and 34 patients with open-angle glaucoma (20 normotensive [NTG] and 14 high tension glaucoma [HTG]) were examined. Steady-state PERG amplitudes and latencies were analyzed at baseline, during cold stimulus using a modified CPT, and during the subsequent recovery phase. Blood pressure and heart rate were simultaneously recorded in 10 normals and 11 glaucoma patients.During the three test conditions (baseline, ice water, and warm water) glaucoma patients (NTG and HTG) showed significantly reduced PERG amplitudes in comparison with control subjects (P < 0.001) and with OHT patients (P < 0.004). Patients with OHT displayed lower PERG amplitudes than control subjects (nonsignificant, with consideration of Bonferroni). Only NTG patients showed a significant effect of the CPT on PERG amplitude (significant decrease during warm water P = 0.02). Latencies shortened significantly during warm-water period after cold stimulus in control subjects (P = 0.05) and in NTG patients (P = 0.02) with a nonsignificant trend of shortened latencies in the OHT (P = 0.06) and HTG groups (P = 0.3). Systolic and diastolic blood pressure increased during cold water (P < 0.001) and decreased during warming-up conditions (P < 0.001).This study shows that a CPT influences the PERG responses particularly in NTG. (ClinicalTrials.gov number, NCT00494923.).
EVALuna2:21162

Patterns of photoreceptor-specific temporal contrast sensitivity losses in patients with different phenotypic variants of retinitis pigmentosa - Huchzermeyer, Cord; Fars, Julien; Lorenz, Birgit; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2020)
CRIS-Team WoS Importer:2020-09-11

Perifoveal cone- And rod-mediated temporal contrast sensitivities in stargardt disease/fundus flavimaculatus - Fars, Julien; Pasutto, Francesca; Kremers, Jan; Huchzermeyer, Cord (Investigative Ophthalmology & Visual Science, 2021)
PURPOSE. The purpose of this study was to compare L-cone–driven, S-cone–driven, and rod-driven temporal contrast sensitivities (tCSs) in patients with Stargardt disease 1/fundus flavimaculatus (STGD1/FF). METHODS. Fourteen patients (eight male, six female; mean age, 43.21 ± 13.18 years) with genetically confirmed STGD1/FF participated in this study. A dedicated light-emitting diode stimulator was used to measure perifoveal tCSs in an annular test field (1°–6° of visual eccentricity) at temporal frequencies between 1 and 20 Hz. Photoreceptor classes were isolated with the triple silent substitution technique. To compare functional damage among photoreceptor classes, sensitivity deviations (decibels) were calculated based on age-related normal values and then averaged across those frequencies where perception is mediated by the same post-receptoral pathway (L-cone red–green opponent pathway: 1, 2, 4 Hz; luminance pathway: 12, 16, 20 Hz; S-cone pathway: 1, 2, 4 Hz; fast rod pathway: 8, 10, 12 Hz). Sensitivity deviations were compared with infrared scanning laser ophthalmoscopy (IR-SLO) and standard automated perimetry (SAP). RESULTS. Photoreceptor-driven tCSs were generally lower in patients with STGD1/FF than in normal subjects but were without systematic differences among photoreceptors. Although sensitivity deviations were significantly correlated between each other, only luminance-driven L-cone sensitivity deviations were significantly correlated with the IR-SLO area of hyporeflectance (AoH) and SAP central mean deviation within 6° eccentricity (MD6deg). CONCLUSIONS. No systematic differences between photoreceptor classes were detected; however, our data suggest that temporal contrasts detected by the luminance pathway were closely correlated with other clinical parameters (AoH and MD6deg) and might be most useful as functional biomarkers in clinical trials.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Fundus flavimaculatus; Perifovea; Photoreceptors; Stargardt disease; Temporal contrast sensitivity

Perifoveal L- and M-cone-driven temporal contrast sensitivities at different retinal illuminances - Huchzermeyer, Cord; Kremers, Jan (Journal of the Optical Society of America A-Optics Image Science and Vision, 2016)
We established a protocol using a well-established LED stimulator to measure temporal contrast sensitivities driven by sine-wave modulation of L- and M-cones in the perifovea using triple silent substitution. The stimulus was presented in an annular field (2° inner diameter, 13° outer diameter). We validated this technique by studying the contrast sensitivity of three color normal observers at 10 different temporal frequencies (between 1 and 28 Hz) over a large range of retinal illuminances (between 0.07 and 587 phot Td), spanning the complete mesopic range. In one subject, sensitivities to counterphase modulation of L- and M-cones and in-phase modulation of L, M, and S-cones were additionally measured, which putatively reflected the parvo- and magnocellular retinogeniculate pathways, respectively. Furthermore, we performed measurements of temporal contrast sensitivities as a function of frequency at 294 phot Td in two protanopes, in two deuteranopes, and in one subject with S-cone monochromacy. Quality of isolation was satisfactory and we were able to reproduce known physiological patterns of temporal vision, such as the typical temporal contrast sensitivity functions of the L- and M-cone, the parvo- and magnocellular retinogeniculate pathways, as well as the light adaptation curves. These results will help determine optimal stimulus conditions in future studies. Results from the dichromats and the S-cone monochromat also support the quality of isolation of our protocol and underpin its potential clinical value.
EVALuna2:21317

Perifoveal S-cone and rod-driven temporal contrast sensitivities at different retinal illuminances - Huchzermeyer, Cord; Kremers, Jan (Journal of the Optical Society of America A-Optics Image Science and Vision, 2017)
We evaluated a technique for measuring temporal contrast sensitivities to sine-wave modulation driven by S-cones and rods in the perifovea using triple silent substitution. Isolating stimuli for S-cones and rods were created using an eight-channel, four-primary LED stimulator that has been validated before. Sensitivities were measured at 10 different temporal frequencies between 1 and 28 Hz in three normal observers at 14 different retinal illuminances between 0.07 and 587 photopic troland (phot Td) and at three different retinal illuminances over the same range in one S-cone monochromat. The technique was further validated by measuring bleaching adaptation in two normal subjects, demonstrating sufficient isolation in rods. Good isolation was apparent from the differences in the temporal contrast sensitivity functions and the sensitivity-versus-retinal illuminance functions between S-cones and rods, and also from the results in the S-cone monochromats and the delayed recovery of rod sensitivities after bleaching. The results will help to determine optimal stimulus conditions in future studies. The results in the S-cone monochromat demonstrate the potential clinical value of our protocol.
EVALuna2:21334

Perimetric measurements with flicker-defined form stimulation in comparison with conventional perimetry and retinal nerve fiber measurements - Horn, Folkert; Tornow, Ralf-Peter; Jünemann, Anselm; Lämmer, Robert; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2014)
We compared the results of flicker-defined form (FDF) perimetry with standard automated perimetry (SAP) and retinal nerve fiber layer (RNFL) thickness measurements using spectral domain optical coherence tomography (OCT).A total of 64 healthy subjects, 45 ocular hypertensive patients, and 97 "early" open-angle glaucoma (OAG) patients participated in this study. Definition of glaucoma was based exclusively on glaucomatous optic disc appearance. All subjects underwent FDF perimetry, SAP, and peripapillary measurements of the RNFL thickness. The FDF perimetry and SAP were performed at identical test locations (G1 protocol). Exclusion criteria were subjects younger than 34 years, SAP mean defect (SAP MD) > 5 dB, eye diseases other than glaucoma, or nonreliable FDF measurements. The correlations between the perimetric data on one hand and RNFL thicknesses on the other hand were analyzed statistically.The age-corrected sensitivity values and the local results from the controls were used to determine FDF mean defect (FDF MD). The FDF perimetry and SAP showed high concordance in this cohort of experienced patients (MD values, R = -0.69, P < 0.001). Of a total of 42 OAG patients with abnormal SAP MD, 38 also displayed abnormal FDF MD. However, FDF MD was abnormal in 28 of 55 OAG patients with normal SAP MD. The FDF MD was significantly (R = -0.61, P < 0.001) correlated with RNFL thickness with a (nonsignificantly) larger correlation coefficient than conventional SAP MD (R = -0.48, P < 0.001).The FDF perimetry is able to uncover functional changes concurrent with the changes in RNFL thickness. The FDF perimetry may be an efficient functional test to detect early glaucomatous nerve atrophy. (ClinicalTrials.gov number, NCT00494923.).
EVALuna2:21150

Phase Changes in the Chromaticity and Luminance Driven Flicker Electroretinograms (ERGs) of Glaucoma Patients - Barboni, M. T.; Pangeni, G.; Ventura, D. F.; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2010)
Keywords: electroretinography: clinical; retina; color vision

Photoreceptor degeneration in two mouse models for congenital stationary night blindness type 2 - Regus-Leidig, Hanna; Atorf, Jenny; Feigenspan, Andreas; Kremers, Jan; Maw, Marion A.; Brandstätter, Johann Helmut (PLoS ONE, 2014)
Light-dependent conductance changes of voltage-gated Cav1.4 channels regulate neurotransmitter release at photoreceptor ribbon synapses. Mutations in the human CACNA1F gene encoding the ?1F subunit of Cav1.4 channels cause an incomplete form of X-linked congenital stationary night blindness (CSNB2). Many CACNA1F mutations are loss-of-function mutations resulting in non-functional Cav1.4 channels, but some mutations alter the channels' gating properties and, presumably, disturb Ca(2+) influx at photoreceptor ribbon synapses. Notably, a CACNA1F mutation (I745T) was identified in a family with an uncommonly severe CSNB2-like phenotype, and, when expressed in a heterologous system, the mutation was shown to shift the voltage-dependence of channel activation, representing a gain-of-function. To gain insight into the pathomechanism that could explain the severity of this disorder, we generated a mouse model with the corresponding mutation in the murine Cacna1f gene (I756T) and compared it with a mouse model carrying a loss-of-function mutation (?Ex14-17) in a longitudinal study up to eight months of age. In ?Ex14-17 mutants, the b-wave in the electroretinogram was absent, photoreceptor ribbon synapses were abnormal, and Ca(2+) responses to depolarization of photoreceptor terminals were undetectable. In contrast, I756T mutants had a reduced scotopic b-wave, some intact rod ribbon synapses, and a strong, though abnormal, Ca(2+) response to depolarization. Both mutants showed a progressive photoreceptor loss, but degeneration was more severe and significantly enhanced in the I756T mutants compared to the ?Ex14-17 mutants.
EVALuna2:21185

Photoreceptor driven non-invasive electrophysiology in humans and mice - Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-11-01

Photoreceptor-specific light adaptation of critical flicker frequency in trichromat and dichromat observers - Huchzermeyer, Cord; Martins, Cristiane M. G.; Nagy, Balazs; Barboni, Mirella T. S.; Ventura, Dora F.; Costa, Marcelo F.; Kremers, Jan (Journal of the Optical Society of America A-Optics Image Science and Vision, 2018)
The silent substitution paradigm offers possibilities to investigate and compare the temporal properties of mechanisms driven by single photoreceptor types, including the critical flicker frequency (CFF), in which the state of adaptation can be kept as invariant. We have (1) measured CFFs using triple silent substitutions to isolate L-, M-, and S-cone as well as rod-driven pathways under identical mean luminances and chromaticities; (2) repeated the CFF measurements at different mean luminances in order to validate the Ferry-Porter law (stating that the relationship between CFF and the log retinal illuminance-log I-is linear); and (3) compared these CFF versus log I functions for L-, M-, S-cone-, and rod-isolating stimuli for five trichromats and four X-linked dichromats (two protanopes, two deuteranopes). We show that the effects of luminance on the CFFs with silent substitution are comparable to those measured previously with chromatic stimuli. We found that M-cone-driven CFFs are smaller in trichromats than in protanopes. Furthermore, the slopes of the M-cone-driven CFF versus log I functions are smaller in trichromats. Possibly, the lacking L-cones are replaced by M-cones in these two protanopes and the CFF depends on cone density. Furthermore, we found that in trichromats, the slopes of the CFF-log I functions are smaller for M-cone-than for L-cone-isolating stimuli. This contradicts the current interpretation of the CFF-log I functions for chromatic stimuli, which states that CFF is mediated by the most strongly modulated photoreceptor type. Thus, the larger slopes that were previously found with medium-wavelength chromatic stimuli compared with long-wavelength chromatic stimuli seem to be the result of an addition of signals from different photoreceptors and do not necessarily result from M-cones being inherently faster. (C) 2018 Optical Society of America

Photoreceptor-specific loss of perifoveal temporal contrassensitivity in retinitis pigmentosa - Huchzermeyer, Cord; Fars, Julien; Kremers, Jan (Translational Vision Science & Technology, 2020)
Purpose: Inherited retinal diseases affect the L-, M-, S-cones and rods in distinct ways, which calls for new methods that enable quantification of photoreceptor-specific functions. We tested the feasibility of using the silent substitution paradigm to estimate photoreceptor-driven temporal contrast sensitivity (tCS) functions in patients with retinitis pigmentosa. Methods: The silent substitution paradigm is based on substitution of lights of different spectral composition; this offers considerable advantage over other stimulation techniques. We used a four-primary LED stimulator to create perifoveal annular stimuli (2° inner, 12° outer diameters) and used a triple silent substitution to probe photoreceptor-selective tCS. Measurements were performed in a heterogeneous cohort of 15 patients with retinitis pigmentosa and related to those in a control group of nine color-normal healthy observers. Age differences between groups were addressed with a model of age-related normal contrast sensitivity derived from measurements in 20 healthy observers aged between 23 and 83 years. Results: The age-related loss of tCS amounted to 0.1 dB/year in healthy subjects across all photoreceptor subtypes. In patients, tCS was decreased for every photoreceptor subtype; however, S-cone-and rod-driven sensitivities were most strongly affected. Postreceptoral mechanisms were not affected. Conclusions: This feasibility study provides evidence that the silent substitution technique enables the estimation of photoreceptor-selective tCS functions and can serve as an accurate biomarker of photoreceptor-specific contrast sensitivity loss in patients with retinitis pigmentosa. Translational Relevance: We aim to develop tests of visual function for clinical trials of novel therapies for inherited retinal diseases from methods that can currently be used only in vision research labs.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Contrast sensitivity; Photoreceptors; Retinal dystrophy; Retinitis pigmentosa; Temporal vision

Photoreceptor-Specific Temporal Contrast Sensitivities in RP1L1-Associated Occult Macular Dystrophy - Huchzermeyer, Cord; Fars, Julien; Kremers, Jan; Kühlewein, Laura; Kempf, Melanie; Ott, Saskia; Stingl, Krunoslav; Stingl, Katarina (Investigative Ophthalmology & Visual Science, 2023)
Purpose: The purpose of this study was to compare L-, M-, S-cone-, and rod-driven temporal contrast sensitivities (tCS) in patients with RP1L1-associated autosomal-dominant occult macular dystrophy (OMD), and to investigate how photoreceptor degeneration determines which post-receptoral channels dominate perception. Methods: Photoreceptor isolating stimuli were created with the silent substitution technique. Photoreceptor-selective tCS deviations (D L-cone/M-cone/S-cone/Rod) were obtained as a function of temporal frequency with identical retinal adaptation, by subtracting tCS from age-corrected normal values. A linear-mixed effects model was used for analysis. Results: Eleven genetically confirmed patients were included (7 women, 5 men; age = 52.27 ± 14.44 years). Overall, L- and M-cone-driven sensitivity deviations (DL-cone and DM-cone) were more negative than DS-cone; DRod was normal at frequencies between 8 and 12 Hz in all subjects. Rod-driven tCS functions allowed identification of two subgroups of patients: one with band-pass properties and one with low-pass properties, suggesting dominance of different post-receptoral filters. The same filtering properties were observed in L-cone-driven tCS functions. Furthermore, the two subgroups also differed in clinical parameters (spherical equivalent, BCVA, perimetry, and ocular coherence tomography (OCT) reflectivity of the ellipsoid zone relative to the RPE). Conclusions: OMD was characterized predominantly by deterioration of L- and M-cone-cone driven function in the perifovea. Rod-driven functions were normal. Differences in the photoreceptor signals were further modified by postreceptoral filters.
CRIS-Team Scopus Importer:2023-07-07

Pre-stimulus bioelectrical activity in light-adapted ERG under blue versus white background - Tsay, Katherine; Safari, Sara; Abu-Samra, Abdullah; Kremers, Jan; Tzekov, Radouil (Visual Neuroscience, 2023)
To compare the baseline signal between two conditions used to generate the photopic negative response (PhNR) of the full-field electroretinogram (ERG): red flash on a blue background (RoB) and white flash on a white background (LA3). The secondary purpose is to identify how the level of pre-stimulus signal affects obtaining an unambiguous PhNR component. A retrospective chart review was conducted on four cohorts of patients undergoing routine ERG testing. In each group, LA3 was recorded the same way while RoB was generated differently using various luminances of red and blue light. The background bioelectrical activity 30 ms before the flash was extracted, and the root mean square (RMS) of the signal was calculated and compared between RoB and LA3 using Wilcoxon test. Pre-stimulus noise was significantly higher under RoB stimulation versus LA3 in all four conditions for both right and left eyes (ratio RoB/LA3 RMS 1.70 and 1.57 respectively, p < 0.033). There was also no significant difference between the RMS of either LA3 or RoB across protocols, indicating that the baseline noise across cohorts were comparable. Additionally, pre-stimulus noise was higher in signals where PhNR was not clearly identifiable as an ERG component versus signals with the presence of unambiguous PhNR component under RoB in all four groups for both eyes (p < 0.05), whereas the difference under LA3 was less pronounced. Our study suggests that LA3 produces less background bioelectrical activity, likely due to decreased facial muscle activity. As it seems that the pre-stimulus signal level affects PhNR recordability, LA3 may also produce a better-quality signal compared to RoB. Therefore, until conditions for a comparable bioelectrical activity under RoB are established, we believe that LA3 should be considered at least as a supplementary method to evaluate retinal ganglion cell function by ERG.
CRIS-Team Scopus Importer:2023-12-22
Keywords: electroretinography; ERG; eye; PhNR; photopic negative response; retina

Pseudorandom full-field electroretinograms reflect different light adaptation mechanisms - Assis, Juliana Bizerra; Brasil, Alódia; Loureiro, Terezinha Medeiros Gonçalves; da Silva, Veronica Gabriela Ribeiro; Herculano, Anderson Manoel; Ventura, Dora Fix; Silveira, Luiz Carlos Lima; Kremers, Jan; Souza, Givago Silva (Documenta Ophthalmologica, 2021)
Purpose: To investigate the magnitude and time course of pseudorandom ffERG during light adaptation. Methods: Ten healthy subjects (26 ± 10.1 years) underwent 20 min of dark adaptation, and then the ffERG was evoked by pseudorandom flash sequences (4 ms per flash, 3 cd.s/m2) driven by m-sequences (210–1 stimulus steps) using Veris Science software and a Ganzfeld dome over a constant field of light adaptation (30 cd/m2). The base period of the m-sequence was 50 ms. Each stimulation sequence lasting 40 s was repeated at 0, 5, 10, 15 and 20 min of light adaptation. Relative amplitude and latency (corrected by values found at 0 min) of the three components (N1, P1, and N2) of first-order (K1) and first slice of the second-order (K2.1) kernel at 5 time points were evaluated. An exponential model was fitted to the mean amplitude and latency data as a function of the light adaptation duration to estimate the time course (τ) of the light adaptation for each component. Repeated one-way ANOVA followed by Tukey post-test was applied to the amplitude and latency data, considering significant values of p < 0.05. Results: Regarding the K1 ffERG, N1 K1, P1 K1, and N2 K1 presented an amplitude increase as a function of the light adaptation (N1 K1τ value = 2.66 min ± 4.2; P1 K1τ value = 2.69 min ± 2.10; and N2 K1 τ value = 3.49 min ± 2.96). P1 K1 and N2 K1 implicit time changed as a function of the light adaptation duration (P1 K1τ value = 3.61 min ± 5.2; N2 K1τ value = 3.25 min ± 4.8). N1 K1 had small implicit time changes during the light adaptation. All the K2,1 components also had nonsignificant changes in amplitude and implicit time during the light adaptation. Conclusions: Pseudorandom ffERGs showed different mechanisms of adaptation to retinal light. Our results suggest that K1 ffERG is generated by retinal mechanisms with intermediate- to long-term light adaptation, while K2.1 ffERG is generated by retinal mechanism with fast light adaptation course.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Full-field ERG; Light adaptation; Pseudorandom stimulation; Retina; Visual electrophysiology

Psychometric curves in retinitis pigmentosa patients - Fars, Julien; Huchzermeyer, Cord; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2021)
CRIS-Team WoS Importer:2021-10-01

Psychophysical temporal contrast sensitivities for modulation of the four photoreceptor types using the silent substitution paradigm at different retinal illuminances - Huchzermeyer, Cord; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2014)
Keywords: 730 temporal vision; 471 color vision; 693 retinal connections; networks; circuitry

Relationship between stimulus size and different components of the electroretinogram (ERG) elicited by flashed stimuli - Nittmann, Mathias; Aher, Avinash; Kremers, Jan; Tzekov, Radouil T. (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-11-01

Relationship between stimulus size and different components of the electroretinogram (ERG) elicited by flashed stimuli - Nittmann, Mathias G.; Aher, Avinash; Kremers, Jan; Tzekov, Radouil (Documenta Ophthalmologica, 2020)
Purpose: To investigate how light stimulus conditions of varying spatial sizes affect components of the flash and long-flash electroretinogram (ERG) in normal subjects. Method: Three stimulus conditions were generated by a Ganzfeld stimulator: a white flash on white background (WoW), a red flash on a blue background (RoB) and an L+M-cone isolating on–off (long flash) stimulus (Cone Iso). ERGs were recorded from six subjects (5 M, 1 F) with DTL electrodes to full-field (FF), 70°, 60°, 50°, 40°, 30° and 20° diameter circular stimuli. Amplitudes and peak times for a-, b-, d- and i-wave, and PhNR were examined. PhNR amplitudes were estimated in two different ways: from baseline (fB) and from preceding b-wave peak (fP). Results: With decreasing stimulus size, amplitudes for all ERG waveform components attenuated and peak times increased, although the effect varied across different components. An exponential fit described the relationship between amplitudes and size of stimulated retinal area well for most components and conditions (R2= 0.75-0.99), except for PhNR(fB) (R2= − 0.16–0.88). For peak times, an exponential decay function also fitted the data well (R2= 0.81–0.97), except in a few cases where the exponential constant was too small and a linear regression function was applied instead (a-wave Cone Iso, b- and i-wave WoW). The exponential constants for RoB amplitudes (b-wave, PhNR(fB), PhNR(fP)) were larger compared to their counterparts under WoW (p < 0.05), while there was no difference between the constants for a-wave amplitudes and peak times and for PhNR peak times. The exponential constants of amplitudes vs. area under WoW and Cone Iso were remarkably similar, while under RoB PhNR(fB) showed larger constants compared to either a- or b-wave (p < 0.05). Conclusion: ERG components change in a predictable way with stimulus size and spectral characteristics of the stimulus under these conditions. This predictability could allow a modified version of these sets of stimuli to be tested for clinical applicability.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Electroretinogram; Flash stimuli; Photopic negative response; Square wave stimuli; Stimulus size

Relationship between temporal L-coneflicker sensitivity and established clinical parameters in Stargardt's disease - Huchzermeyer, Cord; Fars, Julien; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2021)
CRIS-Team WoS Importer:2021-10-15

Reproducibility of Multifocal Erg Responses in Patients and Healthy Subjects - Link, B.; Ruehl, S.; Jünemann, Anselm; Horn, Folkert; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2010)
Keywords: electroretinography: clinical

Rescue of Defective Electroretinographic Responses in Dp71-Null Mice With AAV-Mediated Reexpression of Dp71 - Salgueiro Barboni, Mirella Telles; Vaillend, Cyrille; Joachimsthaler, Anneka; Passos Liber, Andre Mauricio; Khabou, Hanen; Roux, Michel J.; Vacca, Ophelie; Vignaud, Lucile; Dalkara, Deniz; Guillonneau, Xavier; Ventura, Dora Fix; Rendon, Alvaro; et al. (Investigative Ophthalmology & Visual Science, 2020)
PURPOSE. To study the potential effect of a gene therapy, designed to rescue the expression of dystrophin Dp71 in the retinas of Dp71-null mice, on retinal physiology.
CRIS-Team WoS Importer:2020-03-20

Responses of postreceptoral pathways elicited by L- And M-cone isolating ON- And OFF-electroretinograms in glaucoma patients - Aher, Avinash; Horn, Folkert; Huchzermeyer, Cord; Lämmer, Robert; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2021)
PURPOSE. To compare the electroretinographical (ERG) responses elicited by L- and M-cone isolating ON- and OFF-sawtooth stimuli in normal subjects and glaucoma patients. METHODS. Twenty-one normal subjects and 44 primary open-angle glaucoma patients participated in the study. L- and M-cone isolating (18% cone contrast; 284 cd/m2) rapid ON- and rapid OFF-sawtooth (4 Hz) stimuli with two stimulus sizes (full-field (FF) and central 70° diameter) were generated using the triple silent substitution technique. ON- and OFF-response asymmetries were studied by adding the two (to obtain L-add and M-add responses). The initial positive (P) and subsequent late negative (LN) components of the L-add and M-add ERGs were compared between the subject groups and correlated with retinal nerve fiber layer thickness (RNFLT) and pattern ERG responses. RESULTS. The responses to L-ON and to M-OFF stimuli and vice versa resembled each other particularly with 70° stimuli. The PL-add amplitudes were not significantly different between the normal subjects and glaucoma patients, whereas the LNL-add amplitude was significantly (P < 0.01) smaller in the glaucoma patients. Both PM-add and LNM-add were not significantly different between the subject groups. The PERG amplitude with 0.8° check sizes and the 0.8°/16° amplitude ratio (PERG ratio) were significantly (P < 0.05) different between the subject groups. The 70° LNL-add amplitude and the 0.8° PERG amplitude were significantly correlated with RNFLT. CONCLUSIONS. The ERGs to 70° cone isolating sawtooth stimuli reflect cone opponency. The cone opponent ERG responses were not significantly different between glaucoma patients and normal subjects. Luminance driven L-add responses were significantly different, indicating that central luminance signals are mainly affected in glaucoma.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Glaucoma; Magnocellular; ON- and OFF electroretinogram; Parvocellular; Sawtooth stimuli; Silent substitution; Stimulus size

Retinal disorders in northern Brazilian patients treated with chloroquine assessed by multifocal ERG - Raster, M.; Horn, Folkert; Jünemann, Anselm; Rosa, A. A. M.; Souza, G. S.; Gomes, B. D.; Lima, M. G.; Silveira, L. C. L.; Kremers, Jan (Documenta Ophthalmologica, 2011)
The effects of chloroquine intake on the retinal function in a Brazilian population of patients were assessed by multifocal electroretinography. Twenty-four randomly chosen eyes of patients treated with chloroquine for rheumatoid arthritis and systemic lupus erythematosus were examined using multifocal electroretinography (mfERG). Control measurements were acquired from 21 randomly chosen eyes of age-matched healthy subjects. None of the study participants had an inherited retinal disease or a Snellen visual acuity reduced to less than 20/40. In patients and control subjects, cumulative chloroquine dose, total daily dose, duration of treatment, retinal examination, visual field defects, visual acuity, and the mfERG were assessed. The average amplitudes and implicit times of the N1, P1, and P2 components of the mfERGs were measured in the central hexagon (R1) and in five rings (R2-R6). The values measured in patients and normal subjects were compared. The P1 amplitudes in R2 were significantly decreased in the patients. In addition, the amplitudes of N1 and N2 in R1 were significantly smaller in the patients. The implicit times of none of the components were significantly different between patients and controls. The response amplitude was not significantly correlated with cumulative dose and duration of intake. There was no correlation with retinal appearance, visual field, and visual acuity. In agreement with earlier data, the central mfERG amplitudes were decreased in chloroquine patients indicating functional alterations in the retina. These changes are also present in a Brazilian population suggesting that the effects of chloroquine are general and that genetic background and life circumstances probably have, if at all, only little effect.
EVALuna2:21006

Retinal dystrophins and the retinopathy of Duchenne muscular dystrophy - Barboni, Mirella Telles Salgueiro; Joachimsthaler, Anneka; Roux, Michel J.; Nagy, Zoltán Zsolt; Ventura, Dora Fix; Rendon, Alvaro; Kremers, Jan; Vaillend, Cyrille (Progress in Retinal and Eye Research, 2022)
Duchenne muscular dystrophy (DMD) is caused by X-linked inherited or de novo DMD gene mutations predominantly affecting males who develop early-onset muscle degeneration, severely affecting their quality of life and leading to reduced life expectancy. DMD patients may also develop proliferative retinopathy, cataract, ERG abnormalities, altered contrast sensitivity, color vision losses, and elevated flash detection thresholds during dark adaptation. Depending on the position of the genetic alteration in the large DMD gene, it is associated with a lack of the full-length dystrophin protein possibly with an additional loss of one or several other dystrophins, which are normally transcribed from internal promoters in retina and crystalline lens. During the last decades, the properties of the dystrophins have been characterized in patients with different genetic alterations and in genetic mouse models of DMD. The complex expression pattern of the dystrophins in photoreceptors, Müller glial cells and astrocytes, likely influences synaptic transmission, ionic balance and vascular integrity of the retina. However, the specific function of each retinal dystrophin remains largely unknown. This review describes the current knowledge on dystrophin expression, the putative molecular, structural, and physiological properties of retinal dystrophins, and the main clinical implications associated with the loss of dystrophins in DMD patients and mouse models. Current data and working hypotheses warrant future research on retinal dystrophins to increase our understanding of dystrophin function in the central nervous system in general and to unveil new retinal mechanisms and therapeutic avenues for retinal diseases.
CRIS-Team Scopus Importer:2022-12-02
Keywords: DMD gene; Duchenne and becker muscular dystrophy; Dystrophin; Electroretinogram; Gene therapy; Retina

Rod- and cone-driven responses in mice expressing human L-cone pigment - Tsai, Tina I.; Atorf, Jenny; Neitz, Maureen; Neitz, Jay; Kremers, Jan (Journal of Neurophysiology, 2015)
The mouse is commonly used for studying retinal processing, primarily because it is amenable to genetic manipulation. To accurately study photoreceptor driven signals in the healthy and diseased retina, it is of great importance to isolate the responses of single photoreceptor types. This is not easily achieved in mice because of the strong overlap of rod and M-cone absorption spectra (i.e., maxima at 498 and 508 nm, respectively). With a newly developed mouse model (Opn1lw(LIAIS)) expressing a variant of the human L-cone pigment (561 nm) instead of the mouse M-opsin, the absorption spectra are substantially separated, allowing retinal physiology to be studied using silent substitution stimuli. Unlike conventional chromatic isolation methods, this spectral compensation approach can isolate single photoreceptor subtypes without changing the retinal adaptation. We measured flicker electroretinograms in these mutants under ketamine-xylazine sedation with double silent substitution (silent S-cone and either rod or M/L-cones) and obtained robust responses for both rods and (L-)cones. Small signals were yielded in wild-type mice, whereas heterozygotes exhibited responses that were generally intermediate to both. Fundamental response amplitudes and phase behaviors (as a function of temporal frequency) in all genotypes were largely similar. Surprisingly, isolated (L-)cone and rod response properties in the mutant strain were alike. Thus the LIAIS mouse warrants a more comprehensive in vivo assessment of photoreceptor subtype-specific physiology, because it overcomes the hindrance of overlapping spectral sensitivities present in the normal mouse.
EVALuna2:21228

Rod and S-cone driven ERG signals at high retinal illuminances - Kremers, Jan; Czop, Dariusz; Link, Barbara (Documenta Ophthalmologica, 2009)
The purpose of the present study was to investigate whether L- and M-cone driven responses can be influenced by concomitant modulation in the rods or the S-cones. In addition, it was studied whether a change in the state of adaptation in L- or M-cones can have a different influence on ERG data when simultaneously the mean number of photoisomerizations in either rods or S-cones is altered. It was found that rods and/or S-cones cannot be neglected when measuring L- or M-cone driven ERGs.
Keywords: Electroretinogram; Rod driven signals; S-cone driven signals; Temporal frequency; Retinal illuminance

Rod Electroretinograms Elicited by Silent Substitution Stimuli from the Light-Adapted Human Eye - Maguire, John; Parry, Neil R. A.; Kremers, Jan; Kommanapalli, Deepika; Murray, Ian J.; Mckeefry, Declan J. (Translational Vision Science & Technology, 2016)
To demonstrate that silent substitution stimuli can be used to generate electroretinograms (ERGs) that effectively isolate rod photoreceptor function in humans without the need for dark adaptation, and that this approach constitutes a viable alternative to current clinical standard testing protocols.Rod-isolating and non-isolating sinusoidal flicker stimuli were generated on a 4 primary light-emitting diode (LED) Ganzfeld stimulator to elicit ERGs from participants with normal and compromised rod function who had not undergone dark-adaptation. Responses were subjected to Fourier analysis, and the amplitude and phase of the fundamental were used to examine temporal frequency and retinal illuminance response characteristics.Electroretinograms elicited by rod-isolating silent substitution stimuli exhibit low-pass temporal frequency response characteristics with an upper response limit of 30 Hz. Responses are optimal between 5 and 8 Hz and between 10 and 100 photopic trolands (Td). There is a significant correlation between the response amplitudes obtained with the silent substitution method and current standard clinical protocols. Analysis of signal-to-noise ratios reveals significant differences between subjects with normal and compromised rod function.Silent substitution provides an effective method for the isolation of human rod photoreceptor function in subjects with normal as well as compromised rod function when stimuli are used within appropriate parameter ranges.This method of generating rod-mediated ERGs can be achieved without time-consuming periods of dark adaptation, provides improved isolation of rod- from cone-based activity, and will lead to the development of faster clinical electrophysiologic testing protocols with improved selectivity.
EVALuna2:21318

Rod versus cone driven ERGs at different stimulus sizes - Aher, Avinash; Mckeefry, Declan J.; Parry, Neil Robert Alan; Maguire, John; Murray, Ian J.; Tsai, Tina I.; Huchzermeyer, Cord; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2017)

Rod- versus cone-driven ERGs at different stimulus sizes in normal subjects and retinitis pigmentosa patients - Aher, Avinash; Mckeefry, Declan J.; Parry, Neil R. A.; Maguire, John; Murray, I. J.; Tsai, Tina I.; Huchzermeyer, Cord; Kremers, Jan (Documenta Ophthalmologica, 2018)
Purpose To study how rod- and cone-driven responses depend on stimulus size in normal subjects and patients with retinitis pigmentosa (RP), and to show that comparisons between responses to full-field (FF) and smaller stimuli can be useful in diagnosing and monitoring disorders of the peripheral retina without the need for lengthy dark adaptation periods.Method The triple silent substitution technique was used to isolate L-cone-, M-cone- and rod-driven ERGs with 19, 18 and 33% photoreceptor contrasts, respectively, under identical mean luminance conditions. Experiments were conducted on five normal subjects and three RP patients. ERGs on control subjects were recorded at nine different temporal frequencies (between 2 and 60 Hz) for five different stimulus sizes: FF, 70A degrees, 60A degrees, 50A degrees and 40A degrees diameter circular stimuli. Experiments on RP patients involved rod- and L-cone-driven ERG measurements with FF and 40A degrees stimuli at 8 and 48 Hz. Response amplitudes were defined as those of the first harmonic component after Fourier analysis.Results In normal subjects, rod-driven responses displayed a fundamentally different behavior than cone-driven responses, particularly at low temporal frequencies. At low and intermediate temporal frequencies (<= 12 Hz), rod-driven signals increased by a factor of about four when measured with smaller stimuli. In contrast, L- and M-cone-driven responses in this frequency region did not change substantially with stimulus size. At high temporal frequencies (>= 24 Hz), both rod- and cone-driven response amplitudes decreased with decreasing stimulus size. Signals obtained from rod-isolating stimuli under these conditions are likely artefactual. Interestingly, in RP patients, both rod-driven and L-cone-driven ERGs were similar using 40A degrees and FF stimuli.Conclusion The increased responses with smaller stimuli in normal subjects to rod-isolating stimuli indicate that a fundamentally different mechanism drives the ERGs in comparison with the cone-driven responses. We propose that the increased responses are caused by stray light stimulating the peripheral retina, thereby allowing peripheral rod-driven function to be studied using the triple silent substitution technique at photopic luminances. The method is effective in studying impaired peripheral rod- and cone- function in RP patients.
Keywords: Rods; Cones; Stimulus size; Electroretinogram; Retinitis pigmentosa

Selektive Stimulation der verschiedenen Fotorezeptorklassen mittels Silent Substitution bei psychophysischen und elektroretinografischen Messungen - Huchzermeyer, Cord; Kremers, Jan (Klinische Monatsblätter für Augenheilkunde, 2022)
The silent substitution technique allows creating photoreceptor- selective stimuli for psychophysical and electrophysiological tests. In contrast to other techniques, the purpose of silent substitution is not to make the targeted photoreceptor type more sensitive in comparison to the other types, but to make the stimulus invisible ("silent") to the other photoreceptor types. This allows selectivity independent of the retinal state of adaptation and enables comparing photoreceptor types under identical conditions. The foundations of these techniques will be explained in this paper. Furthermore, the importance of postreceptoral processing for the perception of photoreceptor-selective stimuli is discussed here. Although this technique is currently only available in specialized vision science labs, there is an enormous potential for clinical application.
CRIS-Team Scopus Importer:2022-12-23
Keywords: electrophysiology; glaucoma; psychophysics; retina

Simultaneous chromatic and luminance human electroretinogram responses - Parry, Neil R. A.; Murray, Ian J.; Panorgias, Athanasios; Mckeefry, Declan J.; Lee, Barry B.; Kremers, Jan (The Journal of Physiology, 2012)
The parallel processing of information forms an important organisational principle of the primate visual system. Here we describe experiments which use a novel chromatic-achromatic temporal compound stimulus to simultaneously identify colour and luminance specific signals in the human electroretinogram (ERG). Luminance and chromatic components are separated in the stimulus; the luminance modulation has twice the temporal frequency of the chromatic modulation. ERGs were recorded from four trichromatic and two dichromatic subjects (1 deuteranope and 1 protanope). At isoluminance, the fundamental (first harmonic) response was elicited by the chromatic component in the stimulus. The trichromatic ERGs possessed low-pass temporal tuning characteristics, reflecting the activity of parvocellular post-receptoral mechanisms. There was very little first harmonic response in the dichromats' ERGs. The second harmonic response was elicited by the luminance modulation in the compound stimulus and showed, in all subjects, band-pass temporal tuning characteristic of magnocellular activity. Thus it is possible to concurrently elicit ERG responses from the human retina which reflect processing in both chromatic and luminance pathways. As well as providing a clear demonstration of the parallel nature of chromatic and luminance processing in the human retina, the differences that exist between ERGs from trichromatic and dichromatic subjects point to the existence of interactions between afferent post-receptoral pathways that are in operation from the earliest stages of visual processing.
EVALuna2:21088

Single opsin driven white noise ERGs in mice - Stallwitz, Nina; Joachimsthaler, Anneka; Kremers, Jan (Frontiers in Neuroscience, 2023)
Purpose: Electroretinograms elicited by photopigment isolating white noise stimuli (wnERGs) in mice were measured. The dependency of rod- and cone-opsin-driven wnERGs on mean luminance was studied. Methods: Temporal white noise stimuli (containing all frequencies up to 20 Hz, equal amplitudes, random phases) that modulated either rhodopsin, S-opsin or L*-opsin, using the double silent substitution technique, were used to record wnERGs in mice expressing a human L*-opsin instead of the native murine M-opsin. Responses were recorded at 4 mean luminances (MLs). Impulse response functions (IRFs) were obtained by cross-correlating the wnERG recordings with the corresponding modulation of the photopigment excitation elicited by the stimulus. So-called modulation transfer functions (MTFs) were obtained by performing a Fourier transform on the IRFs. Potentials of two repeated wnERG recordings at corresponding time points were plotted against each other. The correlation coefficient (r2repr) of the linear regression through these data was used to quantify reproducibility. Another correlation coefficient (r2ML) was used to quantify the correlations of the wnERGs obtained at different MLs with those at the highest (for cone isolating stimuli) or lowest (for rod isolating stimuli) ML. Results: IRFs showed an initial negative (a-wave like) trough N1 and a subsequent positive (b-wave like) peak P1. No oscillatory potential-like components were observed. At 0.4 and 1.0 log cd/m2 ML robust L*- and S-opsin-driven IRFs were obtained that displayed similar latencies and dependencies on ML. L*-opsin-driven IRFs were 2.5–3 times larger than S-opsin-driven IRFs. Rhodopsin-driven IRFs were observed at −0.8 and − 0.2 log cd/m2 and decreased in amplitude with increasing ML. They displayed an additional pronounced late negativity (N2), which may be a correlate of retinal ganglion cell activity. R2repr and r2ML values increased for cones with increasing ML whereas they decreased for rods. For rhodopsin-driven MTFs at low MLs and L*-opsin-driven MTFs at high MLs amplitudes decreased with increasing frequency, with much faster decreasing amplitudes for rhodopsin. A delay was calculated from MTF phases showing larger delays for rhodopsin- vs. low delays for L*-opsin-driven responses. Conclusion: Opsin-isolating wnERGs in mice show characteristics of different retinal cell types and their connected pathways.
CRIS-Team Scopus Importer:2023-08-25
Keywords: electroretinography (ERG); mouse retina; photopigment; silent substitution; temporal white noise (TWN)

Spatial distributions of on- and off-responses determined with the multifocal ERG - Rodrigues, Anderson R.; Da Silva Filho, Manoel; Silveira, Luiz Carlos L.; Kremers, Jan (Documenta Ophthalmologica, 2010)
We studied the contribution of retinal on- and off-mechanisms in the multifocal electroretinogram (mfERG) by measuring responses to sawtooth stimuli. Six healthy subjects participated in this study. Rapid-on and rapid-off sawtooth stimuli with a period of 427 ms were presented in a multifocal pattern composed of 19 hexagons. The stimuli were interleaved with a blank field of the mean luminance and chromaticity. On- and off-responses were added to extract response asymmetries. The amplitudes of on-, off-, and added-responses were determined for different eccentricities relative to a signal baseline that was defined as the average of the electrical level recorded in two different time windows in which no responses were present. Measurements were repeated with eight different stimulus stretch factors to account for changes in retinal cell density as a function of eccentricity. The amplitudes of all ERG components decreased with increasing eccentricity for all stretch factors. For stretch factors between 0 and 20, responses to the central and immediately adjacent hexagons were large in amplitude. For more peripheral hexagons, the responses were very small or absent. Three components were identified in the on-responses (N20(on), P46(on) and N100(on)). In the off-responses, we found one positive (P20(off)) and one negative (N90(off)) component, whereas in the addition, three components (N20(add), P46(add) and N100(add)) could be observed. The N20(on) and P46(on) amplitudes decreased less steeply with eccentricity than the N100(on) amplitude, whilst the P20(off) and N90(off) amplitudes exhibited a similar decrease with eccentricity. In the addition, the two negative components exhibited a similar decrease in amplitude as a function of eccentricity and decreased more steeply than the positive component. The number of stimulated cones and retinal ganglion cells was estimated from anatomical data and compared with the responses. The spatial properties of the amplitudes of N20(on), P46(on), P20(off), and N90(off) and P46(add) were similar to those of the stimulated cone numbers. The remaining components had spatial characteristics that resembled those of the retinal ganglion cells. It is proposed that the ERG asymmetries revealed in the summed responses have post-receptoral origins, some of them reflecting the activity of the ganglion cell population. The use of sawtooth stimuli provide, similar to the pattern ERG, a way to record the ERG asymmetries.
Keywords: On- and off-mechanisms; Multifocal ERG; Retinal pathways; Retinal eccentricity

Spatial Properties of Electroretinograms Elicited by High Temporal Frequency L- and M-cone Isolating Stimuli - Aher, Avinash; Jacob, Mellina M.; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-11-01

Spatial properties of L- and M-cone driven incremental (On-) and decremental (Off-) electroretinograms: evidence for the involvement of multiple post-receptoral mechanisms - Tsai, Tina I.; Jacob, Mellina M.; Mckeefry, Declan; Murray, Ian J.; Parry, Neil R. A.; Kremers, Jan (Journal of the Optical Society of America A-Optics Image Science and Vision, 2016)
An overview of electroretinogram response components to incremental and decremental steps in L- and M-cone excitation was obtained in human observers, while varying the spatial properties of the stimulus. Responses to L- and M-cone stimuli of opposite polarity resembled each other, particularly within the central 35° of the retina. All amplitudes grew as stimulus size increased; however, earlier and later components of the On- and Off-responses showed differing degrees of dependency on stimulus size. Thus, they may reflect different proportions of responses originating in parvocellular (less stimulus size-dependent) and magnocellular (more stimulus size-dependent) streams.
EVALuna2:21297

Spatial properties of L- and M-cone driven incremental (on-) and decremental (off-) electroretinograms: normal subjects Vs. glaucoma patients - Aher, Avinash; Horn, Folkert; Huchzermeyer, Cord; Lämmer, Robert; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2021)
CRIS-Team WoS Importer:2021-09-24

Spatial receptive field properties of lateral geniculate cells in the owl monkey (Aotus azarae) at different contrasts: a comparative study - Kilavik, B.E.; Silveira, L. C. L.; Kremers, Jan (European Journal of Neuroscience, 2007)
Several physiological properties of owl monkey lateral geniculate nucleus (LGN) cells were studied to verify whether its nocturnal habit has an influence on the organization of its subcortical visual system. Receptive field (RF) dimensions were measured using drifting gratings and bipartite field stimuli. We found that owl monkey cells LGN have larger RFs and were on average more non-linear than those of diurnal monkeys. But, as in other anthropoids, there is an increase in RF centre size with increasing eccentricity, and there is a limited correlation between these centre sizes and retinal ganglion cell dendritic tree sizes. The influence of contrast on sizes and peak sensitivities of RF centres and surrounds and on the response phases was studied. Both the sizes and peak sensitivities of the RF centres and surrounds decrease as contrast increases. As a result, the responses to low spatial frequency stimuli saturate with increasing contrast. Estimates of contrasts at half-maximal responses confirm the presence of saturation. It was found that the magnocellular cells saturate more strongly than parvocellular cells. The response phase increases with increasing contrast. These data resemble those obtained in the common marmoset, indicating that these are basic features of the primate visual system. We conclude that during evolution and as an adaptation to a nocturnal lifestyle, cells in the owl monkey LGN display an increased spatial integration in comparison with diurnal primate species, without a change in the basic organization common to the primate subcortical visual system.
Keywords: contrast sensitivity; koniocellular; lateral geniculate nucleus; magnocellular; parvocellular; primates

Spectral characteristics of the PhNR in the full-field flash electroretinogram of normals and glaucoma patients - Kremers, Jan; Jertila, Mounira; Link, Barbara; Pangeni, Gobinda; Horn, Folkert (Documenta Ophthalmologica, 2012)
Flash electroretinogram responses were measured in normal subjects to different chromatic combinations of flashes and backgrounds. The amplitudes of the flash response components were measured at different flash strengths and could be described by a generalized Naka-Rushton function. The measurements were repeated at different background luminances to study adaptation effects. It was found that when flash strength and background luminance were expressed in photometric terms (cd s/m² and cd/m², respectively), then the responses were very similar for all chromatic combinations with the exception of the condition in which blue (peak wavelength 458 nm) was flashed upon an orange (peak wavelength 591 nm) background. We propose that in this condition, a second (possibly S-cone or rod-driven) mechanism intrudes. The negative response after the b-wave (here called "photopic negative response" or PhNR for all conditions) is thought to reflect ganglion cell activity and was also largest at this condition. Responses were measured to the 458 nm flash on 591 nm background and the reversed combination in a population of 39 normal subjects and 49 glaucoma patients. It was found that the PhNR amplitude was affected by glaucoma in all conditions. Other component parameters, reflecting responses and adaptation dynamics, were not altered. The best stimulus condition among the conditions used to separate the PhNR amplitude of normals and patients was a 1 cd s/m² 458 nm flash on a 10 cd/m² 591 nm background.
EVALuna2:21075

Steady-state multifocal visual evoked potential (ssmfVEP) using dartboard stimulation as a possible tool for objective visual field assessment - Horn, Folkert; Selle, Franziska; Hohberger, Bettina; Kremers, Jan (Graefes Archive For Clinical and Experimental Ophthalmology, 2016)
To investigate whether a conventional, monitor-based multifocal visual evoked potential (mfVEP) system can be used to record steady-state mfVEP (ssmfVEP) in healthy subjects and to study the effects of temporal frequency, electrode configuration and alpha waves.Multifocal pattern reversal VEP measurements were performed at 58 dartboard fields using VEP recording equipment. The responses were measured using m-sequences with four pattern reversals per m-step. Temporal frequencies were varied between 6 and 15 Hz. Recordings were obtained from nine normal subjects with a cross-shaped, four-electrode device (two additional channels were derived). Spectral analyses were performed on the responses at all locations. The signal to noise ratio (SNR) was computed for each response using the signal amplitude at the reversal frequency and the noise at the neighbouring frequencies.Most responses in the ssmfVEP were significantly above noise. The SNR was largest for an 8.6-Hz reversal frequency. The individual alpha electroencephalogram (EEG) did not strongly influence the results. The percentage of the records in which each of the 6 channels had the largest SNR was between 10.0 and 25.2 %.Our results in normal subjects indicate that reliable mfVEP responses can be achieved by steady-state stimulation using a conventional dartboard stimulator and multi-channel electrode device. The ssmfVEP may be useful for objective visual field assessment as spectrum analysis can be used for automated evaluation of responses. The optimal reversal frequency is 8.6 Hz. Alpha waves have only a minor influence on the analysis. Future studies must include comparisons with conventional mfVEP and psychophysical visual field tests.
EVALuna2:21244

Steady-State Visually Evoked Potentials Elicited by Multifrequency Pattern-Reversal Stimulation - Hohberger, Bettina; Kremers, Jan; Horn, Folkert (Translational Vision Science & Technology, 2019)
Purpose: It has been shown that multifrequency stimulation with multifocal electroretinography can reduce recording time without a loss in signal-to-noise ratio. Here, we studied the applicability of multifrequency stimulations for steady-state visually evoked potential (VEP) recordings.
CRIS-Team WoS Importer:2019-03-15
Keywords: Objective visual field test; Multifocal VEP; Signal-to-noise ratio; Pattern reversal; Steady-state

Strain differences in illumination-dependent structural changes at mouse photoreceptor ribbon synapses - Fuchs, Michaela; Sendelbeck, Anna; Atorf, Jenny; Kremers, Jan; Brandstätter, Johann Helmut (Journal of Comparative Neurology, 2013)
Photoreceptor cells encode light signals over a wide range of intensities with graded changes in their membrane potential. At their highly specialized ribbon synapses they transmit the signals to the postsynaptic neurons by the tonic release of glutamate, which is continuously adjusted to changes in light intensity. Such a level of performance requires adaptive mechanisms, and it is suggested that illumination-dependent changes in ribbon shape and size are one of these adaptive processes. In this study we compared structural properties of synaptic ribbons under various illumination conditions between three mouse strains: the pigmented C57BL/6 and the two albino strains Balb/c and B6(Cg)-Tyr(c-2J) /J (coisogenic to C57BL/6). In addition, electroretinograms (ERGs) recorded in the same groups were compared. In the C57BL/6 mouse a change in illumination did not result in structural alterations of the synaptic ribbon. Similarly, in the B6(Cg)-Tyr(c-2J) /J mouse only minor structural changes were detected. In contrast, the state of adaptation had a large influence on the ribbon structure of the Balb/c mouse. The ERG recordings showed only small functional differences between C57BL/6 and B6(Cg)-Tyr(c-2J) /J mice, but the retinal function of Balb/c mice was strongly compromised. We conclude that illumination-dependent changes of photoreceptor ribbon structure differ between strains and thus cannot be regarded as a general mechanism for light adaptation.
EVALuna2:21087

Summation of Temporal L-Cone- and M-Cone-Contrast in the Magno- and Parvocellular Retino-Geniculate Systems in Glaucoma - Huchzermeyer, Cord; Horn, Folkert; Lämmer, Robert; Mardin, Christian; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2021)
Purpose: The purpose of this study was to characterize summation of temporal L- and M-cone contrasts in the parvo- (P-) and magnocellular (M-) pathways in glaucoma and the relationship between the respective temporal contrast sensitivities (tCS) and clinical parameters. Methods: Perifoveal tCS to isolated or combined L- and M-cone contrasts (with different contrast ratios, and therefore different luminance and chromatic components) were measured at different temporal frequencies (at 1 or 2 Hz and at 20 Hz) using triple silent substitution in 73 subjects (13 healthy, 25 with glaucoma, and 35 with perimetric glaucoma). A vector summation model was used to analyze whether perception was driven by the P-pathway, the M-pathway, or both. Using this model, L- and M-cone input strengths (AL, AM) and phase differences between L- and M-cone inputs were estimated. Results: Perception was always mediated by the P-pathway at low frequencies, as indicated by a median phase angle of 179.84 degrees (cone opponency) and a median AL/AM ratio of 1.04 (balanced L- and M-cone input strengths). In contrast, perception was exclusively mediated by the M-pathway at higher frequencies (input strength not balanced: AL/AM = 2.94, median phase angles = 130.17 degrees). Differences in phase were not significant between diagnosis groups (Kruskal-Wallis = 0.092 for P- and 0.35 for M-pathway). We found differences between groups only for the M-pathway (L-cone tCS deviations at 20 Hz were significantly lower in the patients with glaucoma P = 0.014, with a strong tendency in M-cones P = 0.049). L-cone driven tCS deviations at 20 Hz were linearly correlated with perimetric mean defect (MD) and quadratically correlated with retinal nerve fiber layer (RNFL) thickness. Conclusions: Unaltered phase angles between L- and M-cone inputs in glaucoma indicated intact temporal processing. Only in the M-pathway, contrast sensitivity deviations were closely related to diagnosis group, MD, and RNFL thickness, indicating M-pathway involvement.
CRIS-Team Scopus Importer:2021-06-04

Temporal characteristics of L- and M-cone isolating steady-state electroretinograms - Kommanapalli, Deepika; Murray, Ian J.; Kremers, Jan; Parry, Neil R. A.; Mckeefry, Declan J. (Journal of the Optical Society of America A-Optics Image Science and Vision, 2014)
Cone isolating stimuli were used to assess the temporal frequency response characteristics of L- and M-cone electroretinograms (ERGs) in nine trichromatic and four dichromatic human observers. The stimuli comprised sinusoidal temporal modulations varying from 5 to 100 Hz. ERGs were recorded using corneal fiber electrodes and subjected to fast Fourier transform analysis. At low temporal frequencies (<10 Hz) the L- and M-cone ERGs had similar amplitude and exhibited minimal differences in apparent latency. At higher flicker rates (>20 Hz) L-cone ERGs had greater amplitudes and shorter apparent latencies than the M-cone responses. These differences between the L- and M-cone ERGs are consistent with their mediation by chromatic and luminance postreceptoral processing pathways at low and high temporal frequencies, respectively.
EVALuna2:21213

Temporal Contrast Sensitivities are Locally Reduced around 4Hz for L-cone- and around 10Hz for M-cone isolating stimuli in Glaucoma Patients - Huchzermeyer, Cord; Haubner, Sarah; Lämmer, Robert; Mardin, Christian Y.; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2016)

Temporal contrast sensitivities elicited by the four photoreceptor classes using the silent substitution paradigm in retinitis pigmentosa - Huchzermeyer, Cord; Auer, Judith; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2015)

The Association Between Acquired Color Deficiency and PET Imaging of Neurodegeneration in Mild Cognitive Impairment and Alzheimer Disease - Vidal, Kallene Summer Moreira; Decleva, Diego; Barboni, Mirella Telles Salgueiro; Nagy, Balazs Vince; De Menezes, Paulo Augusto Hidalgo; Aher, Avinash; Coutinho, Artur Martins; Squarzoni, Paula; Faria, Daniele De Paula; Duran, Fabio Luis De Souza; Buchpiguel, Carlos Alberto; Kremers, Jan; et al. (Investigative Ophthalmology & Visual Science, 2022)
PURPOSE. To evaluate color vision changes and retinal processing of chromatic and lumi-nance pathways in subjects with Alzheimer disease (AD) and mild cognitive impairment (MCI) compared with a matched control group and whether such changes are associated with impaired brain glucose metabolism and beta-amyloid deposition in the brain.METHODS. We evaluated 13 patients with AD (72.4 +/- 7.7 years), 23 patients with MCI (72.5 +/- 5.5 years), and 18 controls of comparable age (P = 0.44) using Cambridge color test and the heterochromatic flicker ERG (HF-ERG). The Cambridge color test was performed using the trivector protocol to estimate the protan, deutan and tritan color confusion axes. HF-ERG responses were measured at a frequency of 12 Hz, which ERGs reflect chromatic activity, and at 36 Hz, reflecting luminance pathway. A study subsample was performed using neuropsychological assessments and positron emission tomography.RESULTS. Patients with AD presented higher mean values indicating poorer color discrim-ination for protan (P = 0.04) and deutan (P = 0.001) axes compared with the controls. Along the tritan axis, both patients with AD and patients with MCI showed decreased color vision (P = 0.001 and P = 0.001) compared with controls. The analyses from the HF-ERG protocol revealed no differences between the groups (P = 0.31 and P = 0.41). Diffuse color vision loss was found in individuals with signs of neurodegeneration (protan P = 0.002, deutan P = 0.003 and tritan P = 0.01), but not in individuals with signs of beta-amyloid deposition only (protan P = 0.39, deutan P = 0.48, tritan P = 0.63), regardless of their clinical classification.CONCLUSIONS. Here, patients with AD and patients with MCI present acquired color vision deficiency that may be linked with impaired brain metabolism.
CRIS-Team WoS Importer:2023-04-28

The BEACH Protein LRBA Promotes the Localization of the Heterotrimeric G-protein Golf to Olfactory Cilia - Kurtenbach, Stefan; Gießl, Andreas; Stromberg, Siv; Kremers, Jan; Atorf, Jenny; Rasche, Sebastian; Neuhaus, Eva M.; Herve, Denis; Brandstätter, Johann Helmut; Asan, Esther; Hatt, Hanns; Kilimann, Manfred W. (Scientific Reports, 2017)
BEACH domain proteins are involved in membrane protein traffic and human diseases, but their molecular mechanisms are not understood. The BEACH protein LRBA has been implicated in immune response and cell proliferation, and human LRBA mutations cause severe immune deficiency. Here, we report a first functional and molecular phenotype outside the immune system of LRBA-knockout mice: compromised olfaction, manifesting in reduced electro-olfactogram response amplitude, impaired food-finding efficiency, and smaller olfactory bulbs. LRBA is prominently expressed in olfactory and vomeronasal chemosensory neurons of wild-type mice. Olfactory impairment in the LRBA-KO is explained by markedly reduced concentrations (20-40% of wild-type levels) of all three subunits ?olf, ?1 and ?13 of the olfactory heterotrimeric G-protein, Golf, in the sensory cilia of olfactory neurons. In contrast, cilia morphology and the concentrations of many other proteins of olfactory cilia are not or only slightly affected. LRBA is also highly expressed in photoreceptor cells, another cell type with a specialized sensory cilium and heterotrimeric G-protein-based signalling; however, visual function appeared unimpaired by the LRBA-KO. To our knowledge, this is the first observation that a BEACH protein is required for the efficient subcellular localization of a lipid-anchored protein, and of a ciliary protein.
EVALuna2:21341

The consequence of modulating background on the luminance-response function of the human photopic electroretinogram - Kremers, Jan; Huchzermeyer, Cord; Aher, Avinash (Documenta Ophthalmologica, 2025)
Purpose: To study the consequences of a modulating background on the luminance-response function of the human photopic flash electroretinogram for different relative timings of the flash relative to the background luminance. Methods: Seven healthy subjects (age: 29–63 years; four females) participated in the study. We measured the response to flashes (9 flash strengths in total between 0.12 and 29.76 cd.s/m2 while doubling the strength at each step; 5 ms flash duration) on a steady background (24 cd/m2) and on a 1 Hz modulating background (24 cd/m2 mean luminance; 100% contrast). The flashes were presented at 6 different phases during the sine wave (0°, 90°, 180°, 225°, 270°, and 315°). Responses to a 1 Hz sinusoidally modulating stimulus were subtracted from the responses to the combined flash plus sine-wave stimuli to obtain the flash ERGs at different phases. Results: The a-wave and PhNR amplitudes monotonically increased with increasing flash strength. The b- and i-wave amplitudes displayed a maximum at 1.9 cd.s/m2, above which they decreased again (the so-called “Photopic hill effect”). The responses could be described by an addition of a logistic growth and a Gaussian. The parameters of these functions depended on the time of flash presentation relative to the background. The dependency of the a-, b- and i-wave on flash presentation time with constant flash strength could be described by a model that assumes that the amplitude depends on the Weber fraction of the flash including a delay and a saturation. Conclusions: The use of modulating backgrounds may increase the signal-to-noise ratio of flash ERGs and thus its diagnostic value. The dynamics of the response as a function of flash presentation time gives additional information about the retinal processing of flash and background. The photopic hill model allows the separation of processing in retinal On- and Off-pathways.
CRIS-Team Scopus Importer:2025-06-06
Keywords: ERG; Modulating background; Photopic flash electroretinogram; Photopic hill

The dynamics of rod and cone driven ERG adaptation using the silent substitution stimulation technique - Kremers, Jan; Joachimsthaler, Anneka (2018)
EVALuna2:34920

The effect of sinusoidally modulating backgrounds on flash electroretinograms - Aher, Avinash; Huchzermeyer, Cord; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2022)
CRIS-Team WoS Importer:2022-09-30

The Impact of Luminance and Temporal Frequency on S-Cone-Driven ERGs in Wildtype Mice and Mice with Long-Wavelength Absorption Spectra - Joachimsthaler, Anneka; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

The influence of melanopsin activation on the cone-mediated photopic white noise electroretinogram (wnERG) in humans - Adhikari, Prakash; Zele, Andrew J.; Cao, Dingcai; Kremers, Jan; Feigl, Beatrix (Frontiers in Optics, FIO 2018, 2018)

The influence of retinal illuminance on L- and M-cone driven electroretinograms - Kremers, Jan; Parry, Neil R. A.; Panorgias, Athanasios; Murray, Ian J. (Visual Neuroscience, 2011)
The electroretinographic response to L- and M-cone isolating stimuli was measured at different luminance levels to study the effect of retinal illuminance on amplitude and phase, and how this may influence estimates of L:M ratios in the retina. It was found that the amplitude of L- and M-cone driven responses increases differently with increasing retinal illuminance: L-cone responses increase more quickly than those of M-cones. The L:M ratio does not change strongly with retinal illuminance. The phase of both L- and M-cone driven responses advances with increasing retinal illuminance. There is considerable interindividual variability in the phase difference between the two, but generally M-cone driven responses are phase advanced.
EVALuna2:21018

The influence of stimulus size on heterochromatic modulation electroretinograms - Gomes Martins, Cristiane Maria; Tsai, Tina; Salgueiro Barboni, Mirella Telles; Da Costa, Marcelo Fernandes; Nagy, Balazs; Ventura, Dora Fix; Kremers, Jan (Journal of Vision, 2016)
When combined with the electroretinogram (ERG), the heterochromatic flicker photometry procedure allows an objective in vivo assessment of postreceptoral activity. Responses evoked at intermediate (approximately 12 Hz) and high (>30 Hz) temporal frequencies reflect the red-green cone opponent (possibly parvocellular) and the luminance (possibly magnocellular) responses, respectively. Previously, we found that cone-isolating stimuli at intermediate temporal frequencies elicited ERG responses with similar amplitudes and phases for different spatial arrangements of the stimuli, whereas response amplitudes at high temporal frequencies were positively correlated with stimulus size. The purpose of this study was to investigate whether the influence of stimulus size was confined to cone-isolating stimuli or whether it was a general feature of heterochromatic stimulation. Furthermore, we aimed to determine the smallest spatial extent for a significant response in the two postreceptoral mechanisms. Monocular ERGs were recorded to red-green counterphase modulated sinusoidal stimuli (mean luminance of 200 cd/m2) presented at 12 and 36 Hz at different stimulus sizes. At each stimulus condition, a series of ERGs were recorded with the red-contrast fraction (FR) [FR = CR/(CR + CR)] of the stimulus varying between 0.0 and 1.0. Response amplitudes at 36 Hz changed with FR for all subjects, exhibiting a V-shaped amplitude profile with a minimum close to the psychophysics-based isoluminance, where the ERG phase changed by 180°. As stimulus size decreased, the amplitudes to 36 Hz also decreased. In contrast, amplitudes and phases at 12 Hz generally were constant for all values of FR. These amplitudes were invariant to stimulus sizes larger than 10° but decreased with decreasing stimulus size below 10°. Phase also changed in this range. Thus, luminance pathway ERG responses (36 Hz) show direct dependency on stimulus size, whereas chromatic pathway responses (12 Hz) are independent of the stimulus size above 10°.
EVALuna2:21293

The influence of stimulus size on L- and M-cone driven electroretinograms - Jacob, Mellina Monteiro; Gomes, Bruno Duarte; Souza, Givago S.; Da Silva, Manoel; Mckeefry, Declan J.; Parry, Neil Robert Alan; Silveira, Luiz Carlos L.; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2014)
Keywords: 510 electroretinography: non-clinical; 688 retina; 471 color vision

The light adaptation phenomenon in human: receptoral and post-receptoral involvement - Brasil, Alodia; Tsai, Tina I.; Souza, Givago S.; Herculano, Anderson Manoel; Ventura, Dora Fix; Silveira, Luiz Carlos L.; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2016)

The melanopsin-directed white noise electroretinogram (wnERG) - Adhikari, Prakash; Zele, Andrew J.; Cao, Dingcai; Kremers, Jan; Feigl, Beatrix (Vision research, 2019)
The white noise electroretinogram (wnERG) provides a measure of the impulse response function under conditions of retinal equilibrium; it is yet to be determined how the electrical response generated by melanopsin ganglion cell photoreception is expressed in the impulse response. To this end, we recorded the human wnERG to continuous temporal white noise (TWN) stimuli that were melanopsin-directed (rod and cone silent) or cone-directed (rod and melanopsin silent). The impulse response of the electroretinogram was derived by cross-correlating the TWN stimulus with the wnERG response. We observed that the LMS-cone directed wnERG contained the expected N1 wave (24.1 ± 2.4 ms; mean ± SEM) and P1 wave (49.7 ± 1.8 ms). Melanopsin-directed stimuli produced a unique wnERG with a slower negative deflection (Nm) at 62.9 ± 3.3 ms followed by a positive deflection (Pm) at 126.3 ± 5.1 ms. Additional experiments indicated this melanopsin-directed wnERG response was not due to cone intrusion. The Nm and NmPm amplitudes increased with illuminance (32,000–80,000 Td; no rod intrusion) and melanopsin contrast (10–36% Michelson contrast). As there are known pathways connecting melanopsin cells to the outer retina, we then measured the wnERG to combined melanopsin and cone-directed stimuli to quantify melanopsin interactions with cone signalling. With the combined stimuli, the N1P1 amplitudes were suppressed by 59%, which may be a result of a destructive interference between the positive (P1) and negative (Nm) waves generated by the cone and melanopsin pathways. We conclude that the human wnERG to melanopsin-directed stimuli may reflect the combined response of intra-retinal melanopsin pathways, independent of rod and cone photoreception.
CRIS-Team Scopus Importer:2019-09-24
Keywords: Electroretinogram; Melanopsin; Silent substitution; White noise electroretinogram (wnERG)

The morphology of human rod ERGs obtained by silent substitution stimulation - Maguire, J.; Parry, N. R. A.; Kremers, Jan; Murray, I. J.; Mckeefry, D. (Documenta Ophthalmologica, 2017)
To record transient ERGs from the light-adapted human retina using silent substitution stimuli which selectively reflect the activity of rod photoreceptors. We aim to describe the morphology of these waveforms and examine how they are affected by the use of less selective stimuli and by retinal pathology.Rod-isolating stimuli with square-wave temporal profiles (250/250 ms onset/offset) were presented using a 4 primary LED ganzfeld stimulator. Experiment 1: ERGs were recorded using a rod-isolating stimulus (63 ph Td, rod contrast, C rod = 0.25) from a group (n = 20) of normal trichromatic observers. Experiment 2: Rod ERGs were recorded from a group (n = 5) using a rod-isolating stimulus (C rod = 0.25) which varied in retinal illuminance from 40 to 10,000 ph Td. Experiment 3: ERGs were elicited using 2 kinds of non-isolating stimuli; (1) broadband and (2) rod-isolating stimuli which contained varying degrees of L- and M-cone excitation. Experiment 4: Rod ERGs were recorded from two patient groups with rod monochromacy (n = 3) and CSNB (type 1; n = 2).The rod-isolated ERGs elicited from normal subjects had a waveform with a positive onset component followed by a negative offset. Response amplitude was maximal at retinal illuminances <100 ph Td and was virtually abolished at 400 ph Td. The use of non-selective stimuli altered the ERG waveform eliciting more photopic-like ERG responses. Rod ERGs recorded from rod monochromats had similar features to those recorded from normal trichromats, in contrast to those recorded from participants with CSNB which had an electronegative appearance.Our results demonstrate that ERGs elicited by silent substitution stimuli can selectively reflect the operation of rod photoreceptors in the normal, light-adapted human retina.
EVALuna2:21335

The photopic negative response of the blue-on-yellow flash-electroretinogram in glaucomas and normal subjects - Wakili, Nina; Horn, Folkert; Jünemann, Anselm; Nguyen, Nhung; Mardin, Christian Y.; Korth, Matthias-Johannes; Kremers, Jan (Documenta Ophthalmologica, 2008)
The photopic negative response of the flash-electroretinogram driven by the middle- and long-wavelength cones has been shown to be reduced in non-human primates with experimental glaucoma and in human patients with glaucoma. The photopic negative response for the blue-sensitive response has been studied using a blue-green silent-substitution-technique on a red background. The aim of this study was to re-evaluate the value of the photopic negative response of the blue-sensitive pathway in glaucoma using a conventional flash-electroretinogram. In 37 eyes of 37 controls (age: 53 +/- 13.6 years) and 37 eyes of 37 patients with open-angle glaucoma of different perimetric visual field defects (age: 58.3 +/- 10 years; MD: 11.7 +/- 6.7 dB) of the Erlangen glaucoma registry Ganzfeld flash-electroretinograms (LKC, UTAS 3000) were recorded using blue Xenon-flashes of increasing photopic luminance (0.013, 0.018, 0.030, and 0.052 cd s/m(2); 440 nm) on a bright yellow background (238 cd/m(2); 550 nm) after 2 min of light adaptation. Amplitudes and implicit times of the photopic negative response and of L&M-cone- and S-cone-driven b-waves were compared between glaucomas and controls for all flash energies (unpaired t-test). The amplitudes of the photopic negative response were significantly reduced in glaucoma patients for all flash energies (P < 0.001). The implicit times of L&M-cone-driven b-wave (0.013, 0.018, 0.030, and 0.052 cd s/m(2)) and S-cone-driven b-wave (0.030 and 0.052 cd s/m(2)) were significantly prolonged in glaucoma patients (P < 0.05). The changes in these implicit times, however, are very small (1.5 ms or less). The other measures did not differ significantly. The amplitude of the photopic negative response and the implicit times of the L&M-cone and S-cone b-wave in the same responses of the blue-on-yellow flash-electroretinogram are potentially useful in the evaluation of inner-retinal function in glaucoma.
Keywords: electroretinogram; glaucoma; L&M-cone; photopic negative response; S-cone

The photopic negative response of the Light-adapted 3.0 ERG in clinical settings - Ortiz, Gonzalo; Drucker, David; Hyde, Connor; Staffetti, Joseph; Kremers, Jan; Tzekov, Radouil (Documenta Ophthalmologica, 2019)
Purpose To analyze the effects of different methods of measurement on the photopic negative response (PhNR), recorded as part of a standard ISCEV Photopic 3.0 ERG responses from patients with a variety of clinical diagnoses. Methods ERGs were recorded from both eyes of 97 patients (187 eyes) as part of a standard clinical assessment. The average age was 56.4 +/- 15.7 years, the gender balance was 35 M, 62F, and only recordable responses of acceptable quality were included. PhNR was measured at an identifiable trough before (PhNR1) and after the i-wave (PhNR2), and the amplitudes and peak times were compared with a-, b- and i-wave corresponding parameters. PhNR components were measured: from baseline and from b-wave peak. Correlation between PhNR troughs and with ERG parameters were tested for right eyes. The possibility to predict and substitute PhNR2 amplitude from PhNR1 amplitude was also tested. Results PhNR1 was recordable in 97.3% of eyes and PhNR2 in 85.6%. An identifiable PhNR2 peak was found to occur before 65 ms at similar to 50% of the records, while in similar to 38% of the cases was within 65-75 ms in similar to 12%-after 75 ms. The correlation between the PhNR1 and PhNR2 peaks was quite strong (with coefficients 0.81-0.98, depending on method of measurement, and slopes close to 1). The average difference between predicted and measured PhNR2 was reasonably small in absolute (< 2 mu V) and relative (< 2%) terms. The correlations between PhNR amplitudes and other ERG component amplitudes showed different ranges of correlation coefficients depending on the method of measurement: for the a-wave amplitudes the range of coefficients was 0.48-0.73, while for the b-wave amplitudes it was 0.30-0.95 and 0.39-0.65 for i-wave. Conclusion The strong correlation between the two PhNR troughs could allow using PhNR1 when PhNR2 is poorly defined due to artifacts. Different methods of PhNR measurement lead to different correlations with other ERG parameters, and this needs to be considered when analyzing and comparing PhNR data between studies.
CRIS-Team WoS Importer:2019-10-25

The Photoreceptor Ribbon Synapse in the Absence of Piccolo: An RNAi Approach - Regus-Leidig, Hanna; Atorf, Jenny; Feigenspan, Andreas; Boye, S.; Chiodo, V.; Seigel, G. M.; Hauswirth, W. W.; Kremers, Jan; Brandstätter, Johann Helmut (Investigative Ophthalmology & Visual Science, 2010)
Keywords: photoreceptors; synapse

The spatial distribution of ERGs reflecting luminance and L-/M-cone-opponent signals - Vidal, Kallene Summer; Aher, Avinash; Ventura, Dora Fix; Kremers, Jan (Documenta Ophthalmologica, 2021)
Purpose: To study the spatial retinal distribution of electroretinographic (ERG) responses that reflect signals in the L-/M-cone-opponent and luminance post-receptoral pathways. Methods: ERG recordings to heterochromatic stimuli (sinusoidal counter-phase modulation of red and green LED light sources) were performed, while varying fractions of red and green modulation. Two temporal frequencies of the stimuli were employed: 12 Hz to record ERGs that reflect L-/M-cone-opponent signal and 36 Hz for recording ERG signals sensitive to stimulus luminance. Stimuli were about 20° in diameter and projected on various retinal locations: the fovea and four eccentricities (10°, 19°, 28° and 35°), each presented nasally, temporally, inferiorly and superiorly from the fovea. Results: The 36 Hz stimuli elicited responses that strongly varied with red fraction and were minimal at iso-luminance. Moreover, response phases changed abruptly at the minimum by 180°. In contrast, the responses to the 12 Hz stimuli had amplitudes and phases that changed more gradually with red fraction. The 36 Hz response amplitudes were maximal close to the fovea and sharply decreased with increasing distance from the fovea. The responses to 12 Hz stimuli were more broadly distributed across the retina. Conclusions: In the present study, it was found that retinal eccentricity and direction from the fovea have distinct effects on ERGs reflecting different post-receptoral mechanisms. The results are in accord with previous findings that ERGs to 12 Hz stimuli are predominantly determined by the red–green chromatic content of the stimuli, thus reflecting activation in the L-/M-cone-opponent pathway, while responses to 36 Hz stimuli manifest post-receptoral luminance-dependent activation. We found that the response in the cone-opponent pathway is broadly comparable across the retina; in comparison, response amplitude of the luminance pathway strongly depends on retinal stimulus position.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Cone opponency; Electroretinography; Luminance; Post-receptoral pathways; Spatial distribution

The Spatial Distribution of L- and M-Cone Driven ERGs Reflecting Parvo- and Magnocellular Activity - Gomes, Bruno; Souza, Givago; Filho, Manoel; Pangeni, Gobinda; Silveira, Luiz Carlos; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2013)
Keywords: 688 retina; 510 electroretinography: non-clinical; 508 electrophysiology: non-clinical

The spatial extent of lateral interactions in flicker perception - Kremers, Jan; Rimmele, Ulrike (Vision research, 2007)
We investigated the influence of the relative phase of a temporally modulated annulus on the perceived flicker strength of a center stimulus having the same temporal modulation. These measurements were performed in two subjects at two temporal frequencies and with different outer diameters of the annulus. The perceived flicker strength was strongly modulated by the phase difference between center and surround stimulus. This modulation depended on the size of the annulus. In the absence of an annulus the perceived flicker strength was not modulated. The modulation initially increased with increasing annulus size and reached a plateau. The space constant of the function describing the modulation as a function of annulus size was about 0.5 degrees and is similar to the sizes of receptive field surrounds of subcortical cells. This finding is in favor of the hypothesis that the physiological basis of the perceived flicker strength in the center stimulus is present already at a subcortical level. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: lateral interactions; flicker; psychophysics; linking hypothesis

The spatial properties of L- and M-cone inputs to electroretinograms that reflect different types of post-receptoral processing - Jacob, Mellina M.; Pangeni, Gobinda; Gomes, Bruno D.; Souza, Givago S.; Da Silva Filho, Manoel; Silveira, Luiz Carlos L.; Maguire, John; Parry, Neil R. A.; Mckeefry, Declan J.; Kremers, Jan (PLoS ONE, 2015)
We studied the spatial arrangement of L- and M-cone driven electroretinograms (ERGs) reflecting the activity of magno- and parvocellular pathways. L- and M-cone isolating sine wave stimuli were created with a four primary LED stimulator using triple silent substitution paradigms. Temporal frequencies were 8 and 12 Hz, to reflect cone opponent activity, and 30, 36 and 48 Hz to reflect luminance activity. The responses were measured for full-field stimuli and for different circular and annular stimuli. The ERG data confirm the presence of two different mechanisms at intermediate and high temporal frequencies. The responses measured at high temporal frequencies strongly depended upon spatial stimulus configuration. In the full-field conditions, the L-cone driven responses were substantially larger than the full-field M-cone driven responses and also than the L-cone driven responses with smaller stimuli. The M-cone driven responses at full-field and with 70° diameter stimuli displayed similar amplitudes. The L- and M-cone driven responses measured at 8 and 12 Hz were of similar amplitude and approximately in counter-phase. The amplitudes were constant for most stimulus configurations. The results indicate that, when the ERG reflects luminance activity, it is positively correlated with stimulus size. Beyond 35° retinal eccentricity, the retina mainly contains L-cones. Small stimuli are sufficient to obtain maximal ERGs at low temporal frequencies where the ERGs are also sensitive to cone-opponent processing.
EVALuna2:21160

Towards an electroretinographic assay for studying colour vision in human observers - Kremers, Jan; Bhatt, Deepak (Documenta Ophthalmologica, 2016)
To determine whether electroretinograms (ERGs) to heterochromatic stimulation can detect and quantify hereditary colour vision deficiency.ERGs were measured to counterphase modulation of red and green stimuli. The total modulation depth of the red and green stimuli was constant. The ratio of red to green modulation was varied, and the responses were measured at two temporal frequencies: 12 and 36 Hz. Subjects were 13 protanopes, 19 protanomalous trichromats, 38 deuteranopes, 16 deuteranomalous trichromats and 22 normal trichromats.The responses are in agreement with previous findings: they were determined by a vector additive input of L- and M-cones (and thus is luminance sensitive) at 36 Hz. At 12 Hz, the responses can be modelled a vector addition of an L-/M-additive response (as determined by the 36 Hz ERGs) and an L-/M-opponent response. From the models, L-cone input fraction (36 Hz) and luminance input fraction (12 Hz) were estimated. The five groups showed different characteristics. However, the signal-to-noise ratio (SNR) at 12 Hz was not always satisfactory.The ERGs to heterochromatic stimuli are potentially interesting for determining the presence and the type of colour vision deficiencies, provided some measures are taken to improve the 12 Hz SNRs.
EVALuna2:21315

Visual Field Progression Rates in Glaucoma Eyes With Progressive Optic Disc Change - Bellios, N.; Horn, Folkert; Lämmer, Robert; Link, B.; Kremers, Jan; Mardin, C. Y.; Junemann, A. G. (Investigative Ophthalmology & Visual Science, 2010)
Keywords: visual fields